Long-term ecotoxicological risk dynamics of pesticide use under contrasting tillage systems in grain cropping systems - Rodrigo de Paula; Felipe Ghersa; María Cintia Palladino; Sebastián Pessah; Alejandra C. Duarte Vera; Diego O. Ferraro (Crop Protection, 2027)

Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Occurrence, typing and inactivation kinetics of Listeria monocytogenes isolated from commercial frozen desserts - Arthur K.R. Pia; Juliana S. Graça; Larissa P. Margalho; Caroline Heckler; Caio H.T. Iwase; Alexandra L.P.M. Amaral; Rodrigo C.L. Pereira; Deyse C. Vallim; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2026)

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

The role of post-flood climate disaster in southern Brazil and its impact on the atmospheric remobilization of trace elements and particulate matter - Kassiano S. Sousa; Antonio Azeredo; Gilberto Fillmann; Adan S. Lino; Rodrigo O. Meire; Daniela C. Oliveira; Janeide Padilha; Enrico M. Saggioro; Carla Sirtori; Suélem Soares; Cláudia Teixeira; José Araújo Souto-Neto; et al. (Atmospheric Pollution Research, 2026)

A Design and Life Cycle Assessment Framework for Electrochemical Ozone-based Indoor Air Treatment in Hospitals - V. Pertegal; S. E. Correia; A. Rodríguez-Gómez; C. M. Fernández-Marchante; M. A. Rodrigo; C. Sáez; E. Lacasa (Environmental Processes, 2026)

Evaluation of deep learning-based pipelines for salmon segmentation and multi-object tracking in commercial aquaculture cages - Martin Campos; Juan C. Aguilera; Marcos D. Zuniga; Luis F. Leiva; Julio Lopez; Nicolas Jara; Mohamed A. Ahmed; Manuel Pedraza; Alexis Alva; Rodrigo Carvajal; Gonzalo Carvajal (Aquacultural Engineering, 2026)

Toxicity of synergized permethrin residues in cattle dung to two temperate dung beetle species after application of common livestock pour-on treatment - Michael C. Cavallaro; Michelle L. Hladik; Rodrigo Soares; Mikaela Anderson; W. Wyatt Hoback (Agriculture, Ecosystems & Environment, 2026)

Advancing wastewater sustainability through electro-refineries: Oxalic acid valorization - Rainy Alves de Sousa; Suelya da S. Mendonça de Paiva; Raúl García-Cervillla; Jussara C. Cardozo; Carlos A. Martínez-Huitle; Elisama V. dos Santos; Justo Lobato; Manuel A. Rodrigo (Journal of Environmental Chemical Engineering, 2026)

First plastome assembly of rice cytoplasmic male sterility (CMS) A/B lines reveals wild maternal origin - Renerio P. Gentallan; Edelweiss E. Sajise; Juan Rodrigo A. Vera Cruz; Bjorn Q. Manuel; Kristine Joyce O. Quiñones-Arribado; Jeremaiah L. Estrada; Emmanuel Bonifacio S. Timog; Patricia Izabelle M. Lopez; Wendy A. Gaspar; Sancho G. Bon; Mark Ian C. Calayugan; Teresita H. Borromeo (Genetic Resources and Crop Evolution, 2026)

Clomiphene citrate versus testosterone replacement therapy in male hypogonadism: a systematic review of literature and meta-analysis - Beatriz T. Constantinou; Bianca C. Benedicto; Lilian Galligani; Beatriz N. Schiavon; Caio M.O Mendes; Maria Micaela G. Petri; Beatriz Uzueli; Ronaldo Soares Maia; Rodrigo Afonso Silva da Sardenberg; Renato Fraietta; Jose Arnaldo Shiomi da Cruz (European Journal of Clinical Pharmacology, 2026)
Introduction Male hypogonadism, including age-related and functional forms, is characterized by insufficient testosterone production often associated with obesity and metabolic comorbidities. Testosterone replacement therapy (TRT) increases serum testosterone but suppresses spermatogenesis and may cause adverse effects. Selective estrogen receptor modulators (SERMs), such as clomiphene citrate, have emerged as an alternative approach to restore endogenous testosterone while preserving fertility. This study aimed to compare the efficacy of clomiphene citrate versus testosterone replacement therapy (TRT) in increasing serum testosterone levels in men with hypogonadism. Methods We conducted a systematic review of the literature in PubMed, Embase, Scopus, The Cochrane Library, and Google Scholar to identify studies comparing clomiphene citrate and testosterone replacement therapy (TRT) in men with male hypogonadism’. The primary outcome was the change in serum testosterone levels before and after treatment. Secondary outcomes included variations in other hormonal parameters, and clinical symptom improvement assessed through standardized instruments. Results A total of 11 studies with 1512 patients were included (764 on clomiphene citrate; 748 on testosterone replacement therapy, TRT). For serum testosterone, the overall pooled effect showed no significant difference between clomiphene and TRT (MD = 6.64 ng/dL; 95% CI -35.35 to 48.63; I² = 80.6%). Subgroup analyses indicated injectable testosterone achieved higher levels than clomiphene (1 study, 62 patients; MD = -290.50; 95% CI -518.78 to -62.22), whereas gel-based TRT showed no difference (8 studies, 1012 patients; MD = 24.29; 95% CI -18.91 to 67.48; I² = 76.1%). For sexual function, three studies (199 patients; 85 on clomiphene; 114 on TRT) assessing post-treatment libido (ADAM 1–5) showed lower libido scores with clomiphene than TRT (MD = − 0.54; 95% CI − 0.87 to − 0.21; P = 0.009; I² = 18.8%). Conclusions No statistically significant difference in serum testosterone levels was observed between clomiphene citrate and testosterone gel, although the evidence is limited by high heterogeneity and some concerns to high risk of bias. TRT was associated with greater improvements in libido. These findings should be interpreted as preliminary, and large-scale randomized trials incorporating clinical and fertility endpoints are needed.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Risk of failure of insecticides and Cry/Vip Bt maize hybrids to control field populations of fall armyworm in Brazil - Josélia C.O. França; Hugo M. Monteiro; Rafael M. Pitta; Simone M. Mendes; João G.T. Moraes; Arleide F. Neto; Royner J. Ortiz-Rojas; Rodrigo J.S. Satolo; Leidiana M. Ribeiro; Yann J.M. Campos; Thadeu C. Souza; Eliseu J.G. Pereira (Crop Protection, 2026)

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

Influence of carbohydrate on the microparticulation process of whey proteins: structural modifications and indicators of the Maillard Reaction - Igor L. de Paula; Natalia C. Mesa; Alan F. Wolfschoon-Pombo; Uwe Schwarzenbolz; Thomas Henle; Ítalo T. Perrone; Luiz Fernando C. de Oliveira; Rodrigo Stephani (International Dairy Journal, 2026)

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Patterns of resource use in loggerhead turtle (Caretta caretta) from the Southwestern Atlantic Ocean - Celina Carolina Almeida; Rodrigo F. Bastos; Sérgio C. Estima; Andrine Paiva da Silva; Gabriela M. Vélez-Rubio; Danielle S. Monteiro (Marine Biology, 2026)
The Southwestern Atlantic Ocean (SWAO) is an important feeding and developmental area for loggerhead turtle ( Caretta caretta ). However, long-term patterns of resource use across life stages and sexes remain poorly understood for the species in this region. Here, we used stable isotope analysis (SIA) of sequential layers of carapace scutes to investigate resource use of loggerhead turtles in the SWAO across life stages and sexes. Scute samples were collected from 42 individuals stranded or incidentally caught by pelagic longline and bottom pair trawl fishery in southern Brazil and Uruguay (from 31º21′S–51º05′W to 34º55′S–56º09′W), between 2013 and 2024. Cluster analysis based on δ¹⁵N values revealed two distinct groups, corresponding to oceanic and neritic foraging habitats, whereas linear mixed models indicated ontogenetic increases in δ¹³C and δ¹⁵N values consistent with habitat shifts. Significant differences between sexes were observed only for δ¹³C values. Bayesian mixing models (MixSIAR) were used to estimate prey contributions to the diet, based on isotopic values from the literature, revealing a dominance of pelagic prey in oceanic non-shifters and of benthic invertebrates in neritic non-shifters. Shifters showed a transition from oceanic to neritic habitats, with a dietary shift from pelagic to benthic prey, reflecting two main ontogenetic shift patterns: discrete and facultative. Our results enhance the understanding of life-history variation in loggerhead turtles and highlight that sequential analysis of carapace scutes is a valuable tool for reconstructing long-term resource use patterns, providing a broader view of the ecology of this long-lived and endangered species.

Time‐calibrated relationships of a rare cave catfish ( Trichomycterus rubbioli ): Shedding light on troglobitic lifestyle origin in the Brazilian caatinga - Wilson J. E. M. Costa; Paulo J. Vilardo; José Leonardo O. Mattos; Axel M. Katz; Valter M. Azevedo‐Santos; Pedro L. C. Uzeda; Rodrigo L. Ferreira (Journal of Fish Biology, 2026)
Catfishes of the subfamily Trichomycterinae comprise the most diverse fish group with species adapted to live in Neotropical caves, but past evolutionary scenarios that have driven the origin of these troglobitic species remain unknown. We herein investigate the phylogenetic position of the cave‐restricted Trichomycterus rubbioli , endemic to the semi‐arid Caatinga of northeastern Brazil, through a time‐calibrated molecular phylogenetic analysis of a broad sample of trichomycterine taxa (84 spp), using two nuclear and two mitochondrial genes (3030 bp). The analysis supported T. rubbioli as a member of the Trichomycterus s.s. clade endemic to eastern South America and an early Miocene origin for the T. rubbioli lineage. The combination of available data suggests that the T. rubbioli lineage adapted to the troglobitic lifestyle between the Middle and Late Miocene, a period when the semi‐arid conditions of the Caatinga biome became established and consequently streams of the region became seasonal. This past scenario would be responsible for extinction of epigean trichomycterines while preserving the lineage within the cave system. Morphological characters of the troglobitic ‘Trichomycterus’ itacarambiensis from the transition area between the Cerrado and the Caatinga indicate distant relationships with T. rubbioli , suggesting an independent evolutionary event of cave colonization.

Ant‐Mediated Ecosystem Functions Along a Tropical Elevational Gradient - Chaim J. Lasmar; Mariana A. Rabelo; Tom R. Bishop; Catherine L. Parr; Icaro Wilker; Antônio C. M. Queiroz; Mayara M. G. Imata; Guilherme P. Alves; Gabriela B. Nascimento; Vanessa L. Resende; Rodrigo M. Feitosa; Carla R. Ribas (Journal of Biogeography, 2026)
Aim Elevational gradients are excellent systems to study biodiversity variation, yet the ecosystem functions performed by animals along these gradients are poorly understood. We assessed tropical elevational patterns of ant‐mediated seed removal, insect predation and the phylogenetic diversity of the local ant assemblages performing these functions as well as the effects of climate and productivity. Location Southeast Brazil, Atlantic Forest. Taxon Ants. Methods We sampled ant‐mediated seed removal and insect predation across 20 transects, comprising an elevational gradient of approximately from 0 to 1000 m a.s.l. We extracted standardized phylogenetic metrics of the assemblages performing the functions: Faith's PD (SES PD), mean pairwise distance (SES MPD), and mean nearest taxon distance (SES MNTD). We also extracted climatic and productivity predictors for each transect. We then used generalized additive models to evaluate the responses of each function and their phylogenetic metrics along elevation, climate and NPP. Results Both ant‐mediated functions and species richness decreased along the elevational gradient, peaking at the same mid‐elevation, while SES MNTD increased linearly with elevation. Both ant‐mediated functions were positively correlated with temperature. However, we found that phylogenetic richness (SES PD) was lower in warmer and more seasonal environments, while phylogenetic divergence (SES MNTD) was also lower in warmer but drier environments. Main Conclusions Our findings suggest that diversity is linked to ecosystem functioning along the elevational gradient. Although high‐elevation assemblages may show greater evolutionary potential because they comprise distantly related taxa, ecosystem functions might be more vulnerable to species loss. Additionally, we highlighted that although elevated temperatures may boost ecosystem functioning in the short term, when acting together with increased seasonality and dryness, as expected under climate change, they could heighten the vulnerability of the ants responsible for these functions, potentially compromising ecosystem resistance and resilience in a changing world.

Climate Vulnerability of Australian Seafood Systems: A National Assessment of Exposure and Adaptive Capacity - Stephanie Brodie; Laura K. Blamey; Ana Bugnot; Rodrigo H. Bustamante; Julia L. Blanchard; Lara Buhagiar; Elizabeth A. Fulton; Alistair J. Hobday; Éva E. Plagányi; Anthony J. Richardson; Richard Matear; Skipton N. C. Woolley; et al. (Fisheries Oceanography, 2026)
Marine waters are becoming warmer and acidified and experiencing more intense and longer heatwaves under climate change. These changes are already impacting marine ecosystems and seafood production, which are vital for supporting food security and economic productivity. For Australia, a national‐scale assessment of exposure to climate hazards is needed to support climate‐resilient ecosystem management across one of the world's largest exclusive economic zones. Commercial fishing relies on healthy ecosystems and is one of Australia's most important sectors in terms of cultural identity and regional value. However, Australian fisheries and aquaculture are increasingly exposed to climate‐driven changes in ocean conditions, creating substantial risks for marine ecosystems, seafood production and coastal economies. We assess the exposure of Australia's seafood sector to climate change using high‐resolution climate projections and ecosystem model outputs under three global warming levels (1.5°C, 2°C and 3°C futures). Our findings reveal that the entire Australian exclusive economic zone is exposed, with cumulative exposure highest for regions with a large continental shelf. The biomass available to fisheries is projected to decline. Negative impacts from climate change are generally expected for fisheries and aquaculture production. Despite some evidence of adaptation, uneven adaptive capacity across sectors and jurisdictions presents challenges for climate resilience. This study underscores the urgency of global mitigation efforts to reduce risk, coordinated adaptation strategies, improved coastal hazard modelling and ecological risk assessments to safeguard the future of fisheries and aquaculture industries under climate change.

A novel hunting‐by‐riding association of reef fishes mediated by habitat complexity - Guilherme M. Castro; Ivan M. Carneiro; Fernando C. Cardoso; Rodrigo L. Moura (Ecology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

First highly pathogenic avian influenza outbreak in a commercial poultry farm in Brazil: Outbreak timeline, control actions, risk analysis, and transmission modeling - Nicolas C. Cardenas; Francisco P.N. Lopes; Paulo A.S.C. de Souza; Fernando H.S. Groff; Ananda P. Kowalski; Alessandra Krein; Grazziane Rigon; Rodrigo N. Etges; Daniela L. de Azevedo; Alencar Machado; Vinícius Maran; Felipe A. Machado; et al. (Preventive Veterinary Medicine, 2026)

Bioluminescent diversity and ecotourism potential in the Juréia-Itatins Ecological Station, integrating conservation and sustainable development - Danilo T. Amaral; Rodrigo O. Castro; João Roberto Fentanes-Machado; Lara C. Muniz; Isabel A.S. Bonatelli (Journal for Nature Conservation, 2026)

Extralimital records of Antarctic seals in South America - Andrea Elissamburu; María A. Mandiola; Joaquín C. M. Gana; Pablo Denuncio; Gisela V. Giardino; M. Carolina De León; Mariela Dassis; Antonella D. Padula; Ricardo Bastida; Sergio Morón; Sergio Rodríguez Heredia; Mauricio Failla; et al. (Polar Biology, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

From maleic to succinic acid: Electrochemical reduction as a game-changer for green electro-refinery schemes - Suelya da S. Mendonça de Paiva; Rainy Alves de Sousa; Raúl García-Cervillla; Jussara C. Cardozo; Carlos A. Martínez-Huitle; Elisama V. Dos Santos; Justo Lobato; Manuel A. Rodrigo (Journal of Cleaner Production, 2026)

Metagenomic analysis of the tomato microbiome in Colombia reveals bacterial diversity, potential pathogens, and resistance determinants - Yefferson Enciso-Rodríguez; Rodrigo Echeverry-Gallego; Diego C. Franco; Jimena Sánchez; Alejandro Moncayo-Lasso; Diana Martínez-Pachón; Javier Vanegas (Food Research International, 2026)

Influence of agricultural residues on the formation of TiO2 phases: Real-time in situ X-ray diffraction monitoring in a reaction chamber - Rodrigo P. Feitosa; Johar Amin Ahmed Abdullah; Ramón R. Peña-Garcia; Maria G. Fonseca; Edson C. Silva-Filho; Santiago Medina-Carrasco; Maria del Mar Orta Cuevas; Josy A. Osajima (Chemical Engineering Journal, 2026)

Molecular detection of Escherichia coli virulence factors in swine isolates: A systematic review and meta-analysis - Elisa De Conti; Rodrigo C. Paiva; Brad Kuennen; Giovani Trevisan; Daniel C.L. Linhares; Annette M. O’Connor; Marcelo N. Almeida (Veterinary Microbiology, 2026)

Oxidative technologies for olive grove soils: Impacts of electrogenerated H2O2 and O3 on pesticide degradation and ecosystem health - C. Navas-Higuero; B.A. Tiban; V. Valenzuela-Polo; M.I. Reyes-Alcalde; A.J. Manzaneda; A.J. Rascón; J.F. García-Reyes; R. Salazar-García; J.E. Palomares-Rius; E. Lacasa; M.A. Rodrigo; C. Saez (Journal of Environmental Chemical Engineering, 2026)

A new approach for HEMS to optimize cost, emissions and comfort through a smart integration of V2G, load scheduling, and PVT generation - Rodrigo Fiorotti; Jussara F. Fardin; Helder R.O. Rocha; Augusto C. Rueda-Medina; Antonio M. Pantaleo; Mohammad R. Nasab; Sergio Bruno (Energy and Buildings, 2026)

Hydrodynamic and water quality modelling of a free water surface constructed wetland for urban runoff mitigation - A. Martínez-Biosca; C. Hernández-Crespo; E. Asensi; I. Andrés-Doménech; M.Eugenia Rodrigo-Santamalia; V. Benedito-Durá; M. Martín (Ecological Modelling, 2026)

The dynamics of coastal macroalgal assemblages after the Fundão dam disaster: challenges and lessons from impact assessment - Ivan M. Carneiro; Guilherme M. Castro; Fernando C. Cardoso; Julia P. Curvêllo; Rodrigo T. Carvalho; Leonardo T. Salgado; Julia Kaiser; Paulo S. Salomon; Rodrigo L. Moura (Environmental Monitoring and Assessment, 2026)
Anthropogenic marine disasters impair biodiversity, ecosystem services provisioning, and socioeconomic development, with long-lasting consequences. Robust impact assessment, however, depends on understanding the spatiotemporal variability of the indicators used to detect change. Here, we present the results of a monitoring program (2018–2025) targeted at two Coastal and Marine Protected Areas located 40 km south of the Doce River mouth (Eastern Brazil), which were affected by the discharge of iron ore tailings from the Fundão dam collapse in 2015. Besides assessing the dynamics of the benthic assemblages, we revealed a high variability among sampling units (residual), along with relevant variability across seasons, sites, and their interactions. Wave height and distance from rivers were the most influential drivers explaining assemblage variability. Before–after contrasts based on pre-disaster data from the literature indicate shifts in the assemblage structure. However, because baseline data are limited, the observed changes cannot be conclusively attributed to the disaster. An overview of marine areas under long-term ecological monitoring in Brazil revealed a concerning mismatch with the distribution of mining, oil and gas, port, and nuclear activities. Rethinking funding for baseline data collection and monitoring of disaster-prone marine areas, primarily from industries that are often responsible for marine disasters, constitutes a necessary step toward effective solutions.

Non-native mollusc species in Brazil: a first national inventory and distributional overview - Fabrizio Marcondes Machado; Rodrigo B. Salvador; Igor C. Miyahira; Luiz Ricardo Lopes de Simone; Tarcilla C. de Lima; Mariana Osório Côrtes; Julia D. Sigwart; Angie Patiño Montoya; Vanessa S. Amaral; Paula Spotorno; Marcel Sabino Miranda; Augusto L. Ferreira Júnior; et al. (Biological Invasions, 2026)

Invasive Fishes Interact With Temperature to Reshape Community Size Structure Across Climatic Zones - Barbbara Silva Rocha; Ignasi Arranz; Henrique C. Giacomini; Daniel M. Perkins; Gilberto Nepomuceno Salvador; José Luís Costa Novaes; Jorge Iván Sánchez‐Botero; Angelo Antonio Agostinho; Paulo Santos Pompeu; Rosemberg Fernandes Menezes; Silvia Yasmin Lustosa‐Costa; Telton Pedro A. Ramos; et al. (Global Change Biology, 2026)
The body size spectrum (or individual size distribution) is a simple yet widely recognized approach that links individual and population traits to community structure and ecosystem functions, making it a valuable indicator of anthropogenic effects. However, the assessment of size spectra in the context of biological invasions remains poorly explored. We investigated the impacts of non‐native (NN) fish invasions on the size structure of 667 lacustrine fish communities across climatic regions (temperate, tropical, and subtropical systems) and the roles of trophic position and temperature in modulating these effects. We found that fish communities under higher invasion pressure exhibit flatter, or less negative, size spectrum exponents. Also, NN species from lower trophic levels can have greater impacts than piscivorous NNs by reshaping size spectra and reducing the overall biomass of native communities. We also observed that piscivore NNs and NNs from lower trophic levels interacted positively with temperature to drive the size spectrum exponent and total biomass of the native communities, respectively. These results can be explained by two main mechanisms: (i) NN piscivores primarily act through size‐selective predation (top–down control), which may be intensified particularly on small prey in warmer lakes, and (ii) NN fish from lower trophic levels primarily act through competition, hence reducing the numerical abundance of small‐sized native fish, which may be more vulnerable in colder and less productive lakes. These mechanisms are leading to flatter size spectrum exponents mainly at higher temperatures and to a decline in the total biomass of the native community, mainly at lower temperatures, effectively reversing the expected temperature–size rule pattern. By disentangling the trophic and temperature‐dependent mechanisms through which NN fishes affect size structure, this study strengthens our ability to anticipate the impact of biological invasions on freshwater communities and their ecosystem functions and services under global change.

How scientists can make the case for international cooperation in an age of diplomatic retrenchment - James A. Dubovsky; Juanita Sundberg; Rodrigo A. Medellín; Jonathan J. Derbridge; Brady J. Mattsson; Charles C. Chester; Laura López‐Hoffman (Conservation Biology, 2026)

Red Aroeira (Schinus terebinthifolia)-based zinc oxide nanoparticles: A green approach to combat fish pathogens - Cindy C.M. Santos; Peterson E.G. Paixão; Juliana O. Meneses; Joel A.R. Dias; Amanda S. Carvalho; Hugo Leandro dos Santos; Thigna de Carvalho Batista; Patricia Severino; Eliana B. Souto; Juliana C. Cardoso; Rodrigo Y. Fujimoto (Environmental Toxicology and Pharmacology, 2026)

The Marsupial Database: A comprehensive dataset on the ecology and life history of American and Australasian marsupials - Mariana Silva Ferreira; Rodrigo C. Rossi; Stephane Batista; Kathleen Sena; Kevin R. Bairos‐Novak; Shamia Farhana Shoma; Natália O. Leiner; Diego Astúa; Graeme Coulson; Diana O. Fisher; Natasha D. Harrison; Julian Nicholas Garcia Willmer; et al. (Ecology, 2026)
Marsupials are an important but typically neglected group of mammals that have been overlooked in many comparative analyses of vertebrate ecology and life history evolution. In order to address this knowledge bias, we have developed The Marsupial Database. The Marsupial Database contains traits for a phylogenetically diverse set of 414 extant and recently extinct (last 200 years) species from all seven modern marsupial orders (Dasyuromorphia, Didelphimorphia, Diprotodontia, Microbiotheria, Notoryctemorphia, Paucituberculata, Peramelemorphia) native to 34 countries in the Americas and Australasia. The database comprises 11,054 records of 35 traits describing anatomical, physiological, phenological, and reproductive characteristics, as well as information on species' ecology and current conservation status. Data were collected from 41 sources, comprising published databases and other relevant sources of information. By providing a centralized repository of marsupial ecological and life history traits, The Marsupial Database facilitates analyses of ecological and evolutionary patterns within the group, and also encourages inclusion of marsupials in comparative studies of mammals, vertebrates, and the entire animal kingdom. The Marsupial Database is free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Calibration transfer from HPGe to NaI(Tl) detectors for radionuclides quantification - João M.F. Lopes; Fábio L. Melquiades; Rodrigo O. Bastos; Angelo Z. Neto; Avacir C. Andrello (Journal of Environmental Radioactivity, 2026)

Mercury concentration: A new window into ancient diets and trophic levels in vertebrate paleontology - Felipe M.S. Cardia; José Vicente E. Bernardi; Carlos Eduardo M. Oliveira; Marco B. Andrade; Max C. Langer; Sandra A.S. Tavares; Fabiano V. Iori; William R. Nava; Thiago S. Marinho; Luiz Carlos B. Ribeiro; Jurandir R. Souza; Rodrigo M. Santucci (Chemical Geology, 2026)

Same-sex sexual behavior in a male-dimorphic arachnid with a resource-defense polygyny: evidence for female mimicry? - Diego Solano-Brenes; Cláudia M. Furlan; Rafael C. da Silva; Rodrigo H. Willemart; Fábio S. Nascimento; Glauco Machado (The Science of Nature, 2026)

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Tackling CECs and antimicrobial resistant bacteria in hospital wastewater using biological and AOP hybrid technologies - Eloísa Stéphanie da Silva; Alessandra S. Martins; Lara Fabian S. Ribeiro; Jhonatha Rodrigo Cordeiro-Moura; Daniel A.S. Rodrigues; Renata Cristina Picão; Maria Clara V. M. Starling; Camila C. Amorim (Bioresource Technology, 2026)

Synergistic Experimental and Theoretical Studies on Pesticide Detection in River samples Using Faujasite-CTAB Modified Carbon Paste Electrode - Cybelle C. C. M. Barbosa; Barbara L. Ramos; Elivelton A. Ferreira; Rodrigo G. Amorim; Ramon S. da Silva; Rodrigo Della Noce; Adriana E. de Carvalho; Mendelssolm K. de Pietre (Water, Air, & Soil Pollution, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

First At‐Sea Identifications of Ginkgo‐Toothed Beaked Whale ( Mesoplodon ginkgodens ): Acoustics, Genetics, and Biological Observations Off Baja California, México - E. Elizabeth Henderson; Lisa T. Ballance; Gustavo Cárdenas‐Hinojosa; Jay Barlow; Annamaria I. DeAngelis; Sergio Martínez‐Aguilar; Craig Hayslip; L. Todd Pusser; Mario Márquez Segovia; C. Scott Baker; Debbie Steel; Rodrigo Huerta‐Patiño; et al. (Marine Mammal Science, 2026)
In 2024, an expedition was conducted off northwestern Baja California, México, to find and identify the beaked whale species that produced the BW43 echolocation pulse previously recorded in this area and elsewhere in the North Pacific. There were five Mesoplodon sightings and 21 BW43 acoustic detections on both a towed array and drifting pole buoy recorders over the course of the survey. Three of the sightings had concurrent acoustic detections, and a biopsy sample and environmental DNA were also collected from one of the sightings. The genetic identification confirms that the Mesoplodon sighted and acoustically recorded was the ginkgo‐toothed beaked whale ( Mesoplodon ginkgodens ), and the co‐occurrence of these sightings with the BW43 acoustic detections definitively links the species and its echolocation pulse. This is the first time that genetically confirmed ginkgo‐toothed beaked whales have been observed at sea and definitively linked to the BW43 pulse. This paper details the encounters, acoustic behavior, genetics, coloration, and external morphology of this species, including a comprehensive review of its distribution using historical sightings, strandings, and acoustic detection data from the North Pacific Ocean.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

In vitro and in silico schistosomicidal activity of hexane fraction from Copaifera oblongifolia leaves - Rafael Corrêa Ramos; Lizandra G. Magalhães; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio; Híllary Ozorio Gobeti Caprini; Cibelle Ramos Da Silva; Jairo K. Bastos; Márcio L. Andrade e Silva; Erdi Can Aytar; Mario F. C. Santos; Wilson R. Cunha (In Silico Pharmacology, 2025)

Vegetation type and climate determine temperature thresholds of soil respiration across drylands - María Almagro; Ana Rey; Rosa M. Inclán; Josep Barba; Rodrigo Vargas; Arnaud Carrara; José M. Grünzweig; Marcelo Sternberg; Yiftach Talmon; Rebecca L. McCulley; Sara Marañón-Jiménez; Penélope Serrano-Ortiz; et al. (Soil Biology and Biochemistry, 2025)

Plastic waste leakage in the oceans: Socioeconomic influences, predictive modeling with artificial intelligence and wavelet analysis - Iwldson G.S. Santos; Adalgiza Fornaro; Daniel C. Zacharias; Ana L.F. Nascimento; Inaura P.S. Santos; Isnaldo I. Barbosa; José F. Oliveira-Júnior; Micejane S. Costa; Marcos F.M. Ferreira; Rodrigo M.S. Brito (Regional Studies in Marine Science, 2025)

An uncommon large Eocene wood boring from the Antarctic Peninsula: Evidence of a giant teredinid bivalve? - Jorge Villegas-Martín; Leslie M.E. Manríquez; Bruna C. Schneider; Gerson Fauth; Rodrigo do Monte Guerra; Rodrigo S. Horodyski; Karlos G.D. Kochhann (Palaeoworld, 2025)

A multi-step forecasting framework for short-term flocculation modelling in water treatment using attention-enhanced hybrid deep learning and image analysis - Abayomi O. Bankole; Rodrigo Moruzzi; Rogério G. Negri; Soroosh Sharifi; Afolashade R. Bankole; Luiza C. Campos (Journal of Environmental Chemical Engineering, 2025)

Two-phased ITCZ-driven upper salinity stratification in the western equatorial Atlantic during Heinrich Stadial 11 - Marília C. Campos; Rodrigo A. Nascimento; Tainã M.L. Pinho; Laura Kraft; Stefano Crivellari; Svetlana Radionovskaya; Luke Skinner; Bruna B. Dias; Rodrigo C. Portilho-Ramos; Gelvam A. Hartmann; Paul A. Baker; Cleverson G. Silva; et al. (Global and Planetary Change, 2025)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Delayed embryonic attachment, circulating pregnancy-associated glycoproteins, and pregnancy loss in heifer embryo recipients - João Paulo N. Andrade; Rafael R. Domingues; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

Carcass traits and tissue composition of commercial cuts in hair lambs of different genetic groups finished at 50 kg: Multivariate approach - Rodrigo Portillo Salgado; Juan Escobedo Canul; Ángel C. Sierra Vásquez; Dany A. Dzib Cauich; Alfonso J. Chay Canul; Gaspar M. Parra Bracamonte; Raciel J. Estrada León (Small Ruminant Research, 2025)

Local and climatic drivers of coral growth in Southwestern Atlantic turbid-zone reefs - Ludmilla N. Falsarella; Gabriel O. Cardoso; Pamela M. Chiroque-Solano; Lelis A. Carlos-Júnior; Fernando C. Cardoso; Milton Kampel; Alex C. Bastos; Rodrigo L. Moura (Estuarine, Coastal and Shelf Science, 2025)

A comprehensive approach to evaluate environmentally adaptive façade concepts through the use of fundamental environmental conditions - Rodrigo Arauz; Elaheh Mehdizadeh; Alessandro Fascetti; Evgeni Filipov; Dale T. Clifford; John C. Brigham (Energy and Buildings, 2025)

Historical Fragmentation in Atlantic Forest Explains the Diversification of a Clade of Mountaintop Bromeligenous Frogs (Leptodactylidae: Crossodactylodes ) - Marcus Thadeu T. Santos; Marcelo Gehara; Caroline B. Oswald; Rodrigo B. Ferreira; Fabrício R. Santos; Paulo C. A. Garcia; Kelly R. Zamudio; Célio F. B. Haddad; Rafael F. Magalhães (Zoologica Scripta, 2025)
The Atlantic Forest domain is a biodiversity hotspot with remarkable amphibian diversity, including over 700 species, 70% of which are endemic. Most of these endemic species have restricted geographic ranges, often confined to mountainous areas, as exemplified by the leptodactylid genus Crossodactylodes . These frogs are characterised by small body sizes, a bromeligenous habit and limited dispersal abilities, with species often restricted to their type localities. Previous studies have revealed geographically structured lineages within the genus, even when separated by short distances. Here, we focused on a clade of Crossodactylodes comprising three lineages from southeastern Brazil, inhabiting montane forest ‘islands’ distinct from surrounding lowland areas regarding vegetation structure and microclimate. We integrated genetic, geographic, morphometric and qualitative morphological data to assess species boundaries through species delimitation analyses and validation procedures. This integrative approach provided evidence supporting the recognition of one lineage as a distinct taxonomic entity, which we formally describe herein as Crossodactylodes alairi sp. nov. Additionally, we applied coalescent simulations and supervised machine‐learning approaches to evaluate alternative diversification hypotheses. Our results provide strong support for fragmentation models, suggesting that divergences within the focal lineages were driven by climate‐related habitat fragmentation during the Plio‐Pleistocene. Given that these lineages inhabit a non‐macrorefugium region of the Atlantic Forest, their evolutionary trajectories were likely shaped by survival in isolated microrefugia that offered stable and suitable microclimatic conditions amidst broader environmental changes.

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Bio-based polyurethane coatings for controlled-release phosphorus fertilizers: Synthesis, characterization and effect on P use efficiency - Eduardo Lopes Cancellier; Fien Degryse; Rodrigo C. da Silva; Roslyn Baird; Douglas Guelfi; Mike J. McLaughlin (Science of The Total Environment, 2025)

Age-related Changes in Dehydroepiandrosterone-sulfate in Black-and-gold Howler Monkeys (Alouatta caraya) - Josi T. Melo; Gessiane P. Silva; Ana K. F. Pereira; Aline A. Imbeloni; Emilee N. Hart; Abbigail Swiney; Rodrigo H. F. Teixeira; Frederico O. B. Monteiro; Rafaela S. C. Takeshita (International Journal of Primatology, 2025)
Dehydroepiandrosterone-sulfate (DHEAS) is the most abundant steroid in humans and some nonhuman primates. This adrenal androgen contributes to immune enhancement, neuroprotection, and reproduction. In humans and apes, DHEAS levels increase before puberty, a phenomenon called adrenarche. However, a postnatal increase in the levels of these hormones is not apparent in cercopithecoids. In marmosets, DHEAS is only synthesized from female adrenal glands, if their ovarian function is compromised. However, DHEAS is poorly investigated among other platyrrhines. Our main objective was to test the influence of sex and age on fecal and serum DHEAS levels in black-and-gold howler monkeys ( Alouatta caraya ) under human care. We measured DHEAS levels in feces from 16 females and 21 males aged between 6 months and 26 years old and in serum from 27 of those animals using a commercial enzyme immunoassay kit. We found high levels of serum DHEAS in adult females, and DHEAS levels in fecal and serum samples were strongly and positively correlated. Fecal DHEAS levels showed a quadratic relationship with age, increasing from infancy to adulthood, then declining in older adults. There was no significant effect of sex, although females had a greater range than males. The postnatal increase in DHEAS levels in howler monkeys is like that of apes and humans, while the large variation in DHEAS levels among adult females suggests that, as in marmosets, DHEAS may be important for female howler monkey reproduction. This pattern highlights the importance of comparative studies to investigate the biological function of DHEAS in evolution. Graphical Abstract

Effects of prolonged unsaturated fatty acid supplementation on reproductive competence and metabolic profiles in serum and follicular fluid of Holstein heifers - Lenita C. Verdurico; Caio S. Takiya; Alanne T. Nunes; Tiago A. Del Valle; Filipe Zanferari; Rodrigo Gardinal; Gustavo D. Calomeni; Elmeson Ferreira de Jesus; Guilherme G. Silva; Larissa Vitória Franco da Cruz; Francisco P. Rennó (Animal Reproduction Science, 2025)

Ovarian superstimulation for in vitro embryo production based on Anti-Müllerian hormone phenotype: Effect of FSH dose schedule - Jessica C.L. Motta; Rodrigo V. Sala; Cameron B. Hayden; Daniela C. Pereira; Vanessa C. Fricke; Victor A. Absalón-Medina; Pablo J. Ross; Alvaro García-Guerra (Animal Reproduction Science, 2025)

Break the Political Deadlock on Drought Through an Integrated Policy Approach - Lindsay C. Stringer; Johannes Kruse; Mariam Akhtar-Schuster; Rodrigo Andrade Ramirez (Anthropocene Science, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

210Pb chronology assessing the historical microplastics dynamics and aging effects in urban areas with separate sewer systems and multiple-use reservoir - Fabiano T. Conceição; Alexandre M. Fernandes; Sarah G. Lacerda; Rodrigo B. Moruzzi; Naiara O. Santos; Rosa Busquets; Luiza C. Campos (Journal of Hazardous Materials, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Bismuth release from endodontic materials: Proposed mechanisms for systemic circulation and organ accumulation - Lauter Eston Pelepenko; Benjamin Hewitt; Rodrigo Bueno de Oliveira; Brenda Fornazaro Moraes; Débora C. Coraça-Huber; Ana Cristina Padilha Janini; Marina Angélica Marciano (Journal of Hazardous Materials, 2025)

Landowner willingness to adopt active management practices in the Cross-Timbers forests in USA - Chamali Rodrigo; Omkar Joshi; Neelam C. Poudyal; Aaron Russell; Andres Susaeta (Forest Policy and Economics, 2025)

Bridging biocatalysis and chemical catalysis: Innovative approaches for enhancing chemoenzymatic cascades - Alexandre S. França; Gabriela C. Breda; Ivaldo Itabaiana; Rodrigo O.M.A. de Souza (Current Opinion in Green and Sustainable Chemistry, 2025)

Soil carbon and nutrient stocks under intensified pasture and sugarcane expansion - Luiza Pecci Canisares; Eduardo Mariano; Adibe L. Abdalla-Filho; Lucas P. Canisares; Mauricio C. A. Leite; Maria G. S. Araújo; Rodrigo F. Almeida; Taciana F. Gomes; Érika S. P. B. Saldanha; Luiz A. Martinelli (Nutrient Cycling in Agroecosystems, 2025)

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

A validated ultra-performance liquid chromatography with tandem mass spectrometry method for the quantification of Brazilian green propolis main compounds - Mário Ferreira Conceição Santos; Giulia Stavrakas Mirada; Joice Olinda do Couto; Gilvana de Oliveira Costa; Ana Carla Rangel Rosa; Carly Henrique Gambeta Borges; Eduardo José Crevelin; Luciana Silva de Araújo; Jairo K. Bastos; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio (Natural Product Research, 2025)

Impact of a Novel Aquatic-Based Strength Program on Body Composition, Strength, and Quality of Life in Older Women: a 16-Week Randomized Controlled Trial - Alvaro Juesas; Carlos Babiloni-Lopez; Javier Gene-Morales; Pablo Jiménez-Martínez; Rodrigo Ramirez-Campillo; Juan C. Colado (Journal of Science in Sport and Exercise, 2025)
Purpose This study aimed to compare the effects of water- versus land-based resistance training on body composition (fat and muscle mass), strength (isometric and isokinetic), and health-related quality of life in older women. Methods Ninety-three apparently healthy volunteers (age: 68.91 ± 5.05 years) participated in this prospective randomized controlled trial and were divided into three groups with a block-design randomization sequence: (i) water-based training (WG) using drag devices at a fast-paced execution, (ii) land-based training (LG) using tornado devices at a moderate-paced execution, and (iii) control group (CG) with no training. The training program lasted 16 weeks, with two weekly sessions, each including three upper-limb and three lower-limb exercises. Both groups progressively increased intensity (rating of perceived exertion) and volume (sets) throughout the program. Each set lasted 40 s, with LG performing 10 repetitions (2 s concentric, 2 s eccentric) and WG performing as many repetitions as possible. Results Significant group × time effects were found for body fat ( P = 0.016, η p 2 = 0.13), upper-limb muscle mass ( P = 0.027, η p 2 = 0.12), all isometric strength tests ( P < 0.001, η p 2 = 0.45–0.57), and isokinetic knee extension at 60º/s and 180º/s ( P = 0.001–0.013, η p 2 = 0.15–0.26). No significant differences were found between LG and WG in most variables ( P > 0.05). The WG significantly improved isometric vertical row ( d = 1.47), isokinetic knee extension ( d = 0.41–1.11), physical function ( d = 0.44), and body pain ( d = 0.50), while the LG did not. Conversely, only the LG significantly reduced body fat ( d = 0.24). Conclusion Although both training programs show similar results, power training in water significantly improves strength parameters and health-related quality of life, while moderate-paced resistance training on land effectively reduces body fat.

Effect of the follicular stage and circulating progesterone concentrations at the beginning of an estradiol/progesterone-based synchronization protocol on profile of gonadotropins and follicle dynamics in beef heifers - Lucas O. e Silva; Patrícia R. Cavalcanti; Rodrigo L.O.R. Alves; Natália P. Folchini; Natália N. Teixeira; Pedro J.L. Monteiro; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

From ocean to meadow: A circular bioeconomy by transforming seaweed, seagrass, grass, and straw waste into high-value products - Rodrigo Salvador; M. Lynn Eriksen; Niels C. Kjaersgaard; Michael Hedegaard; Torben Knudby; Victor Lund; Samuel B. Larsen (Waste Management, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Handheld-pen plasma treatment of graphite sheet electrodes for highly sensitive detection of emerging pollutants in waters - Mariana C. Marra; Gilvana P. Siqueira; Raquel G. Rocha; Thiago C. Oliveira; Eduardo M. Richter; Julio C. Sagás; Rogério V. Gelamo; Rodrigo A.A. Muñoz (Journal of Environmental Chemical Engineering, 2025)

Integrating gas diffusion electrode technology in a 3D-printed cell for an efficient electrochemical production of hydrogen peroxide - A. Rodríguez-Gómez; C. Sáez; M.A. Rodrigo; J. Lobato (Journal of Environmental Chemical Engineering, 2025)

Life cycle assessment and life cycle costing of the electrochemical production of peroxosulfates - A. Rodríguez-Gómez; M.P. Castro; C. Sáez; M.A. Rodrigo; C.M. Fernández-Marchante (Chemical Engineering Journal, 2025)

Alterations in Gut Microbiome Composition and Increased Inflammatory Markers in Post-COVID-19 Individuals - Tatiana Barichello; Bruno Kluwe-Schiavon; Laura A. Borba; Lucas C. Pedro; Flávia S. Niero; Laísa N. dos Santos; Letícia M. Leonardo; Zuleide M. Ignácio; Rodrigo Morales; Luciane B. Ceretta; Gislaine Z. Reus (Molecular Neurobiology, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Forest citizens and people‐centered conservation in the Brazilian Amazon - Luke Parry; Thiago F. Morello; James A. Fraser; Natalia Guerrero; Gabriela S. Lotta; Rodrigo C. Martins; Peter Newton; Jessica C. Pires Cardoso; Andreza A. Souza Santos; Mauricio Torres (Conservation Biology, 2025)
Demands for territorial recognition are foundational to the claiming of rights by forest‐proximate people who attempt to conserve their forests. The rights of these often‐marginalized populations have been largely overlooked by conservationists, yet they are central to achieving people‐centered conservation. We further developed the concept of forest citizenship as a normative framework and analytical tool based on Brazilian social environmentalism ( socioambientalismo ), florestania (a former political project in Acre state), Latin American scholarship on ecological citizenship, and Eurocentric political philosophy. Decades of struggle for territorial recognition and social inclusion have solidified the right to have rights for Amazonia's forest citizens. Hence, forest citizens are people who have become so through the sociopolitical dynamics of their rights claims. Forest citizenship is built on community mobilization to create legally recognized territories with participatory governance but becomes tangible only if individuals and communities can successfully claim other rights from institutions through everyday practices of citizenship. We also assessed the current number and distribution of forest citizens across Brazilian Amazonia based on gridded population data and spatial analyses to calculate the resident population in four territorial categories that meet these democratic preconditions: Indigenous lands, extractive reserves, sustainable development reserves, ecological settlement projects, and Afro‐descendent Quilombola territories. The territories covered 31% of the Legal Amazon, were home to 1.05 million forest citizens, and had diverse primary policy objectives but shared goals of empowering communities and conserving forests. To be emancipatory, forest citizenship must be bottom‐up, socially inclusive, and improve people's lives. We suggest that conservationists pay greater attention to power relations and decision‐making structures related to forest territories. Territory‐based forest citizenship may be relevant for other countries where environmentalism has intersected with struggles for land rights and democracy.

A novel open-source framework for automatic flocculation kinetics and retention time modelling using image analysis and swarm intelligence - Abayomi O. Bankole; Rodrigo Moruzzi; Rogério G. Negri; Luiza C. Campos (Journal of Water Process Engineering, 2025)

Linking the grain weight damage by Fusarium graminearum and the gluten composition of bread wheat under different sulfur fertilization - Agustín F. Arata; Mauro Martínez; Deborah P. Rondanini; Laura Lázaro; Adriana C. Arrigoni; Rodrigo I. Galizio; Florencia Arroyo; María Inés Dinolfo (Journal of Cereal Science, 2025)

Unique gastropods dominate the fauna on inactive vent sulfide features in the eastern Pacific - Lauren S. Mullineaux; Stace E. Beaulieu; Susan W. Mills; Rose Jones; Johanna N. J. Weston; Ayinde C. Best; Rodrigo Zúñiga Mouret; Michael J. Meneses; Margaret K. Tivey; Mikayla J. Harris; Amanda M. Achberger; Jason B. Sylvan (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Primary intracranial squamous cell carcinoma in a mule - João R.C. Brito Junior; Yanca G.S. Soares; Laynaslan A. Soares; Ismael L. Borges; Rodrigo C. Alves; Daniel M. Assis; Glaucia D. Kommers; Antonio F.M. Dantas; Glauco J.N. Galiza (Journal of Comparative Pathology, 2025)

The mitochondriotropic antioxidants AntiOxBEN2 and AntiOxCIN4 are structurally-similar but differentially alter energy homeostasis in human skin fibroblasts - José Teixeira; Sofia Benfeito; Rodrigo Carreira; André Barbosa; Ricardo Amorim; Ludgero C. Tavares; John G. Jones; Nuno Raimundo; Fernando Cagide; Catarina Oliveira; Fernanda Borges; Werner J.H. Koopman; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

The Combined and Isolated Impacts of El Niño and Positive Indian Ocean Dipole Events on South American Precipitation During Austral Winter and Spring Depending on the Atlantic Multidecadal Oscillation Phases - Itamara P. Souza; Rita V. Andreoli; Mary T. Kayano; Jean A. C. Costa; Leonardo Mamani; Rodrigo A. F. Souza; Wilmar L. Cerón (International Journal of Climatology, 2025)
The isolated/combined impacts of the positive Indian Ocean Dipole (pIOD) and El Niño (EN) events on precipitation in South America (SA) were investigated during austral winter and spring for the 1901–2012 period, considering both Atlantic Multidecadal Oscillation (AMO) phases. Under the warm phase (WAMO), EN events are well characterised in winter and, in spring, are accompanied by anomalous warming of the Tropical North Atlantic (TNA); thus, variations in the Walker circulation and the northward shifted Intertropical Convergence Zone (ITCZ) reduce precipitation over northern SA. In the cold AMO phase (CAMO), EN events are weak in winter. At the same time, an intense cooling in the equatorial North Atlantic, favoured by the CAMO, enhances moisture transport from the Amazon to central and southeastern Brazil, increasing precipitation in the South Atlantic Convergence Zone region. As EN develops in spring, the anticyclone off the east coast of SA associated with the Pacific‐South American (PSA) pattern decreases (increases) precipitation in central (southeastern) SA. The pIOD events predominantly occur during WAMO phase, when warming in the TNA is favoured by AMO. In winter, the moisture transport to northern SA is weakened, and the ITCZ remains northward shifted, inhibiting the precipitation over northeastern Brazil and southeastern Amazon. In spring, pIOD intensified ascending motions in equatorial Atlantic, increasing precipitation over northeastern Brazil. A wave train from the Indian Ocean strengthens the South Atlantic subtropical high, suppressing precipitation in central and eastern SA. EN‐pIOD events are well established in both AMO phases, though the sea surface temperature anomalies in the TNA depend on the AMO. During WAMO, reduced precipitation in western Amazon and northeastern SA is influenced by the Walker circulation, while in CAMO, TNA cooling enhances moisture transport from the Amazon into southeastern SA, where the PSA pattern and wave train from the Indian Ocean increase precipitation.

Long‐haul flights and migratory routes of a nectar‐feeding bat - Theresa M. Laverty; Debbie C. Buecher; David C. Dalton; Mallory L. Davies; Fernando Gual‐Suárez; Paul A. Heady; Rodrigo A. Medellín; Mayra C. Ordóñez‐García; Samara Pérez‐Harp; A. Nayelli Rivera‐Villanueva; Brandi D. Stevenson; Kathryn E. Stoner; et al. (Ecology, 2025)

Feasibility of using silica (Na2SiO3 and SiO2NPs) to mitigate mercury in transgenic soybeans grown in contaminated soils and respective effects on nutrient homeostasis - Vinnícius H. C. da Silva; Rodrigo F. de Lima; Juliana L. S. Mayer; Marco Aurélio Zezzi Arruda (Environmental Science and Pollution Research, 2025)

Facing oceanographic, fisheries, and governance hotspots: Scientific evidence and policy implications from the southwest South Atlantic Ocean - Omar Defeo; Bárbara C. Franco; Alberto R. Piola; Claudio C. Buratti; Luis Gustavo Cardoso; Federico Cortés; Ignacio Gianelli; Micaela Giorgini; Gabriela Jorge-Romero; Diego Lercari; Erika Meerhoff; Leonardo Ortega; et al. (Marine Policy, 2025)

Exploring noncompliance in the intertidal kelp fishery Lessonia berteroana of northern Chile - M. Isidora Ávila-Thieme; Catalina A. Galaz-Catalán; Rodrigo A. Estévez; Pablo Romero; Josh C. Donlan; Stefan Gelcich (Marine Policy, 2025)

ReBreed21-ET: Evaluation of a rapid resynchronization program that allows timed embryo transfer every 21 days - João Paulo N. Andrade; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Rafael R. Domingues; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

Rhizochemistry and soil bacterial community are tailored to natural stress gradients - Thomas Dussarrat; Claudio Latorre; Millena C. Barros Santos; Constanza Aguado-Norese; Sylvain Prigent; Francisca P. Díaz; Dominique Rolin; Mauricio González; Caroline Müller; Rodrigo A. Gutiérrez; Pierre Pétriacq (Soil Biology and Biochemistry, 2025)

AMOC-forced southward migration of the ITCZ under a warm climate background - Laura Kraft; Marília C. Campos; Rodrigo A. Nascimento; Bruna B. Dias; Stefano Crivellari; Marcus V.L. Kochhann; Dailson J. Bertassoli; Igor M. Venancio; Thiago P. Santos; Paul A. Baker; Cleverson G. Silva; Cristiano M. Chiessi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Comparative study of standard and modified groundwater vulnerability methods in the gold and iron mining regions of Western Quadrilátero Ferrífero, Brazil - Alice Zupo; Rodrigo S. de Paula; Jarbas L.D. Sampaio; Jorge G.R. Júnior; Marília C. Melo (Journal of Contaminant Hydrology, 2025)

Development and validation of a rapid method for the determination of oil and oleic acid content in peanut (Arachis hypogaea L.) using time domain nuclear magnetic resonance - Lucas J. Carvalho; Jacqueline Elis de Souza; Evelyn de F. Guimarães; Luiz Alberto Colnago; Daniel Martelozo Consalter; Silvia Paulo de Azevedo; Cristina Torres Consalter; Karla Borba; Rodrigo Garcia; Davi dos Santos Miquelin; Bruno Felipe Caravieri; Jair Heuert; et al. (Food Research International, 2025)

Cannabidiol-Induced Autophagy Ameliorates Tau Protein Clearance - Talita A. M. Vrechi; Gabriel C. Guarache; Rafaela Brito Oliveira; Erika da Cruz Guedes; Adolfo G. Erustes; Anderson H. F. F. Leão; Vanessa C. Abílio; Antonio W. Zuardi; Jaime Eduardo C. Hallak; José Alexandre Crippa; Claudia Bincoletto; Rodrigo P. Ureshino; et al. (Neurotoxicity Research, 2025)
Tau is a neuronal protein that confers stability to microtubules; however, its hyperphosphorylation and accumulation can lead to an impairment of protein degradation pathways, such as autophagy. Autophagy is a lysosomal catabolic process responsible for degrading cytosolic components, being essential for cellular homeostasis and survival. In this context, autophagy modulation has been postulated as a possible therapeutic target for the treatment of neurodegenerative diseases. Studies point to the modulatory and neuroprotective role of the cannabinoid system in neurodegenerative models and here it was investigated the effects of cannabidiol (CBD) on autophagy in a human neuroblastoma strain (SH-SY5Y) that overexpresses the EGFP-Tau WT (Wild Type) protein in an inducible Tet-On system way. The results demonstrated that CBD (100 nM and 10 µM) decreased the expression of AT8 and total tau proteins, activating autophagy, evidenced by increased expression of light chain 3-II (LC3-II) protein and formation of autophagosomes. Furthermore, the cannabinoid compounds CBD, ACEA (CB1 agonist) and GW-405,833 (CB2 agonist) decreased the fluorescence intensity of EGFP-Tau WT; and when chloroquine, an autophagic blocker, was used, there was a reversal in the fluorescence intensity of EGFP-Tau WT with CBD (1 and 10 µM) and GW-405,833 (2 µM), demonstrating the possible participation of autophagy in these groups. Thus, it was possible to conclude that CBD induced autophagy in EGFP-Tau WT cells which increased tau degradation, showing its possible neuroprotective role. Hence, this study may contribute to a better understanding of how cannabinoids can modulate autophagy and present a potential therapeutic target in a neurodegeneration model. Graphical Abstract

Nowhere to hide: massive corals’ mortality after cumulative heat stress in a putative climate change refugium - Fernando C. Cardoso; Ivan M. Carneiro; Guilherme M. Castro; Gabriel O. Cardoso; Aline Shimada; Myllena S. Pereira; Livia B. Villela; Paulo S. Salomon; Rodrigo L. Moura (Coral Reefs, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

Research advances and conservation needs for the protection of the Salas y Gómez and Nazca ridges: A natural and cultural heritage hotspot in the southeastern Pacific ocean - C.F. Gaymer; D. Wagner; R. Álvarez-Varas; B. Boteler; L. Bravo; C.M. Brooks; V. Chavez-Molina; D. Currie; J. Delgado; B. Dewitte; E.E. Easton; A.M. Friedlander; et al. (Marine Policy, 2025)

Millennial- to centennial-scale Atlantic ITCZ swings during the penultimate deglaciation - Marília C. Campos; Cristiano M. Chiessi; Rodrigo A. Nascimento; Laura Kraft; Svetlana Radionovskaya; Luke Skinner; Bruna B. Dias; Tainã M.L. Pinho; Marcus V.L. Kochhann; Stefano Crivellari; Thays D. Mineli; Vinícius R. Mendes; et al. (Quaternary Science Reviews, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

Collagen and collagenases in mare’s endometrium with endometrosis - Luiz Augusto M. Centeno; Henrique B.A. Bastos; Verônica L.C. Bueno; Janislene M. Trentin; MarianiF. Fiorenza; Welden Panziera; Gustavo H.Z. Winter; Nelson A. Kretzmann; Sandra Fiala-Rechsteiner; Rodrigo C. Mattos; Mara I.B. Rubin (Theriogenology, 2024)

Electrochemically assisted remediation of a highly chlorinated organic polluted sludge: A full-scale case study - J. Fernandez-Cascan; J. Isidro; B.A. Tiban-Anrango; J. Guadaño; C. Saez; M.A. Rodrigo (Journal of Hazardous Materials, 2024)

Microbiota diversity of three Brazilian native fishes during ice and frozen storage - Rafaela C. Baptista; Ilario Ferrocino; Matheus Pavani; Tatiane M. Guerreiro; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Rodrigo R. Catharino; Elenilson G. Alves Filho; Sueli Rodrigues; Edy S. de Brito; Magdevis Y.R. Caturla; et al. (Food Microbiology, 2024)

Evaluation of a Kirigami-inspired double-skin adaptive façade for natural ventilation and solar harvesting to enhance indoor environment and energy performance - Rodrigo Arauz; Evgeni Filipov; Alessandro Fascetti; Dale T. Clifford; John C. Brigham (Energy and Buildings, 2024)

Evaluation of the Extract of Pseudopithomyces chartarum to be used as Biocontrol Agent Against Phytophthora cinnamomi in Lupinus luteus - C. García-Latorre; S. Rodrigo; O. Santamaria (Journal of Soil Science and Plant Nutrition, 2024)
Endophytic fungi offer promising opportunities for a sustainable disease management in agricultural systems, often related to their secondary metabolites. In this study, the potential of the metabolites produced in vitro by Pseudopithomyces chartarum to protect the forage crop Lupinus luteus against the soil-borne pathogen Phytophthora cinnamomi was evaluated in different in vitro and in planta tests. The fungal extracts containing the metabolites were applied by two different procedures: to seeds by immersion (mycopriming) and to seedlings by spraying (post-emergence). The antagonism between the endophyte fitrates/extracts and the pathogen was studied by dual culture assays and the minimal inhibitory concentration. Other filtrate/extract traits, such as its phytohormones production and nutrient mobilization, were also analyzed. The metabolites contained in the extract were tentatively identified by mass spectrometry. The endophyte’s filtrates and extracts exhibited significant inhibition on the P. cinnamomi growth in vitro. Additionally, seed mycopriming and post-emergence extract application positively influenced seed germination, reduced disease severity, and enhanced several growth parameters in treated seedlings. Auxins and gibberellins production, and phosphate solubilization activity were observed in the endophyte, traits potentially contributing to its biocontrol efficacy. The bioactive compounds ciclo(L-Phe-L-Pro), dihydroabikoviromycin, medelamine A, herniarin, and Piptamine, all with antimicrobial properties, were tentatively identified in the extracts, but further research is needed to confirm this identity and to evaluate the extract efficacy under field conditions. This study highlights the potential of certain endophytic fungi as sustainable and environmentally friendly alternatives for a disease management in agriculture.

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

Effect of connection elements on shear strength of wooden pieces for structural use - Hellen M. A. C. Rodrigues; Evelize A. Amaral; Rodrigo A Pereira; José Benedito Guimarães Junior; Paulo R. G. Hein (Journal of the Indian Academy of Wood Science, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Integration of a 3D-printed electrochemical reactor with a tubular membrane photoreactor to promote sulfate-based advanced oxidation processes - Agustina R. de Olivera; Carla S. Santos; Ismael F. Mena; Miguel A. Montiel; Rosa Montes; José B. Quintana; Rosario Rodil; Ana I. Gomes; Francisca C. Moreira; Jan Gäbler; Lothar Schäfer; C. Sáez; et al. (Chemical Engineering Journal, 2024)

A systematic review of the land use change effects on ant diversity in Neotropics - Icaro Wilker; Antônio C.M. Queiroz; Carla R. Ribas; Maria Santina C. Morini; Chaim J. Lasmar; Fernando A. Schmidt; Rodrigo M. Feitosa; Anselmo Nogueira; Fabrício B. Baccaro; Mônica A. Ulysséa; Thiago Izzo; Lucas N. Paolucci; et al. (Biological Conservation, 2024)

Climatic variables influence the photosynthetic capacity of forest plantations in Brazil - Juscelina Arcanjo dos Santos; Otávio Camargo Campoe; Michael J. Aspinwall; Cléber Rodrigo de Souza; José Luiz Stape; Clayton A. Alvares; Joannès Guillemot; Guerric le Maire; Jean-Paul Laclau; Yann Nouvellon; Mathias Christina; Patricia Battie-Laclau; et al. (New Forests, 2024)

Disseminated paracoccidioidomycosis in a captive western black-handed tamarin (Saguinus niger) - Isabelle D. de Oliveira; Eduardo Ferreira-Machado; Jamile M. Garcia; Sarah R.J.S. Simões; Ketlyn B. Figueiredo; Rodrigo A. Ressio; André L.M. da Costa; Flora N. Matos; Cássia R.R. Gonzaga; Shamira S. Leandro; Marina A. de Medeiros; Rodrigo H.F. Teixeira; et al. (Journal of Comparative Pathology, 2024)

Socially Acceptable Feed Formulations May Impact the Voluntary Feed Intake and Growth, but Not Robustness of Nile Tilapia (Oreochromis niloticus) - Rodrigo Mendes; Paulo Rema; Jorge Dias; Ana Teresa Gonçalves; Rita Teodósio; Sofia Engrola; Francisco J. Sánchez-Vázquez; Luís E. C. Conceição (Fishes, 2024)
Society is becoming more demanding with aquaculture’s environmental footprint and animal wellbeing. In order to potentially mitigate these concerns, feed formulations could be based on eco-efficient (circular economy-driven) or organic ingredients. This study aimed to investigate the growth performance, feed utilization, and health status of juvenile Nile tilapia (Oreochromis niloticus) when fed with such feeds. The growth trial lasted for 8 weeks, and fish had an initial weight of 31.0 ± 0.5 g (mean ± SD). Fish were fed until visual satiation, in quadruplicate, with one of three isonitrogenous and isoenergetic experimental feeds: a commercial-like feed without fishmeal (PD), a diet based on ingredients compatible with organic certification (ORG), or a feed formulated using circular economy-driven subproducts and emergent ingredients (ECO). Fish fed ECO showed a tendency for decreased feed intake, while ORG fish significantly reduced their intake compared to those fed PD. Consequently, fish fed ECO (62.7 ± 5.4 g) exhibited almost half the growth than those fed PD (107.8 ± 6.1 g), while ORG fish almost did not increase their weight (32.7 ± 1.3 g). ECO and ORG diets had a lower digestibility for protein, lipid, and energy when compared to PD. Feed utilization of fish fed ECO or ORG was also lower than those fed PD. From the health-related genes analyzed, only glutathione reductase (gsr) showed statistically significant differences, being more expressed in fish-fed ECO than those fed PD. Thus, even when such novel formulations induced extreme effects on voluntary feed intake, their impact was noted only in fish growth, but not in robustness.

Cattleya attenboroughiana (Orchidaceae: Laeliinae): a new species from the Diamantina Plateau, Minas Gerais, Brazil - Euler L. F. Menezes; Samuel C. O. Giordani; Rodrigo A. Pinheiro; Paulo M. Gonella (Kew Bulletin, 2024)

Preliminary profile of the gut microbiota from amerindians in the Brazilian amazon experiencing a process of transition to urbanization - Rodrigo M. Alencar; José G. Martínez; Valéria N. Machado; Juan F. Alzate; Cinthya P. Ortiz-Ojeda; Rosiane R. Matias; Denise C. Benzaquem; Maria C.F. Santos; Enedina N. Assunção; Evelyn C. Lira; Spartaco Astolfi-Filho; Tomas Hrbek; et al. (Brazilian Journal of Microbiology, 2024)
The Yanomami are one of the oldest indigenous tribes in the Amazon and are direct descendants of the first people to colonize South America 12,000 years ago. They are located on the border between Venezuela and Brazil, with the Venezuelan side remaining uncontacted. While they maintain a hunter-gatherer society, they are currently experiencing contact with urbanized populations in Brazil. The human gut microbiota of traditional communities has become the subject of recent studies due to the Westernization of their diet and the introduction of antibiotics and other chemicals, which have affected microbial diversity in indigenous populations, thereby threatening their existence. In this study, we preliminarily characterized the diversity of the gut microbiota of the Yanomami, a hunter-gatherer society from the Amazon, experiencing contact with urbanized populations. Similarly, we compared their diversity with the population in Manaus, Amazonas. A metabarcoding approach of the 16 S rRNA gene was carried out on fecal samples. Differences were found between the two populations, particularly regarding the abundance of genera (e.g., Prevotella and Bacteroides ) and the higher values of the phyla Bacteroidetes over Firmicutes, which were significant only in the Yanomami. Some bacteria were found exclusively in the Yanomami ( Treponema and Succinivibrio ). However, diversity was statistically equal between them. In conclusion, the composition of the Yanomami gut microbiota still maintains the profile characteristic of a community with a traditional lifestyle. However, our results suggest an underlying Westernization process of the Yanomami microbiota when compared with that of Manaus, which must be carefully monitored by authorities, as the loss of diversity can be a sign of growing danger to the health of the Yanomami.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Toward new biomarkers of cold tolerance: microRNAs regulating cold adaptation in fish are differentially expressed in cold-tolerant and cold-sensitive Nile tilapia (Oreochromis niloticus) - Eduardo B. Blödorn; Amanda W.S. Martins; Eduardo N. Dellagostin; Leandro S. Nunes; Rita C.S. da Conceição; Antônio D. Pagano; Natiéli M. Gonçalves; Luana F.V. dos Reis; Mariana C. Nascimento; Dionet K.B. Quispe; Charles N. Fróes; Rafael A. Tavares; et al. (Aquaculture, 2024)

Catalytic ozonation using spent battery-based (SB) catalysts for dyes, micropollutant removal and disinfection - Jacqueline A. Malvestiti; Maina Ruth C. Silva; Iure B. de Sousa; Rodrigo P. Cavalcante; Amanda Gondim C. Quirino; Guenther C.C. Viana; Elisângela Maria R. Rocha; Renato F. Dantas (Journal of Water Process Engineering, 2024)

Nile tilapia and gilthead seabream dietary self-selection of alternative feeds - Rodrigo Mendes; Luís E. C. Conceição; Jorge Dias; Sofia Engrola; Francisco J. Sánchez-Vázquez (Fish Physiology and Biochemistry, 2024)
Classical assessments of new fish feeds are anthropocentric, focusing mainly on growth. Although this methodology is accurate, it does not consider the fish’ perspective. This study aimed to investigate the behavioural responses and feed preferences of Nile tilapia ( Oreochromis niloticus ) and gilthead seabream ( Sparus aurata ) through a self-selection trial using self-feeders. Both species were offered three feeds: a control (PD) commercial-like feed and two diets (ORG1 and ORG2) formulated with different inclusions of alternative ingredients to address some of the current environmental concerns and/or ethical issues often associated with commercial formulations. Three groups of tilapia with an average weight of 163.0 g ± 4.3 g (mean ± SD) and four groups of seabreams with 174.7 g ± 27.0 g were tested. Tilapia exhibited a preference for ORG2 (46.5%), influenced by the sensory properties of the feed and post-ingestion signals. Seabream did not show a preference for any feed. These findings highlight the effectiveness of self-selection experiments in allowing fish to express their feeding behaviour and preferences. Therefore, this approach should be considered in the initial screening and design of new aquaculture feeds and ingredients.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

New parameters for in vitro development of cell lines of the species Astyanax bimaculatus (Linnaeus, 1758) and Geophagus proximus (Castelnau, 1855) - Ivanete de Oliveira Furo; Lygia S. Nogueira; Rodrigo Petry Corrêa de Sousa; Glaucia Caroline Silva‐Oliveira; Diovanna Mirella dos Santos da Silva; Allan Costa‐Malaquias; Edivaldo H. C. de Oliveira (Journal of Fish Biology, 2024)
Intending to compare in vitro cell growth in different conditions, we established cell cultures using fin biopsies of two freshwater fishes, Astyanax bimaculatus and Geophagus proximus . Three different culture media (Leibovitz–L‐15, Dulbecco's Modified Eagle Medium [DMEM], and 199) were employed, with or without the addition of AmnioMax, maintaining a standard temperature of 29°C. Based on the results obtained, we standardized a cell growth protocol in which medium 199 was less efficient for both species. Notably, G. proximus cells exhibited superior proliferation in DMEM and L‐15 media, whereas A. bimaculatus cells demonstrated better parameters exclusively in the DMEM medium. Successful subculturing of cells with good proliferation index was observed, accompanied by preserved morphological characteristics. Therefore, the methodology outlined in this study represents an advancement in establishing fish cell cultures.

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

How temperature modulates the expression of pathogenesis-related molecules of the cross-kingdom pathogen Lasiodiplodia hormozganensis - Carina Félix; Rodrigo Meneses; Micael F.M. Gonçalves; Ana S. Duarte; Jesus V. Jorrín-Novo; Yves van de Peer; Dieter Deforce; Filip Van Nieuwerburgh; Artur Alves; Ana C. Esteves (Science of The Total Environment, 2024)

The role of compaction in the diagenetic evolution of Pre-Salt Aptian deposits of Santos Basin, Brazil - Rodrigo B. Rossoni; Carla C. Porcher; Edinei Koester; Júlia S. Sobiesiak; Luis A.C. da Silva; André S. Mexias; Márcia E.B. Gomes; Camila W. Ramnani; Luiz F. De Ros (Sedimentary Geology, 2024)

Determinants of biogeographical distribution of grasses in grasslands of South America - Helena Streit; Rodrigo S. Bergamin; Bianca O. Andrade; Alice Altesor; Felipe Lezama; Susana Perelman; Sandra C. Müller; Gerhard E. Overbeck (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Enhancing flocculation kinetics assessment: Integrating aggregate size distribution into experimental and modelling frameworks - Rodrigo B. Moruzzi; Andre Luiz de Oliveira; Soroosh Sharifi; Abayomi O. Bankole; Luiza C. Campos (Journal of Water Process Engineering, 2024)

Heavy rains and hydrogeological disasters on February 18th–19th, 2023, in the city of São Sebastião, São Paulo, Brazil: from meteorological causes to early warnings - Jose A. Marengo; Ana P. Cunha; Marcelo E. Seluchi; Pedro I. Camarinha; Giovanni Dolif; Vinicius B. Sperling; Enner H. Alcântara; Andrea M. Ramos; Marcio M. Andrade; Rodrigo A. Stabile; José Mantovani; Edward Park; et al. (Natural Hazards, 2024)

Stomatal conductance models in Brazilian forest plantations: genotype and environmental effects on eucalypt and pine forests - Juscelina Arcanjo dos Santos; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Ana Helíosa C. Marrichi; Rafaela Lorenzato Carneiro; Paulo Henrique Muller da Silva; Eduardo Moré de Mattos; Marina Shinkai Gentil Otto; Beatriz Teixeira Gonsalez (New Forests, 2024)

Re-evaluating the link between the Ellsworth Mountains and East Antarctica in the Neoproterozoic: Implications for the breakup of Rodinia and the existence of Pannotia - Paula Castillo; Fernando Poblete; Rodrigo Fernández; Joaquín Bastías-Silva; C. Mark Fanning (Precambrian Research, 2024)

A whole-body transcriptome assembly of the annelid worm Hediste diversicolor - André M. Machado; Rodrigo Samico; Marcos Domingues; Andreas Hagemann; Luísa M.P. Valente; Arne M. Malzahn; André Gomes-dos-Santos; Raquel Ruivo; Juan Carlos Navarro; Óscar Monroig; L. Filipe C. Castro (Marine Genomics, 2024)

The convergence approach may be critical to improving early situational awareness in hostile radioactive environments - Vitor W.L. Silva; William H.S. Profeta; Rodrigo C. Curzio; Avelino Santos; Tercio Brum; Edson R. Andrade (Journal of Environmental Radioactivity, 2024)

Chilled Pacu (Piaractus mesopotamicus) fillets: Modeling Pseudomonas spp. and psychrotrophic bacteria growth and monitoring spoilage indicators by 1H NMR and GC–MS during storage - Rafaela C. Baptista; Rodrigo B.A. Oliveira; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Matheus Pavani; Tatiane M. Guerreiro; Rodrigo R. Catharino; Elenilson G.A. Filho; Sueli Rodrigues; Edy S. de Brito; Verônica O. Alvarenga; et al. (International Journal of Food Microbiology, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Reversible strengthening behaviour of subsurface layers in sandy soils – understanding variable response to strategic deep tillage - Rodrigo C. da Silva; Therese M. McBeath; Diogenes L. Antille; Mark Thomas; Lynne M. Macdonald (Soil and Tillage Research, 2024)

Coralline algae and bryozoans as major carbonate sediment components of shallow and mesophotic reefs on the Abrolhos Bank, Brazil, SW Atlantic - Pedro Cardial; Fernando C. Moraes; Rodrigo T. Carvalho; Cláudia S. Karez; Laís V. Ramalho; Renata dos S. Gomes; Leonardo T. Salgado (Journal of South American Earth Sciences, 2024)

Metabolic engineering on a 3D-printed microfluidic platform: A new approach for modular co-metabolic pathways - Seyed Hossein Helalat; Islam Seder; Rodrigo C. Téllez; Mahmood Amani; Yi Sun (Chemical Engineering Journal, 2024)

Correction: Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2024)

Comment on “No wild bees? Don't worry! Non-bee flower visitors are still hard at work: The edge effect, landscape, and local characteristics determine taxonomic and functional diversity in apple orchards” [Agric. Ecosyst. Environ. 345 (2023) 108554] - José N. Mesquita-Neto; Victor Hugo Monzón; Rodrigo de O. Araujo; Bruna K. Pinheiro-Costa; Benito Cortés-Rivas; Laura C. Pérez-Giraldo; Catalina Escanilla-Jaramillo; Sharon Rodríguez (Agriculture, Ecosystems & Environment, 2024)

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Precision and accuracy of common coral reef sampling protocols revisited with photogrammetry - Ivan M. Carneiro; João A. Sá; Pamela M. Chiroque-Solano; Fernando C. Cardoso; Guilherme M. Castro; Paulo S. Salomon; Alex C. Bastos; Rodrigo L. Moura (Marine Environmental Research, 2024)

Allometric models for non-destructive estimation of the leaflet area in acai (Euterpe oleracea Mart.) - Samara K. A. de Sousa; Rodrigo G. M. Nascimento; Flavio Henrique S. Rodrigues; Rafael G. Viana; Lucas C. da Costa; Hugo A. Pinheiro (Trees, 2024)

Acid coating to increase availability of zinc in phosphate fertilizers - Fien Degryse; Hugh Harris; Roslyn Baird; Ivan Andelkovic; Rodrigo C. da Silva; Shervin Kabiri; Atilla Yazici; Ismail Cakmak; Mike J. McLaughlin (Plant and Soil, 2024)
Background Precipitation of Zn phosphates may limit Zn availability in cogranulated P fertilizers. We assessed whether the Zn availability of Zn could be improved by post-granulation acid treatment. Methods Uncoated Zn-fortified monoammonium phosphate granules were compared with sulfuric acid-coated granules in which Zn was either cogranulated or dissolved in the acid coating. Spatially resolved XRF and XANES was used to assess the distribution and speciation of Zn in the granules (before and after incubation in soil) and in the exposed soil. The amount of Zn remaining in the granule was determined after incubation in various soils. The effect of acid coating rate on corn yield was determined in a highly Zn-deficient soil in a pot trial. Results The speciation of Zn in the untreated granules was dominated by Zn phosphates. In the sulfuric acid treatments, sulfate species accounted for ~ 45% (if cogranulated) or ~ 80% (if coated) of the Zn. After one week incubation in soil, 10–86% of the added Zn remained in the residual granule, mostly as sparingly soluble compounds. The Zn speciation in the soil near the granule was dominated by Zn phosphates irrespective of treatment, but Zn moved further away from the application site in the acid treatments, as more Zn was released from the granule. In the pot trial, the dry matter yield increased by 70% at a coating rate of 0.75% H 2 SO 4 compared to the uncoated control. Conclusions Post-granulation acid treatment of Zn-fortified P fertilizers is an effective way to enhance the phytoavailability of fertilizer Zn.

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

A reliable validated high-performance liquid chromatography-photodiode array detection method for quantification of terpenes in Copaifera pubiflora , Copaifera trapezifolia , and Copaifera langsdorffii oleoresins - Luiza J. Carneiro; Jairo K. Bastos; Rodrigo C. S. Veneziani; Mario F. C. Santos; Sérgio R. Ambrósio (Natural Product Research, 2024)

Influence of GnRH analog and dose on LH release and ovulatory response in Bos indicus heifers and cows on day seven of the estrous cycle - Lucas O. e Silva; Jessica C.L. Motta; Abraham L. Oliva; Guilherme Madureira; Rodrigo L.O.R. Alves; Natália P. Folchini; Mateus A. da Silva; Taynara J.B. da Silva; Carlos E.C. Consentini; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2024)

Incomplete sanitation in the Metropolitan Region of São Paulo results in detection of SARS-CoV-2 in headwater streams - Ricardo H. Taniwaki; Rodrigo F. Bueno; Giulia B.S. Bispo; Matheus R. Augusto; Guilherme S. Souza; Bruna Chyoshi; Roseli F. Benassi; Nelson Gouveia; Lívia M.B. Camilo; Adriana F.A. Duran; Luís C. Schiesari (Science of The Total Environment, 2024)

Long-term heat acclimation training in mice: Similar metabolic and running performance adaptations despite a lower absolute intensity than training at temperate conditions - Gustavo de Oliveira Zanetti; Pedro William Martins Pessoa; Tales Sambrano Vieira; Rodrigo de Almeida Garcia; Nicolas Henrique Santos Barbosa; Rosa Maria Esteves Arantes; Isis do Carmo Kettelhut; Luiz Carlos C. Navegantes; Samuel Penna Wanner; Danusa Dias Soares; Dawit Albieiro Pinheiro Gonçalves (Journal of Thermal Biology, 2024)

Early development of the Patagonian fold and thrust belt and the onset of foreland sedimentation in the Austral-Magallanes basin - Maximiliano Naipauer; Matías C. Ghiglione; Martín H. Senger; Juan Albano; Inés Aramendía; Gonzalo Ronda; Rodrigo Suárez; Miguel E. Ramos; Victor A. Valencia (Journal of South American Earth Sciences, 2024)

Investigation of Cerebral Mitochondrial Injury in a Porcine Survivor Model of Carbon Monoxide Poisoning - Constantine D. Mavroudis; Alistair Lewis; John C. Greenwood; Matthew Kelly; Tiffany S. Ko; Rodrigo M. Forti; Samuel S. Shin; Frances S. Shofer; Johannes K. Ehinger; Wesley B. Baker; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

The importance of Indigenous and local people for cataloging biodiversity - Juan C. Copete; Alfred Kik; Vojtech Novotny; Rodrigo Cámara-Leret (Trends in Ecology & Evolution, 2023)

Overarching Business Models for a Circular Bioeconomy: Systematising archetypes - Rodrigo Salvador; Murillo Vetroni Barros; Marina Pieroni; Diogo A. Lopes Silva; Fausto Freire; Antonio C. De Francisco (Sustainable Production and Consumption, 2023)

Linking centennial scale anthropogenic changes and sedimentary records as lessons for urban coastal management - Leonardo Amora-Nogueira; Joseph M. Smoak; Rodrigo C. Abuchacra; Carla Carvalho; Fernando C.A. Ribeiro; Kevin C. Martins; Ana L. Fonseca-Oliveira; Manuela Carvalho; Luiza P. Machado; Allana F.F. Souza; André L.C. da Silva; Alex Enrich-Prast; et al. (Science of The Total Environment, 2023)

Continuous design and techno-economic assessment of a biorefinery process for heparan sulfate extraction from Nodipecten nodosus viscera waste - Caenam M.B. Bastos; Arthur V.L. Barbosa; Tainá C. Pereira; Pedro H.R. Alijó; Rodrigo F. Cano; Jeiveison G.S.S. Maia; João B.V. Bastos; Mauro S.G. Pavão (Chemical Engineering Journal, 2023)

Complex sulfated galactans from hot water extracts of red seaweed Asparagopsis taxiformis comprise carrageenan and agaran structures - Rodrigo A. Rodríguez Sánchez; Kadri Saluri; Rando Tuvikene; María C. Matulewicz; Marina Ciancia (Carbohydrate Polymers, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Tree hydrological niche acclimation through ontogeny in a seasonal Amazon forest - Mauro Brum; Luciana F. Alves; Raimundo C. de Oliveira-Junior; Victor Hugo Pereira Moutinho; Natalia Restrepo-Coupe; Karoline Chaves; Deliane Penha; Neill Prohaska; Plínio Barbosa de Camargo; Grazielle Sales Teodoro; Sebastião Ribeiro Xavier Júnior; Scott C. Stark; et al. (Plant Ecology, 2023)

Establishing morphological and molecular evidences to support the identification of “yerba buena” (Mentha × villosa Huds.) in the Philippines - Kristine Joyce O. Quiñones; Renerio P. Gentallan; Michael Cedric B. Bartolome; Roselle E. Madayag; Emmanuel Bonifacio S. Timog; Juan Rodrigo A. Vera Cruz; Nadine B. Coronado; Leah E. Endonela; Teresita H. Borromeo; Nestor C. Altoveros; Bartimeus Buiene S. Alvaran; Reneliza D. Cejalvo (Journal of Crop Science and Biotechnology, 2023)

Better Together: Volatile-Mediated Intraguild Effects on the Preference of Tuta absoluta and Trialeurodes vaporariorum for Tomato Plants - F. Rodrigo; A. P. Burgueño; A. González; C. Rossini (Journal of Chemical Ecology, 2023)

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Multiyear versus single‐year El Niño events: Contrasting their impacts on South American seasonal precipitation - Leonardo C. Mamani Jimenez; Rita V. Andreoli; Mary Toshie Kayano; Rodrigo Augusto Ferreira de Souza; Wilmar L. Ceron (International Journal of Climatology, 2023)
Differences in the seasonal distribution of precipitation over South America (SA) associated with single‐year (SY) and multiyear (MY) El Niño (EN) events were analysed based on reanalysis data for the 1901–2012 period. The results suggest that Pacific Sea Surface Temperature (SST) anomalies associated with MY EN events interact with the tropical Atlantic and Indian Oceans SST from austral fall to spring, after the event's first year, affecting SA precipitation distribution in subsequent seasons. Compared to SY EN events, which reproduce well the north–south dipolar precipitation anomaly pattern over SA, the MY EN events show differences in the intensity and positioning of precipitation anomalies. Precipitation decreases over northern SA during all seasons are observed for SY and MY EN events except for differences in magnitudes. Variations in the position and longitudinal extension of the downward motions of Walker circulation in response to these events explain these differences. Over southern and southeastern SA, differences in anomaly positioning are more evident. The positive precipitation anomalies over these regions in the austral spring and summer are weakened and southward shifted during the MY EN in relation to those during SY EN events. These variations are associated with the Rossby‐wave train pattern path that depends on the EN and season. Consequently, the associated local atmospheric circulation patterns also depend on the season. The intense (weak) South American low‐level jet (SALLJ) for the first year of MY EN contrasts with the weak or inexistence (intense) SALLJ for the SY EN during summer (springer). Complementary to previous studies, the results indicate that the differences in the intensity and duration of the SY and MY EN events contribute to changes in the EN‐related atmospheric teleconnection pattern that impacts SA precipitation. The results can be useful for climate prediction and monitoring purposes.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Messor erwini sp. n., a hitherto cryptic harvester ant in the Iberian Peninsula - Noel Orou; Sándor Csősz; Xavier Arnan; Rodrigo G. Pol; Wolfgang Arthofer; Birgit C. Schlick-Steiner; Florian M. Steiner (Zoologischer Anzeiger, 2023)

Tracking new insights into antifungal and anti-mycotoxigenic properties of a biofilm forming Pediococcus pentosaceus strain isolated from grain silage - Carlos M.N. Mendonça; Rodrigo C. Oliveira; Lucas J.L. Pizauro; Wellison A. Pereira; Kahlile Abboud; Sonia Almeida; Ii-Sei Watanabe; Alessandro M. Varani; José M. Domínguez; Benedito Correa; Koen Venema; Pamela O.S. Azevedo; et al. (International Journal of Food Microbiology, 2023)

Feeding rumen-protected Capsicum oleoresin to dairy cows during the transition period and early lactation: Effects on nutrient digestibility, blood metabolites, and performance - Caio S. Takiya; Nathália T.S. Grigoletto; Rodrigo G. Chesini; Osmar Pietro Sbaralho; Milena Bugoni; Paulo Cesar Vittorazzi; Alanne T. Nunes; Guilherme G. da Silva; Daniel José C. Vieira; Ana Carolina de Freitas; Gabriela Acetoze; Francisco P. Rennó (Animal Feed Science and Technology, 2023)

Asymmetric response of Amazon forest water and energy fluxes to wet and dry hydrological extremes reveals onset of a local drought‐induced tipping point - Natalia Restrepo‐Coupe; Bradley O’Donnell Christoffersen; Marcos Longo; Luciana F. Alves; Kleber Silva Campos; Alessandro C. da Araujo; Raimundo C. de Oliveira; Neill Prohaska; Rodrigo da Silva; Raphael Tapajos; Kenia T. Wiedemann; Steven C. Wofsy; et al. (Global Change Biology, 2023)
Understanding the effects of intensification of Amazon basin hydrological cycling—manifest as increasingly frequent floods and droughts—on water and energy cycles of tropical forests is essential to meeting the challenge of predicting ecosystem responses to climate change, including forest “tipping points”. Here, we investigated the impacts of hydrological extremes on forest function using 12+ years of observations (between 2001–2020) of water and energy fluxes from eddy covariance, along with associated ecological dynamics from biometry, at the Tapajós National Forest. Measurements encompass the strong 2015–2016 El Niño drought and La Niña 2008–2009 wet events. We found that the forest responded strongly to El Niño‐Southern Oscillation (ENSO): Drought reduced water availability for evapotranspiration ( ET ) leading to large increases in sensible heat fluxes ( H ). Partitioning ET by an approach that assumes transpiration ( T ) is proportional to photosynthesis, we found that water stress‐induced reductions in canopy conductance ( G s ) drove T declines partly compensated by higher evaporation ( E ). By contrast, the abnormally wet La Niña period gave higher T and lower E , with little change in seasonal ET . Both El Niño‐Southern Oscillation (ENSO) events resulted in changes in forest structure, manifested as lower wet‐season leaf area index. However, only during El Niño 2015–2016, we observed a breakdown in the strong meteorological control of transpiration fluxes (via energy availability and atmospheric demand) because of slowing vegetation functions (via shutdown of G s and significant leaf shedding). Drought‐reduced T and G s , higher H and E , amplified by feedbacks with higher temperatures and vapor pressure deficits, signaled that forest function had crossed a threshold, from which it recovered slowly, with delay, post‐drought. Identifying such tipping point onsets (beyond which future irreversible processes may occur) at local scale is crucial for predicting basin‐scale threshold‐crossing changes in forest energy and water cycling, leading to slow‐down in forest function, potentially resulting in Amazon forests shifting into alternate degraded states.

Restricted connectivity for cobia Rachycentron canadum (Perciformes: Rachycentridae) in the Western Atlantic Ocean - Maria Raquel M. Coimbra; Emilly Benevides; Renata da Silva Farias; Bruno C. N. R. da Silva; Sara Cloux; Vicente Pérez‐Muñuzuri; Manuel Vera; Rodrigo Torres (Fisheries Oceanography, 2023)
Cobia ( Rachycentron canadum ) is a coastal pelagic migratory fish species of tropical and subtropical waters, where it is an important game fish and it has been commercially expanded in offshore aquaculture systems. Understanding population connectivity is of utmost importance to the sustainable use and conservation of aquatic resources, and information on genetic diversity and structure is key element in unraveling differentiation when no clear physical barriers exist. In the present study, cobia genetic diversity and structure were depicted using mitochondrial DNA cytochrome b sequencing and microsatellite genotyping in samples from the Southwestern Atlantic and showed that a major single population inhabits the southern hemisphere. Cytochrome b sequencing also suggested that the Indian Ocean is the center of origin for this species' diversification. A hierarchical analysis of AMOVA compared sampling locations from the Northwestern Atlantic (from a previous study) with the Southwestern ones using nine shared microsatellite markers. Differentiation among groups (F CT = 0.41), Bayesian clustering analysis, and complementary ordination analyses (by discriminant analysis of principal components [DAPC] and factorial correspondence analysis [3D‐FCA]) presented a clear separation between the two hemispheres, supported by a Lagrangian model that explained the ocean dynamics over larval retention on the Western Atlantic. Another genetic subgroup intermingled with the main Southwestern group may also exist further south, probably associated with the Vitória‐Trindade Ridge and the local current systems. The distribution of this species in metapopulations is of extreme relevance for fisheries and fish hatcheries management in the Atlantic Ocean.

25 Years of thermomorphogenesis research: milestones and perspectives - Marcel Quint; Carolin Delker; Sureshkumar Balasubramanian; Martin Balcerowicz; Jorge J. Casal; Christian Danve M. Castroverde; Meng Chen; Xuemei Chen; Ive De Smet; Christian Fankhauser; Keara A. Franklin; Karen J. Halliday; et al. (Trends in Plant Science, 2023)

Amazonian earthworm biodiversity is heavily impacted by ancient and recent human disturbance - Ana C. Conrado; Wilian C. Demetrio; David W.G. Stanton; Marie L.C. Bartz; Samuel W. James; Alessandra Santos; Elodie da Silva; Talita Ferreira; Agno N.S. Acioli; Alexandre C. Ferreira; Lilianne S. Maia; Telma A.C. Silva; et al. (Science of The Total Environment, 2023)

Developing New Scales of Personal Food Security - Rodrigo Aranda; David C. Ribar (Journal of the Academy of Nutrition and Dietetics, 2023)

Thermodynamic air-sea equilibration controls carbon isotopic composition of the South Atlantic thermocline during the last glacial period - Tainã M.L. Pinho; Cristiano M. Chiessi; Marília C. Campos; Rodrigo C. Portilho-Ramos; Gema Martínez-Méndez; Igor M. Venancio; Rodrigo A. Nascimento; Stefano Crivellari; Ana L.S. Albuquerque; Helge W. Arz; Ralf Tiedemann; André Bahr; et al. (Global and Planetary Change, 2023)

Metagenomic and isotopic signatures of the Amazon River plume into the southern red snapper fish (Lutjanus purpureus) - Luciane de C. Nogueira; Nils E. Asp; Carlos E. Rezende; Rodrigo Petry C. Sousa; Breno Barros; Raphael Paixão; Pedro V. Gatts; Cristiane C. Thompson; Ronaldo B. Francini-Filho; Marcelo Vallinoto; Fabiano L. Thompson (Estuarine, Coastal and Shelf Science, 2023)

Evaluation of the effects of cut design parameters on the environmental performance of a kirigami-inspired façade concept - Rodrigo Arauz; Aminallah Pourasghar; John C. Brigham (Energy and Buildings, 2023)

Anti-Candida Potential of Peptides from Immature and Ripe Fruits of Capsicum chinense Jacq - Marilucia C. Ribeiro; Rodrigo S. Gebara; Gabriel B. Taveira; André de O. Carvalho; Rosana Rodrigues; Erica O. Mello; Celso S. Nagano; Renata P. Chaves; Valdirene M. Gomes (Probiotics and Antimicrobial Proteins, 2023)

Bioplastics from orange processing byproducts by an ecoefficient hydrothermal approach - Leticia B. Santos; Rodrigo D. Silva; Jovan D. Alonso; Michel Brienzo; Natalia C. Silva; Giovanni Perotto; Caio G. Otoni; Henriette M.C. Azeredo (Food Packaging and Shelf Life, 2023)

Interaction of Aspergillus niger in Double-Coated Urea Granules Reduces Greenhouse Gas Emissions from N Fertilization - Vinícius F. Majaron; Marisa G. da Silva; Marcela Pfeifer; Ricardo Bortoletto-Santos; Camila C. V. Velloso; Rodrigo Klaic; Wagner L. Polito; Sidney J. L. Ribeiro; Alberto C. C. Bernardi; Cristiane S. Farinas; Caue Ribeiro (Journal of Soil Science and Plant Nutrition, 2023)

Subacute high-refined carbohydrate diet leads to abnormal reproductive control of the hypothalamic-pituitary axis in female rats - Jeanini Zimerman; Oscar M.S. Niño; Charles S. da Costa; Jordana F. Zanol; Milena Comério; Letícia N. da Gama de Souza; Leandro Miranda-Alves; Rosiane A. Miranda; Patrícia C. Lisboa; Tays A. Camilo; Rodrigo Rorato; Guilherme Andrade Alves; et al. (Reproductive Toxicology, 2023)

Hepatic arteriovenous malformation in a calf - Yanca G.S. Soares; Jefferson S. Ferreira; Édipo M. Campos; Rodrigo C. Alves; Ialys M. Leite; Laynaslan A. Soares; Mirele A.S. Ferreira; Antonio F.M. Dantas; Franklin Riet-Correa; Glauco J.N. Galiza (Journal of Comparative Pathology, 2023)

Impact of adding xylooligosaccharides encapsulated in butter: Microstructural, optical, rheological and sensory aspects - Mariana C. Rosa; Benjamin Mahieu; Elson Rogério Tavares Filho; Rodrigo N. Cavalcanti; Manoela Martins; Louise A. Sobral; Celso Sant'Anna; Erick A. Esmerino; Rosana Goldbeck; Tatiana C. Pimentel; Marcia Cristina Silva; Adriano G. Cruz (Food Research International, 2023)

Physical-biological drivers modulating phytoplankton seasonal succession along the Northern Antarctic Peninsula - Raul Rodrigo Costa; Afonso Ferreira; Márcio S. de Souza; Virginia M. Tavano; Rodrigo Kerr; Eduardo R. Secchi; Vanda Brotas; Tiago S. Dotto; Ana C. Brito; Carlos Rafael B. Mendes (Environmental Research, 2023)

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Glutamine supplementation accelerates functional recovery of EDL muscles after injury by modulating the expression of S100 calcium-binding proteins - Audrei R. Santos; Tatiana E. Koike; Alana M. Santana; Natalya C. Miranda; Rodrigo A. Dell Aquila; Thiago C. Silva; Marcelo S. Aoki; Elen H. Miyabara (Histochemistry and Cell Biology, 2023)

Morphological traits for allometric scaling of the European Sea Bass Dicentrarchus labrax (Linnaeus, 1758) from Southern Portugal population - Ana Azevedo; Luiz C. Navarro; Thaís Cavalheri; Hugo G. Santos; Irene Martins; Rodrigo Ozório (Journal of Fish Biology, 2023)
The present study aimed to determine the allometric scaling among a selection of morphological traits in European sea bass ( Dicentrarchus labrax ) to estimate fish body weight. A set of morphological traits (fish body weight, length, height, and width) were directly measured in 146 fish of a recirculating aquaculture system, with body weights ranging from 17.11 to 652.21 g. In addition, a collection of digital imagery of each anesthetized fish from the side and top views were used to estimate other traits (indirect measures). Multiple regression analysis and regression coefficients were calculated using all possible combinations of biometric data (predictors) to estimate fish body weight, applying different numerical fitting models (linear, log‐linear, quadratic, exponential). The results showed that the best combination of traits for estimating fish body weight were fish body width, length and height, collected from direct measure ( R 2 = 0.995), for a log‐linear model fitting, which revealed more accurate determinations than the most commonly used length–weight relationship. Nevertheless, other combinations of morphological traits and fitting models were also found to be suitable in successfully predict fish body weight, with variability ranging between 92.5% and 98.5%. For indirect measures, the best predictor was a combination of traits from top view (width, eye distance and area without fins) fitted with a log‐linear function. These results comprise a relevant baseline in supporting the high potential of noninvasive methods to accurately follow the growth of European sea bass juveniles, recurring to imagery analysis of anesthetized fish. It has major potential applications in feeding consumption trials and fish growth models, as it allows for continuously following up fish growth under different experimental conditions without therein distress derived from manipulation.

Deep Learning-Based Approaches for Oil Spill Detection: A Bibliometric Review of Research Trends and Challenges - Rodrigo N. Vasconcelos; André T. Cunha Lima; Carlos A. D. Lentini; José Garcia V. Miranda; Luís F. F. de Mendonça; José M. Lopes; Mariana M. M. Santana; Elaine C. B. Cambuí; Deorgia T. M. Souza; Diego P. Costa; Soltan G. Duverger; Washington S. Franca-Rocha (Journal of Marine Science and Engineering, 2023)
Oil spill detection and mapping using deep learning (OSDMDL) is crucial for assessing its impact on coastal and marine ecosystems. A novel approach was employed in this study to evaluate the scientific literature in this field through bibliometric analysis and literature review. The Scopus database was used to evaluate the relevant scientific literature in this field, followed by a bibliometric analysis to extract additional information, such as architecture type, country collaboration, and most cited papers. The findings highlight significant advancements in oil detection at sea, with a strong correlation between technological evolution in detection methods and improved remote sensing data acquisition. Multilayer perceptrons (MLP) emerged as the most prominent neural network architecture in 11 studies, followed by a convolutional neural network (CNN) in 5 studies. U-Net, DeepLabv3+, and fully convolutional network (FCN) were each used in three studies, demonstrating their relative significance too. The analysis provides insights into collaboration, interdisciplinarity, and research methodology and contributes to the development of more effective policies, strategies, and technologies for mitigating the environmental impact of oil spills in OSDMDL.

Acute Effects of Fluoxetine on Stress Responses and Feeding Motivation in Nile Tilapia - Julia P. G. A. Miranda; Ana Beatriz J. Isaac; Rebeca B. Silva; Leandro C. S. Toledo; Leonardo J. G. Barcellos; Helton Carlos Delicio; Rodrigo Egydio Barreto (Fishes, 2023)
The selective serotonin reuptake inhibitor fluoxetine is one of the most commonly administered psychotropic medications; however, it has been recognized as toxic to aquatic life. In this study, we showed that stress responses and feeding motivation in Nile tilapia were affected by acute exposure to fluoxetine. To reach that conclusion, we exposed Nile tilapia to 0, 1 or 10 µg/L (environmentally/biologically relevant doses) of fluoxetine over a 24 h period and then exposed them to a handling stressor. We found that the 10 µg/L dose enhanced cortisol response to stress but caused an earlier decrease in the ventilation boost induced by that stressor. An immediate ventilation boost after stressful stimuli indicates sympathetic activation. Thus, this suggests that fluoxetine decreased sympathetic nervous system activity but augmented hypothalamus–pituitary–interrenal axis activity in the fish. Both feeding latency and ingestion were similar among the tested conditions; however, a multiple logistic regression model revealed that in the presence of a stressor or fluoxetine, the Nile tilapia tended to ingest less food but there was a higher probability of this decrease to be associated with fluoxetine. We concluded that acute exposure to environmentally/biologically relevant fluoxetine concentrations over 24 h acted as a modifying factor for Nile tilapia stress physiology and tended to interfere with feeding motivation. An acute stress response is an emergency reaction that contributes to the recovery of homeostasis. In the presence of fluoxetine, modifications of acute stress responses and the tendency to reduce food intake, which restricts the ability to replace the energy spent on stress responses, could compromise the resumption of homeostasis and an animal’s adjustment to different environmental contexts, such as those associated with aquaculture, in which anthropogenic stressors inevitably occur.

From ecological functions to ecosystem services: linking coastal lagoons biodiversity with human well-being - Jorge L. Rodrigues-Filho; Rafael L. Macêdo; Hugo Sarmento; Victor R. A. Pimenta; Cecilia Alonso; Clarissa R. Teixeira; Paulo R. Pagliosa; Sérgio A. Netto; Natália C. L. Santos; Fábio G. Daura-Jorge; Odete Rocha; Paulo Horta; et al. (Hydrobiologia, 2023)

Equine endometrial Th1 and Th2 evaluation during early pregnancy - Gustavo R Larentis; Henrique B A Bastos; Giovani C Camozzato; Maria N Martinez; Luiz A M Centeno; Verônica L C Bueno; Gustavo H Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Evaluation of different platelet-rich plasma protocols for use in the equine reproductive clinic - Joel N De Oliveira; Henrique Ba Bastos; Veronica LC Bueno; Gustavo R Larentis; Rodrigo C Mattos; Adriana P Neves (Journal of Equine Veterinary Science, 2023)

Endometrial fibrosis in mares: Picrosirius Red and Collagen-2 and 3 - Luiz Augusto M Centeno; Henrique BA Bastos; Verônica LC Bueno; Janislene M Trentin; Gustavo R Larentis; Mariani F Fiorenza; Welden Panziera; Gustavo Henrique Z Winter; Sandra Fiala-Rechsteiner; Rodrigo C Mattos; Mara Iolanda B Rubin (Journal of Equine Veterinary Science, 2023)

Proteomic profile of stallion seminal plasma - Sandra Fiala-Rechsteiner; Veronica LC Bueno; Edvaldo Barros; Camilo JR López; Pedro MP Vidigal; Humberto JO Ramos; Henrique BA Bastos; Rodrigo C Mattos (Journal of Equine Veterinary Science, 2023)

Metabolomics profile of equine seminal plasma - Veronica LC Bueno; Henrique BA Bastos; Gustavo R Larentis; Gustavo HZ Winter; Rodrigo C Mattos; Sandra Mara E Rechsteiner (Journal of Equine Veterinary Science, 2023)

Synchronised disturbances in spruce- and beech-dominated forests across the largest primary mountain forest landscape in temperate Europe - Ondrej Kameniar; Ondřej Vostarek; Martin Mikoláš; Marek Svitok; Michal Frankovič; Robert C. Morrissey; Daniel Kozák; Thomas A. Nagel; Martin Dušátko; Jakob Pavlin; Matej Ferenčík; William S. Keeton; et al. (Forest Ecology and Management, 2023)

Green synthesized silver nanoparticles for iron and manganese ion removal from aqueous solutions - Leonardo C. Moraes; Marcelo P. Gomes; Rodrigo Ribeiro-Andrade; Queila S. Garcia; Cleber C. Figueredo (Environmental Pollution, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Multiproxy reconstruction of late quaternary upper ocean temperature in the subtropical southwestern Atlantic - Joana F. Cruz; Ioanna Bouloubassi; Arnaud Huguet; Alice M.S. Rodrigues; Thiago P. Santos; Igor M. Venancio; Douglas Lessa; Rodrigo L. Sobrinho; Rodrigo A. Nascimento; Marcelo C. Bernardes (Quaternary Science Reviews, 2023)

Green cover and socioemotional and academic outcomes of school-age children. The case of Santiago, Chile - Rodrigo Perez-Silva; Ignacio C. Fernández; María Isabel Matas; Esteban Villalobos (Landscape and Urban Planning, 2023)

Daily variability of pelagic metabolism in a subtropical lagoonal estuary - Luís Henrique Bordin; Eunice Da C. Machado; Carlos R.B. Mendes; Elisa H.L. Fernandes; Maurício G. Camargo; Rodrigo Kerr; Carlos A. Schettini (Journal of Marine Systems, 2023)

Simultaneous extraction and analysis of apple pomace by gradient pressurized liquid extraction coupled in-line with solid-phase extraction and on-line with HPLC - Laise C. Da Silva; Juliane Viganó; Vitor L. Sanches; Leonardo M. De Souza Mesquita; Rodrigo Pizani; Mauricio A. Rostagno (Food Chemistry, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Risk factors associated with sow mortality in breeding herds under one production system in the Midwestern United States - Rodrigo C. Paiva; Cesar A. Moura; Pete Thomas; Ben Haberl; Laura Greiner; Christopher J. Rademacher; Ana Paula S.P. Silva; Giovani Trevisan; Daniel C.L. Linhares; Gustavo S. Silva (Preventive Veterinary Medicine, 2023)

Where are they from and where are they going? Detecting areas of endemism, distribution patterns and conservation status of the order Spirostreptida in Brazil (Diplopoda, Juliformia) - Luiz F. M. Iniesta; Rodrigo S. Bouzan; Jackson C. Means; Kaloyan Ivanov; Antonio D. Brescovit (Biodiversity and Conservation, 2023)

Scientometric analysis and literature synthesis of 60 years of science on the Atlantic goliath grouper ( Epinephelus itajara ) - Anna C. P. Locatelli; Rodrigo F. Bastos; Matheus A. Oliveira; Beatrice P. Ferreira (Journal of Fish Biology, 2023)
Here, the authors investigate the evolution of scientific literature on the Atlantic goliath grouper ( Epinephelus itajara ), the largest grouper species in the Atlantic. This species was considered threatened according to the IUCN for nearly three decades due to overfishing and has been protected from fishing in a large part of its range. For the purpose of evaluating the scientific production on an endangered species banned from fishing, the authors present a scientometry and synthesis review analysing the literature produced in the timeline and the content of their studies. To this end, they set up an almost 60‐year literary database through the Scopus, Web of Science and Google Scholar platforms. They analyse the publication and knowledge area patterns over the time in the world and in Brazil. They also feature the main areas, locations, ecosystems and types of those research studies and briefly describe the main records found in each decade. An increase in the number of publications was observed from the 1990s onwards worldwide, and particularly in Brazil from the 2000s, coinciding with the pioneering legislations for species protection. Most of the studies were classified within ecology and conservation and took place in countries that implemented moratoriums and had extensive areas of mangroves. Thus, fishing moratorium, classification as endangered, mangroves distribution and conservation all play a role in the studies distribution and contribute positively to the knowledge, as well as support conservation strategies for the species and its ecosystems of occurrence.

Testing the context dependence of ant nutrient preference across habitat strata and trophic levels in N eotropical biomes - Chaim J. Lasmar; Tom R. Bishop; Catherine L. Parr; Antônio C. M. Queiroz; Icaro Wilker; Rodrigo M. Feitosa; Fernando A. Schmidt; Carla R. Ribas (Ecology, 2023)
Animals are integrated into the wider ecosystem via their foraging and behavior. The compensation hypothesis predicts that animals target their foraging efforts (i) toward nutrients that are scarce in the environment and (ii) toward nutrients that are not present in the usual diet of species, which varies across trophic levels. Understanding how foraging for resources varies locally, such as across habitat strata, and trophic levels will help to elucidate the links between the local environment and communities to the ecological functions that animals mediate. We examined whether the relative resource use of ants varies consistently along a habitat strata gradient and across trophic levels across Neotropical biomes. We placed 4500 baited tubes, each containing one of five liquid resources (sugar, amino acid, lipid, sodium, and distilled water) in one of three habitat strata (subterranean, epigaeic, and arboreal) across 60 transects in Amazon, Atlantic Forest, Caatinga, Cerrado, Pampa, and Pantanal biomes. We assessed the relative resource use of all ants across the habitat strata and among two different trophic groups across biomes. The relative preference for sugar increased from subterranean to arboreal strata in all biomes, while the relative preference for lipids decreased at this gradient in five biomes. We also found that in general sugar‐consuming ants foraged more for sugar and less for lipids than predatory ants across biomes. Conversely, we found no consistency across biomes in nutrient preference of amino acid and sodium across habitat strata or trophic levels. Overall, our results indicate sugar limitation in the arboreal stratum and lipid limitation on the ground across biomes and that the trophic level of ants strongly determines their foraging efforts—possibly because ants try to fix their dietary nutrient imbalances. Hence, our findings suggest strong local niche partitioning of sugar and lipid use across habitat strata and trophic levels and that other large spatial scale processes influence the local amino acid and sodium dynamics.

BTEX profile and health risk at the largest bulk port in Latin America, Paranaguá Port - Hugo Sarmiento; Sanja Potgieter-Vermaak; Guilherme C. Borillo; Ana Flavia L. Godoi; Rodrigo A. Reis; Carlos I. Yamamoto; Theotonio Pauliquevis; Gabriela Polezer; Ricardo H. M. Godoi (Environmental Science and Pollution Research, 2023)

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Ancient vicariance is reinforced by adaptive divergence in the southern beech: Contributions from geogenomics - Mariana Fasanella; Paula Mathiasen; Gabriela Juri; Dayana G. Díaz; Rodrigo Hasbún; Andrea C. Premoli (Journal of Biogeography, 2023)
Aim Geogenomics seeks to understand geological processes linked to lineage divergence. However, the mechanisms that conserve ancient signals in spite of gene flow are still unclear. In the southern beech, the deep lineage divergence produced by vicariant events is associated with ancient marine transgressions. We hereby evaluate the hypothesis that this divergence is maintained by diversifying selection. Location Southern Argentina and Chile. Taxon Nothofagus dombeyi. Methods The lineage divergence by means of analysis of molecular variance (AMOVA), principal coordinate analysis, assignment tests and multiple matrix regression analyses were assessed using chloroplast DNA and neutral and outlier single nucleotide polymorphisms (SNPs). Several environmental variables were used to characterize potential within‐species niche structuring and genotype–environment associations. Results Two deep‐rooted latitudinally structured lineages resulted from cpDNA, the northern cluster being more genetically diverse than the southern one. Of the total of 2943 SNPs, 33 identified as outliers and produced two genetic clusters. Neutral SNPs yielded no structure by AMOVA, whereas higher (>75%) F ST values were obtained for cpDNA and outlier SNPs. Precipitation variables were mostly associated with population clusters and suggested two climatic niches, consisting of cold and dry in the south and more variable precipitation, temperature and soil conditions in the north. Associations of genetic distance with environment and geography suggested isolation‐by‐distance and isolation‐by‐ecology or isolation‐by‐environment effects. Main conclusions Ancient lineage divergence in N. dombeyi, originally driven by vicariance, has been maintained by diversifying selection under distinct environmental conditions that also define distinct within‐species niches. Deeply rooted phylogeographical breaks can be conserved in continuously distributed species in the absence of current geographical barriers. Yet, physical gradients exert differential selective pressures, which are maintained in the face of potential gene flow. As a result, selection can lead to geographically localized and differentially adapted groups of populations that can be detected by a combination of traditional phylogeographical and novel genomic methods.

Development and Application of a Mechanistic Nutrient-Based Model for Precision Fish Farming - Filipe M. R. C. Soares; Ana M. D. Nobre; Andreia I. G. Raposo; Rodrigo C. P. Mendes; Sofia A. D. Engrola; Paulo J. A. P. Rema; Luís E. C. Conceição; Tomé S. Silva (Journal of Marine Science and Engineering, 2023)
This manuscript describes and evaluates the FEEDNETICS model, a detailed mechanistic nutrient-based model that has been developed to be used as a data interpretation and decision-support tool by fish farmers, aquafeed producers, aquaculture consultants and researchers. The modelling framework comprises two main components: (i) fish model, that simulates at the individual level the fish growth, composition, and nutrient utilization, following basic physical principles and prior information on the organization and control of biochemical/metabolic processes; and (ii) farm model, that upscales all information to the population level. The model was calibrated and validated for five commercially relevant farmed fish species, i.e., gilthead seabream (Sparus aurata), European seabass (Dicentrarchus labrax), Atlantic salmon (Salmo salar), rainbow trout (Oncorhynchus mykiss), and Nile tilapia (Oreochromis niloticus), using data sets covering a wide range of rearing and feeding conditions. The results of the validation of the model for fish growth are consistent between species, presenting a mean absolute percentage error (MAPE) between 11.7 and 13.8%. Several uses cases are presented, illustrating how this tool can be used to complement experimental trial design and interpretation, and to evaluate nutritional and environmental effects at the farm level. FEEDNETICS provides a means of transforming data into useful information, thus contributing to more efficient fish farming.

Technological role and metabolic profile of two probiotic EPS-producing strains with potential application in yoghurt: Impact on rheology and release of bioactive peptides - Elisa C. Ale; Rodrigo A. Ibáñez; Daniel J. Wilbanks; Guillermo H. Peralta; Fatma D. Ceylan; Ana G. Binetti; Bradley W. Bolling; John A. Lucey (International Dairy Journal, 2023)

Improved remediation of contaminated water using ZnO systems via chemical treatment: applications, implications and toxicological mitigation - Josy A. Osajima; Alexandro S. Sá; Rodrigo P. Feitosa; Marcelo B. Furtini; Luzia M. C. Honorio; Maria G. Fonseca; Pollyana Trigueiro; Paula Caregnato; Eduardo R. Triboni; Edson C. Silva-Filho (Sustainable Water Resources Management, 2023)

A new method based on machine learning to forecast fruit yield using spectrometric data: analysis in a fruit supply chain context - Javier E. Gómez-Lagos; Marcela C. González-Araya; Rodrigo Ortega Blu; Luis G. Acosta Espejo (Precision Agriculture, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Marine debris ingestion by odontocete species from the Southwest Atlantic Ocean: Absence also matter - Antonella Daira Padula; Rodrigo Machado; Lucas Milmann; M. Carolina de León; Joaquín C.M. Gana; Janaína C. Wickert; María Eugenia Argañaraz; Ricardo O. Bastida; Diego H. Rodríguez; Pablo E. Denuncio (Marine Pollution Bulletin, 2023)

What are the factors associated with pregnancy loss after timed-artificial insemination in Bos indicus cattle? - Carlos E.C. Consentini; Rodrigo L.O.R. Alves; Mateus A. Silva; Juan P.A. Galindez; Guilherme Madureira; Laísse G. Lima; José R.S. Gonçalves; Milo C. Wiltbank; Roberto Sartori (Theriogenology, 2023)

Quantification of the food-water-energy nexus in urban green and blue infrastructure: A synthesis of the literature - Fanxin Meng; Qiuling Yuan; Rodrigo A Bellezoni; Jose A. Puppim de Oliveira; Silvio Cristiano; Aamir Mehmood Shah; Gengyuan Liu; Zhifeng Yang; Karen C. Seto (Resources, Conservation and Recycling, 2023)

Ecosystem-atmosphere CO2 exchange from semiarid mangroves in the Gulf of California - Martha L. Vargas-Terminel; Julio C. Rodríguez; Enrico A. Yépez; Carlos A. Robles-Zazueta; Christopher Watts; Jaime Garatuza-Payán; Rodrigo Vargas; Zulia M. Sanchez-Mejia (Journal of Arid Environments, 2023)

An unprecedented hybrid polyoxometalate based on niobium oligomers: A notable application as redox supercapacitor electrode - Rodrigo L. Lavall; Pedro S.C. de Oliveira; Paulo F.R. Ortega; João P.C. Trigueiro; José B. Gabriel; Ana P. Heitmann; Poliane Chagas; Cinthia C. Oliveira; Luiz C.A. Oliveira (Chemical Engineering Journal, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Soil flooding and its outcome on cadmium and nutrient uptake affect photosynthetic activity in Inga laurina plants - Namir G. M. Lopes; Rodrigo B. Kloss; Ivanildes C. dos Santos; Vânia L. Souza; Majeti N. V. Prasad; Pedro A. O. Mangabeira; Marcel G. C. França (Ecotoxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Application of linear mixed models for multiple harvest/site trial analyses in perennial plant breeding - Saulo F. S. Chaves; Jeniffer S. P. C. Evangelista; Rodrigo S. Alves; Filipe M. Ferreira; Luiz A. S. Dias; Rafael M. Alves; Kaio O. G. Dias; Leonardo L. Bhering (Tree Genetics & Genomes, 2022)

Drugs and Endogenous Factors as Protagonists in Neurogenic Stimulation - Raphaela A. Chiareli; Bruno L. Marques; Gustavo A. de Carvalho; Raysa T. V. de Souza; Pedro H. G. Santana; Helton C. Santiago; Mauro C. X. Pinto; Alexander Birbrair; Ricardo C. Parreira; Henning Ulrich; Rodrigo R. Resende (Stem Cell Reviews and Reports, 2022)

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Density, habitat use and activity patterns of the last giant armadillo population in the Brazilian Atlantic Forest - Juliana B. Pasa; Rodrigo L. Massara; Cynthia E. Widmer; Arnaud L. J. Desbiez; Gabriel F. Massocato; Lucas M. Barreto; Fernando C. C. Azevedo (Mammalian Biology, 2022)

Leveraging multi-harvest data for increasing genetic gains per unit of time for fruit yield and resistance to witches’ broom in Theobroma grandiflorum - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Rafael M. Alves; Jeniffer S. P. C. Evangelista; Kaio O. G. Dias (Euphytica, 2022)

Restaurateurs’ context, decisions, and views on supporting sustainable seafood: Insights from Chile - C. Josh Donlan; Michael G. Sorice; Francisco J. Contreras-Drey; Rodrigo Oyanedel; M. Isidora Ávila-Thieme; Stefan Gelcich (Frontiers in Marine Science, 2022)
While restauranteurs are important actors in seafood systems, information on their decisions and views on sustainability is lacking. Using mixed methods, we explored Chilean restauranters’ contexts, decisions, and views on seafood sustainability. Menus in Chile are diverse and dominated by domestic and wild-caught sources. Restauranters are willing to participate in traceability programs, especially when it is for both sustainability and health safety reasons. Restauranters believe that seafood is an elite resource and high prices are inhibiting access. They also believe patrons care little about seafood sustainability yet are willing to pay a premium for it. This contradiction suggests a mechanism for activating values via situational factors. While demand and benefits for seafood traceability programs appear present, challenges threaten successful implementation. Complex socio-economic factors, such as affordability, elitism, and inequity, need to be integrated into traceability program design to contribute to the necessary transformation of seafood systems.

Effects of Intra-REV Pore Distribution Modeling in the Flow of Non-Newtonian Fluids in Porous Media - Allan B. G. Motta; Roney L. Thompson; Mateus P. Schwalbert; Luiz F. L. R. Silva; Jovani L. Favero; Rodrigo A. C. Dias; Raphael J. Leitão (Transport in Porous Media, 2022)

Economic, social, and environmental assessment of farming Nile tilapia in net-cages in a reservoir in hot semi-arid region during an extended drought event - Gustavo Gonzaga Henry-Silva; Júlio César da Silva Cacho; Rodrigo Sávio Teixeira Moura; Dallas Lee Flickinger; Wagner C. Valenti (Environmental Science and Pollution Research, 2022)

Models to predict live weight from heart girth in crossbred beef heifers - Denis R. Chico-Alcudia; Rodrigo Portillo-Salgado; Enrique Camacho-Pérez; Jorge A. Peralta-Torres; Juan C. Angeles-Hernandez; Alfonso L. Muñoz-Benitez; Víctor Hugo Severino Lendechy; Antonio Leandro Chaves Gurgel; Gelson dos Santos Difante; Luís Carlos Vinhas Ítavo; Alfonso J. Chay-Canul (Tropical Animal Health and Production, 2022)

AsES elicitor induces ethylene production, accelerates ripening, and prevents Botrytis cinerea rot in strawberry fruit - Silvia M. Perato; Ramiro N. Furio; Rodrigo H. Tomas-Grau; Sergio M. Salazar; Juan C. Díaz Ricci; Martín G. Martinez-Zamora (European Journal of Plant Pathology, 2022)

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Outbreak of canine distemper and coinfections in a maned wolf (Chrysocyon brachyurus) and in three giant anteaters (Myrmecophaga tridactyla) - Lucas R. Souza; Marcelo P. N. Carvalho; Carlos E. B. Lopes; Marcelo C. Lopes; Bruna H. Campos; Érika P. T. Teixeira; Ellen J. Mendes; Leidilene P. Santos; Eduardo A. Caixeta; Erica A. Costa; João L. R. Cunha; Ana L. S. Fraiha; et al. (Brazilian Journal of Microbiology, 2022)

An invasive population of Roseau Cane Scale in the Mississippi River Delta, USA originated from northeastern China - Scott A. Schneider; Hannah J. Broadley; Jeremy C. Andersen; Joseph S. Elkinton; Shaw-Yhi Hwang; Chenxi Liu; Suzuki Noriyuki; Jong-Seok Park; Hang Thi Dao; Matthew L. Lewis; Juli R. Gould; Kim A. Hoelmer; et al. (Biological Invasions, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

On the replacement of traditional stabilizers by guaiacol in environmentally safe nitrocellulose-based propellants - Rodrigo L. B. Rodrigues; Ana Paula da Silva; Rogério Rosato; Maurício F. Lemos; Fernando C. Peixoto; Tanos C. C. França; Letivan G. Mendonça Filho (Clean Technologies and Environmental Policy, 2022)

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Oil spill detection based on texture analysis: how does feature importance matter in classification? - Rodrigo N. Vasconcelos; Carlos A. D. Lentini; André T. Cunha Lima; Luís F. F. Mendonça; Garcia V. Miranda; Elaine C. B. Cambuí; Diego Pereira Costa; Soltan Galano Duverger; Mainara B. Gouveia; José M. Lopes; Milton J. Porsani (International Journal of Remote Sensing, 2022)

Thallium Differentially Affects Macronutrients Concentration and Stoichiometric Ratios with Nitrogen in the Leaves of Chili Pepper Varieties - María de la Luz Buendía-Valverde; Fernando C. Gómez-Merino; Tarsicio Corona-Torres; Serafín Cruz-Izquierdo; Rodrigo A. Mateos-Nava; Libia I. Trejo-Téllez (Water, Air, & Soil Pollution, 2022)

Development and selection of transgenic advanced lines of carioca seeded common bean with multiple resistance to viruses - Rodrigo S. Silva; Josias C. Faria; Adriano M. Knupp; Marcelo S. Aguiar; Helton S. Pereira; Amanda L. Ferreira; Antonia L. M. Zaidem; Patrícia V. Pinheiro; Leonardo C. Melo; Thiago Lívio P. O. Souza (Euphytica, 2022)

Impact of invasive marmosets (Primates, Callitrichidae) on bird acoustic diversity in a large neotropical urban forest - Marina T. Zaluar; Rodrigo Tardin; Diego Llusia; Julia Niemeyer; Milton C. Ribeiro; Mariana M. Vale (Biological Invasions, 2022)

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

On the Utilization of Dietary Glycerol in Carnivorous Fish - Part I: Insights Into Hepatic Carbohydrate Metabolism of Juvenile Rainbow Trout (Oncorhynchus mykiss) and European Seabass (Dicentrarchus labrax) - Ivan Viegas; Ludgero C. Tavares; Elisabeth Plagnes-Juan; Emanuel Silva; João Rito; Lucie Marandel; Mariana Palma; Rodrigo O. A. Ozório; Leonardo J. Magnoni; Stéphane Panserat (Frontiers in Marine Science, 2022)
Glycerol is a 3-carbon sugar alcohol successfully employed as an alternative feed ingredient for land-farmed animals and more recently for farmed fish. While most studies address zootechnical performance, few have delved into the metabolic utilization of dietary glycerol. A growth trial was performed using diets with increasing levels of glycerol (0, 2.5 and 5%) on two relevant species for aquaculture: rainbow trout (8-week trial; 3 tank per diet/25 fish per tank, on a 15 ± 1°C flow-through freshwater system); and European seabass (6-week trial; 5 tank per diet/6-8 fish per tank on a 21°C indoor saltwater RAS system). After this period, fish were subjected to a metabolic trial consisting of a 6-day residence in deuterated water ( 2 H 2 O). Measurements of blood glucose and hepatic glycogen 2 H-enrichments through Nuclear Magnetic Resonance, complemented by mRNA levels of key-enzymes for intermediary metabolism were used to evaluate the catabolic pathways of dietary glycerol. Dietary glycerol had no impact on plasma glucose, but hepatic glycogen levels increased significantly with increasing dietary glycerol levels in both species. While trout was able to regulate circulating glycerol plasma, seabass presented elevated levels on the glycerol-supplemented diets. Despite revealing some significant differences between sampling time (6 and 24 h), none of the enzymes’ mRNA levels responded to the dietary treatment. In trout, the main source of blood glucose was not labeled with 2 H (~60%, likely from diet) while other contributors did not differ with glycerol supplementation. In seabass, the unlabeled contribution was approximately half of that observed in trout (~30%), accompanied by a significant increase of gluconeogenic contributions at the triose-phosphate level to the blood glucose with increasing dietary glycerol. In trout, labeling from 2 H 2 O into hepatic glycogen revealed significant differences, with the contribution from the indirect pathway at the triose-phosphate level increasing with increased dietary glycerol. No such differences were found in seabass’ glycogen pool. These findings suggest that fish species are able to retain, catabolize glycerol and incorporate it into carbohydrates. The gluconeogenic utilization of exogenous glycerol differed between species and affected the synthesis of hepatic glycogen in trout and the appearance of blood glucose in seabass.

On the Utilization of Dietary Glycerol in Carnivorous Fish—Part II: Insights Into Lipid Metabolism of Rainbow Trout (Oncorhynchus mykiss) and European Seabass (Dicentrarchus labrax) - Ivan Viegas; Mariana Palma; Elisabeth Plagnes-Juan; Emanuel Silva; João Rito; Luís F. Henriques; Ludgero C. Tavares; Rodrigo O. A. Ozório; Stéphane Panserat; Leonardo J. Magnoni (Frontiers in Marine Science, 2022)
Glycerol is the by-product of biodiesel production and its utilisation in fish feed has recently gained relevance. As an important metabolic intermediate and structural component of triacylglycerol (TAG), it is still unclear whether its supplementation affects lipid utilisation and/or deposition in different tissues. Accordingly, a set of studies was aimed to evaluate how increasing levels of dietary glycerol (0, 2.5 and 5%) affect lipid synthesis in the liver, muscle and adipose tissue. After a growth trial with rainbow trout (8 weeks) and European seabass (6 weeks) fish were sampled at 6 and 24 h to assess mRNA levels of lipid metabolism-related enzymes. The remaining fish were subjected to a metabolic trial consisting of a 6-day residence in deuterated water ( 2 H 2 O) for metabolic flux calculations. This study stands as the second part of a broader experiment that also aimed at evaluating the carbohydrate metabolism ( Viegas et al., 2022 ). Dietary supplementation at 5% glycerol significantly increased plasma TAG levels in both species and liver TAG levels in seabass, with no repercussions on the perivisceral fat index. Despite responding as expected in a postprandial setting, only fas and Δ6-fad in trout and Δ6-fad in seabass responded significantly by increasing with the dietary supplementation of glycerol. In trout, the observed differences in the regulation of these enzymes were not reflected in the de novo lipogenic fluxes. The fractional synthetic rates (FSR) were overall low in all tissues with an average of 0.04, 0.02 and 0.01% d –1 , for liver, muscle and perivisceral fat, respectively. In seabass on the other hand, and despite increased mRNA levels in Δ6-fad, the overall lipid profile in the liver muscle and perivisceral fat was higher in MUFA at the expense of lower PUFA. Moreover, glycerol supplementation altered the lipogenic capacity of seabass with hepatic fractional synthetic rates for TAG-bound FA increasing with increasing glycerol levels (0.32 ± 0.18, 0.57 ± 0.18, and 0.82 ± 0.24 for 0%, 2.5% and 5% glycerol supplementation, respectively). The findings of the present study suggest that supplementation up to 2.5% of glycerol did not severely impact the lipid metabolism nor increased lipogenic potential in liver, muscle and perivisceral fat accumulation.

Response of three local chicken ecotypes of Ghana to lentogenic and velogenic Newcastle disease virus challenge - Christopher K. Tudeka; George K. Aning; Augustine Naazie; Princess K. Botchway; Esinam N. Amuzu-Aweh; Godwin K. Agbenyegah; Ben Enyetornye; Diana Fiadzomor; Perot Saelao; Ying Wang; Terra R. Kelly; Rodrigo Gallardo; et al. (Tropical Animal Health and Production, 2022)

Current Panorama, Practice Gaps, and Recommendations to Accelerate the Transition to a Circular Bioeconomy in Latin America and the Caribbean - Rodrigo Salvador; Reinalda Blanco Pereira; Gabriel Fernandes Sales; Vanessa Campana Vergani de Oliveira; Anthony Halog; Antonio C. De Francisco (Circular Economy and Sustainability, 2022)

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Growth estimates of young‐of‐the‐year broadnose sevengill shark, Notorynchus cepedianus , a top predator with poorly calcified vertebrae - Andrés Javier Jaureguizar; Federico Cortés; J. Matias Braccini; Rodrigo Wiff; Andrés C. Milessi (Journal of Fish Biology, 2022)
The broadnose sevengill shark, Notorynchus cepedianus (Péron, 1807), is a large marine top predator in temperate coastal ecosystems. Some aspects of its life history have been determined, but its growth pattern is yet to be fully understood. The authors used a multi‐modelling approach and a sensitivity test to estimate growth parameters from young‐of‐year (YOY) length data collected off San Antonio Cape (SAC), Argentina, a critical habitat in the Southwest Atlantic Coastal Zone (SACZ). The best selected model, a sex‐combined logistic growth model, estimated an asymptotic length ( L ∞ ) of 92.58 cm TL (95% C.I. : 86.48–105.89 cm), a growth coefficient (K) of 0.006818 days −1 (95% C.I. : 0.004948–0.008777) and a size at birth ( L 0 ) of 40.73 cm. The predicted annual growth ( i.e ., L 1 – L 0 ) was 43.2 cm TL. Males had smaller L 0 , higher K and achieved larger sizes after 1 year. The YOY in SAC attained a larger L 1 and grew faster than their Australian and South African wild counterparts. The consistent year‐round presence of YOY in the SAC highlights the importance of this area as a pupping ground and potential nursery for N. cepedianus ; this has direct implications for the allocation of research and management effort for the conservation of this species in the Southwest Atlantic.

Mouse Neural Stem Cell Differentiation and Human Adipose Mesenchymal Stem Cell Transdifferentiation Into Neuron- and Oligodendrocyte-like Cells With Myelination Potential - Anderson K. Santos; Katia N. Gomes; Ricardo C. Parreira; Sérgio Scalzo; Mauro C. X. Pinto; Helton C. Santiago; Alexander Birbrair; Ulrich Sack; Henning Ulrich; Rodrigo R. Resende (Stem Cell Reviews and Reports, 2022)

Sympathetic nerve-adipocyte interactions in response to acute stress - Gabryella S. P. Santos; Alinne C. Costa; Caroline C. Picoli; Beatriz G. S. Rocha; Sheu O. Sulaiman; Debora C. Radicchi; Mauro C. X. Pinto; Miguel L. Batista; Jaime H. Amorim; Vasco A. C. Azevedo; Rodrigo R. Resende; Niels O. S. Câmara; et al. (Journal of Molecular Medicine, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Association of breakfast skipping with cardiovascular outcomes and cardiometabolic risk factors: an updated review of clinical evidence - Heitor O. Santos; Rafael Genario; Rodrigo C. O. Macedo; Manan Pareek; Grant M. Tinsley (Critical Reviews in Food Science and Nutrition, 2022)

Extreme bill dimorphism leads to different but overlapping isotopic niches and similar trophic positions in sexes of the charismatic extinct huia - Barbara M. Tomotani; Rodrigo B. Salvador; Amandine J. M. Sabadel; Colin M. Miskelly; Julie C. S. Brown; Josette Delgado; Patrick Boussès; Yves Cherel; Susan M. Waugh; Sarah J. Bury (Oecologia, 2022)
The New Zealand huia ( Heteralocha acutirostris ) had the most extreme bill sexual dimorphism among modern birds. Given the quick extinction of the species, the cause of the dimorphism could only be hypothesised to reflect different trophic niches and reduce male/female competition. We tested that hypothesis by combining museum specimens, geometric morphometrics, and isotopic analyses. We used geometric morphometrics to describe bill shape; measured bulk ( δ 15 N bulk ) and ( δ 13 C bulk ) values from feather as proxies of the birds’ foraging habitat and diet; and compared compound-specific stable isotopes analyses (CSIA) of nitrogen in amino acids ( δ 15 N AA ) in male–female pairs to estimate their trophic position. Sexes had significantly different, but overlapping feather δ 15 N bulk and δ 13 C bulk values, but δ 15 N AA indicated identical trophic positions and δ 15 N bulk was not related to bill shape. Trophic position was less variable among females, consistent with a specialised foraging behaviour and, thus, supporting a partial male/female foraging segregation.

Elusive deer occurrences at the Atlantic Forest: 20 years of surveys - Márcio Leite de Oliveira; Francisco Grotta-Netto; Pedro Henrique de Faria Peres; Alexandre Vogliotti; Carlos Rodrigo Brocardo; Jorge José Cherem; Mariana Landis; Roberta Montanheiro Paolino; Roberto Fusco-Costa; Andressa Gatti; Danielle Oliveira Moreira; Paula Modenesi Ferreira; et al. (Mammal Research, 2022)

Severity of SARS-CoV-2 infection is linked to double-negative (CD27− IgD−) B cell subset numbers - Rodrigo Cervantes-Díaz; Víctor Andrés Sosa-Hernández; Jiram Torres-Ruíz; Sandra Romero-Ramírez; Mariana Cañez-Hernández; Alfredo Pérez-Fragoso; José C. Páez-Franco; David E. Meza-Sánchez; Miriam Pescador-Rojas; Víctor Adrián Sosa-Hernández; Diana Gómez-Martín; José L. Maravillas-Montero (Inflammation Research, 2022)

From Settlers to Subspecies: Genetic Differentiation in Commerson’s Dolphins Between South America and the Kerguelen Islands - Sebastián Kraft; MJosé Pérez-Alvarez; Carlos Olavarría; Rodrigo Moraga; C. Scott Baker; Debbie Steel; Paul Tixier; Christophe Guinet; Amelia Viricel; Paul Brickle; Marina Costa; Enrique Crespo; et al. (Frontiers in Marine Science, 2021)
Commerson’s dolphins ( Cephalorhynchus commersonii ) are separated into the subspecies C. c. commersonii , found along southern South America (SA) and the Falkland Islands/Islas Malvinas (FI/IM), and C. c. kerguelenensis , restricted to the subantarctic Kerguelen Islands (KI). Following the dispersal model proposed for the genus, the latter is thought to have originated from SA after a long-distance dispersal event. To evaluate this biogeographic scenario, a distribution-wide, balanced sampling of mitochondrial DNA (mtDNA) control region sequences was designed. New tissue samples from southern Chile, Argentina, FI/IM, and KI were added to published sequences from SA and KI, for a total of 256 samples. Genetic diversity indices, genetic and phylogeographic structure, and migration rates were calculated. One haplotype was shared between subspecies, with which all haplotypes of C. c. kerguelenensis formed a distinct group in the haplotype network. A new haplotype for C. c. kerguelenensis is reported. Differentiation in haplotype frequencies was found among localities within the distribution of C. c. commersonii , yet the phylogeographic signal was only statistically significant between subspecies. Coalescent-based historical gene flow estimations indicated migration between the northern and southern portions of the species’ range in SA as well as between SA and the FI/IM, but not between these and the KI. The net nucleotide divergence between dolphins from SA and the FI/IM was lower than the recommended threshold value suggested for delimiting subspecies, unlike that found between C. c. commersonii and C. c. kerguelenensis . The results are consistent with the model of post-glacial colonization of KI by South American C. commersonii , followed by an ongoing divergence process and subspecies status. Thus, C. c. kerguelenensis may represent the most recent diversification step of Cephalorhynchus , where isolation from their source population is driving a process of incipient speciation.

The microbiome of a shell mound: ancient anthropogenic waste as a source of Streptomyces degrading recalcitrant polysaccharides - Luciano F. Huergo; Marcelo Conzentino; Maria V. Gonçalves; Marcos V. Gernet; Rodrigo A. Reis; Fábio O. Pedrosa; Valter A. Baura; Araceli Pires; Edileusa C. M. Gerhardt; Thalita R. Tuleski; Eduardo Balsanelli; Dieval Guizelini; et al. (World Journal of Microbiology and Biotechnology, 2021)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Penguin predation by extra-limital sub-Antarctic fur seals Arctocephalus tropicalis - Rodrigo Machado; Martin Sucunza Perez; Bernardo A. Arús; Renan C. de Lima; Silvina Botta; Victor Hugo Valiati; Larissa R. Oliveira; Caio J. Carlos (Polar Biology, 2021)

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

Subterranean “oasis” in the Brazilian semiarid region: neglected sources of biodiversity - Diego de M. Bento; Marconi Souza-Silva; Alexandre Vasconcellos; Bruno C. Bellini; Xavier Prous; Rodrigo L. Ferreira (Biodiversity and Conservation, 2021)

LT‐Brazil: A database of leaf traits across biomes and vegetation types in Brazil - Eduardo Mariano; Taciana F. Gomes; Silvia R. M. Lins; Adibe L. Abdalla‐Filho; Amin Soltangheisi; Maria G. S. Araújo; Rodrigo F. Almeida; Fernanda G. Augusto; Luiza P. Canisares; Siglea S. F. Chaves; Cristiane F. G. Costa; Thaís R. Diniz‐Reis; et al. (Global Ecology and Biogeography, 2021)
Motivation Leaf traits represent an important component of plant functional strategies, and those related to carbon fixation and nutrient acquisition form the leaf economics spectrum. However, observations of functional leaf traits are underrepresented in tropical regions in comparison with those in temperate areas. Brazil, a country with continental scale and vast biodiversity is a timely example, where many biomes are impacted by human activities and climate change. However, leaf traits relevant to understand vegetation responses to these impacts remain poorly quantified for many species found in the country. We compiled an extensive data set of four functional leaf traits for native woody species occurring in the Brazilian territory. In addition to trait observations, sampling dates and geo‐references were compiled and climatic parameters and soil properties of each sampling site were extracted from several databases. Main types of variables contained The LT‐Brazil data set contains 3,479, 1,216, 775 and 775 clean observations of leaf mass per area, leaf nitrogen (N) concentration per unit mass, leaf phosphorus (P) concentration per unit mass, and leaf N : P ratio, respectively, from native woody species, encompassing information of biome, vegetation, taxonomic data, geographical coordinates, climatic parameters, as well as soil properties. Spatial location and grain We compiled trait observations from 223 sites under native vegetation distributed in all main biomes (i.e., Amazônia, Caatinga, Cerrado, Mata Atlântica, Pampa and Pantanal) across the Brazilian territory. Time period and grain The data represent information published and/or sampled during the last 25 years. Major taxa and level of measurement Our compilation was focused on trait data observed for native woody species, excluding monocots, palm trees, herbs, and hemiparasitic plants. Thus, 108, 478 and 1,321 botanical families, genera and species were included, covering c . 9% of the woody angiosperm flora of Brazil. Software format Data are provided as comma‐separated value (.csv) files.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Circulating Nestin-GFP+ Cells Participate in the Pathogenesis of Paracoccidioides brasiliensis in the Lungs - Leda M. C. Coimbra-Campos; Walison N. Silva; Ludmila M. Baltazar; Pedro A. C. Costa; Pedro H. D. M. Prazeres; Caroline C. Picoli; Alinne C. Costa; Beatriz G. S. Rocha; Gabryella S. P. Santos; Fabrício M. S. Oliveira; Mauro C. X. Pinto; Jaime H. Amorim; et al. (Stem Cell Reviews and Reports, 2021)

Combined and isolated effects of alcohol consumption and sleep deprivation on maximal strength, muscle endurance and aerobic exercise performance in healthy men: a cross-over randomized controlled trial - Rodrigo Rodrigues; Rodrigo de Azevedo Franke; Bruno C. Teixeira; Rodrigo C. O. Macedo; André Luiz Lopes; Fernando Diefenthaeler; Álvaro Reischak-Oliveira; Bruno Manfredini Baroni; Marco Aurélio Vaz (Sleep and Biological Rhythms, 2021)

A new species of viviparous brotula genus Pseudogilbia (Ophidiiformes: Dinematichthyidae) from Brazilian reefs, with an updated diagnosis of the genus - Arthur B. Bauer; Werner W. Schwarzhans; Rodrigo L. Moura; José Anchieta C. C. Nunes; Michael M. Mincarone (Journal of Fish Biology, 2021)
In this study, a new species of Pseudogilbia Møller, Schwarzhans & Nielsen 2004 is described based on two male specimens (40–44 mm L S ) from shallow reefs of Bahia, Brazil. Pseudogilbia australis sp. nov. is distinguished from its only congener, Pseudogilbia sanblasensis Møller, Schwarzhans & Nielsen 2004 from Caribbean Panama, by having: two lower preopercular pores ( vs . one); dorsal‐fin rays 65–67 ( vs . 69); anal‐fin rays 51–53 ( vs . 56); pectoral‐fin rays 18 ( vs . 20); caudal vertebrae 27–28 ( vs . 30); pectoral‐fin length 15.0%–15.9% L S ( vs . 14.3); pelvic‐fin length 13.5% L S ( vs . 16.4) and a different morphology of the male copulatory organ. Pseudogilbia australis sp. nov. is the only dinematichthyid so far recorded in the South Atlantic. An updated diagnosis for the genus is also provided.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Temperature and productivity distinctly affect the species richness of ectothermic and endothermic multitrophic guilds along a tropical elevational gradient - Chaim J. Lasmar; Clarissa Rosa; Antônio C. M. Queiroz; Cássio A. Nunes; Mayara M. G. Imata; Guilherme P. Alves; Gabriela B. Nascimento; Ludson N. Ázara; Letícia Vieira; Júlio Louzada; Rodrigo M. Feitosa; Antonio D. Brescovit; et al. (Oecologia, 2021)

Transcriptional Profiles Reveal Deregulation of Lipid Metabolism and Inflammatory Pathways in Neurons Exposed to Palmitic Acid - M. Flores-León; N. Alcaraz; M. Pérez-Domínguez; K. Torres-Arciga; R. Rebollar-Vega; I. A. De la Rosa-Velázquez; C. Arriaga-Canon; L. A. Herrera; Clorinda Arias; Rodrigo González-Barrios (Molecular Neurobiology, 2021)

Genome profiling of fluoroquinolone-resistant uropathogenic Escherichia coli isolates from Brazil - Patrick da Silva; Bruna C. Lustri; Ivana Giovannetti Castilho; Adriano Martison Ferreira; Rodrigo T. Hernandes; Mark A. Schembri; Cristiano G. Moreira (Brazilian Journal of Microbiology, 2021)

Bioactivity and composition of lipophilic metabolites extracted from Antarctic macroalgae - Lucas M. Berneira; Ivandra I. de Santi; Caroline C. da Silva; Dalila Venzke; Pio Colepicolo; Rodrigo de A. Vaucher; Marco A. Z. dos Santos; Claudio M. P. de Pereira (Brazilian Journal of Microbiology, 2021)

Influence of niche and neutral processes on fish communities associated with changes in macrophyte rafts along the hydrological cycle - Lucena R. Virgilio; Werther Pereira Ramalho; João C. B. Silva; Monik Oliveira da Suçuarana; Rodrigo Souza Gomes; Lisandro J. S. Vieira (Biologia, 2021)

Differential exopolysaccharide production and composition by Herbaspirillum strains from diverse ecological environments - Valquíria D. C. Antunes; Daniela Freitag; Rodrigo V. Serrato (Archives of Microbiology, 2021)

Wood Volume of Eucalyptus Clones Established Under Different Spacings in the Brazilian Cerrado - Jéssica L André; Rodrigo de S Oliveira; Carlos R Sette; Acelino C Alfenas; Edival Ângelo V Zauza; Leandro de Siqueira; Evandro Novaes (Forest Science, 2021)
Eucalyptus plantations are expanding in Brazil to meet growing demands for wood-based products, such as pulp, paper, and bioenergy. New clones and silvicultural adjustments are needed with the advance of eucalypts to new regions within Brazil. This study’s objective was to evaluate the effect of variable spacing on the development of six Eucalyptus clones cultivated in the Cerrado region of Brazil. These clones were evaluated in a systematic design, with 23 spacing treatments and five biological replicates. Spacing per tree ranged from 1.20 m2 to 21 m2. At two, four, and six years after planting, diameter at breast height (DBH) and height of all trees were measured to estimate wood volume. Regression models were fitted for each trait (DBH, height, and wood volume) and showed that DBH growth was positively affected by spacing, especially at four and six years after planting (R2 > 0.58). Consequently, estimates of individual volume per tree also had a positive relationship with spacing. Total stand volume, on the other hand, was higher under densest spacings. The GG100 clone outperformed all other clones, with higher stand wood volume, especially under the densest spacings. The CCL55 clone is a promising genotype, especially under dense plantations.

Using Compounds Derived from the Glycerol Fermentation as a Carbon Source for Denitrification and Biological Phosphorus Removal - Maria E. S. Dias; Jéssica C. Lopes; Rodrigo B. Carneiro; Márcia H. R. Z. Damianovic; Eugenio Foresti (Water, Air, & Soil Pollution, 2021)

C(3)1-TAg in C57BL/6 J background as a model to study mammary tumor development - Isadora F. G. Sena; Beatriz G. S. Rocha; Caroline C. Picoli; Gabryella S. P. Santos; Alinne C. Costa; Bryan O. P. Gonçalves; Ana Paula V. Garcia; Maryam Soltani-asl; Leda M. C. Coimbra-Campos; Walison N. Silva; Pedro A. C. Costa; Mauro C. X. Pinto; et al. (Histochemistry and Cell Biology, 2021)

Environmental controls on holocene reef development along the eastern brazilian margin - Belinda Dechnik; Alex C. Bastos; Laura S. Vieira; Jody M. Webster; Stewart Fallon; Yusuke Yokoyama; Juan-Carlos Braga; Manuel A. Pereira; Luke Nothdurft; Kelsey Sanborn; Rodrigo L. Moura; Gilberto Amado-filho (Coral Reefs, 2021)

Identifying dominant environmental predictors of freshwater wetland methane fluxes across diurnal to seasonal time scales - Sara H. Knox; Sheel Bansal; Gavin McNicol; Karina Schafer; Cove Sturtevant; Masahito Ueyama; Alex C. Valach; Dennis Baldocchi; Kyle Delwiche; Ankur R. Desai; Eugenie Euskirchen; Jinxun Liu; et al. (Global Change Biology, 2021)
While wetlands are the largest natural source of methane (CH 4 ) to the atmosphere, they represent a large source of uncertainty in the global CH 4 budget due to the complex biogeochemical controls on CH 4 dynamics. Here we present, to our knowledge, the first multi‐site synthesis of how predictors of CH 4 fluxes (FCH4) in freshwater wetlands vary across wetland types at diel, multiday (synoptic), and seasonal time scales. We used several statistical approaches (correlation analysis, generalized additive modeling, mutual information, and random forests) in a wavelet‐based multi‐resolution framework to assess the importance of environmental predictors, nonlinearities and lags on FCH4 across 23 eddy covariance sites. Seasonally, soil and air temperature were dominant predictors of FCH4 at sites with smaller seasonal variation in water table depth (WTD). In contrast, WTD was the dominant predictor for wetlands with smaller variations in temperature (e.g., seasonal tropical/subtropical wetlands). Changes in seasonal FCH4 lagged fluctuations in WTD by ~17 ± 11 days, and lagged air and soil temperature by median values of 8 ± 16 and 5 ± 15 days, respectively. Temperature and WTD were also dominant predictors at the multiday scale. Atmospheric pressure (PA) was another important multiday scale predictor for peat‐dominated sites, with drops in PA coinciding with synchronous releases of CH 4 . At the diel scale, synchronous relationships with latent heat flux and vapor pressure deficit suggest that physical processes controlling evaporation and boundary layer mixing exert similar controls on CH 4 volatilization, and suggest the influence of pressurized ventilation in aerenchymatous vegetation. In addition, 1‐ to 4‐h lagged relationships with ecosystem photosynthesis indicate recent carbon substrates, such as root exudates, may also control FCH4. By addressing issues of scale, asynchrony, and nonlinearity, this work improves understanding of the predictors and timing of wetland FCH4 that can inform future studies and models, and help constrain wetland CH 4 emissions.

Introgression of the sesquiterpene biosynthesis from Solanum habrochaites to cultivated tomato offers insights into trichome morphology and arthropod resistance - Rodrigo Therezan; Ruy Kortbeek; Eloisa Vendemiatti; Saioa Legarrea; Severino M. de Alencar; Robert C. Schuurink; Petra Bleeker; Lázaro E. P. Peres (Planta, 2021)
Main conclusion Cultivated tomatoes harboring the plastid-derived sesquiterpenes from S. habrochaites have altered type-VI trichome morphology and unveil additional genetic components necessary for piercing-sucking pest resistance. Abstract Arthropod resistance in the tomato wild relative Solanum habrochaites LA1777 is linked to specific sesquiterpene biosynthesis. The Sesquiterpene synthase 2 ( SsT2 ) gene cluster on LA1777 chromosome 8 controls plastid-derived sesquiterpene synthesis. The main genes at SsT2 are Z-prenyltransferase (zFPS) and Santalene and Bergamotene Synthase ( SBS ), which produce α-santalene, β-bergamotene, and α-bergamotene in LA1777 round-shaped type-VI glandular trichomes. Cultivated tomatoes have mushroom-shaped type-VI trichomes with much smaller glands that contain low levels of monoterpenes and cytosolic-derived sesquiterpenes, not presenting the same pest resistance as in LA1777. We successfully transferred zFPS and SBS from LA1777 to cultivated tomato (cv. Micro-Tom, MT) by a backcrossing approach. The trichomes of the MT- Sst2 introgressed line produced high levels of the plastid-derived sesquiterpenes. The type-VI trichome internal storage-cavity size increased in MT- Sst2 , probably as an effect of the increased amount of sesquiterpenes, although it was not enough to mimic the round-shaped LA1777 trichomes. The presence of high amounts of plastid-derived sesquiterpenes was also not sufficient to confer resistance to various tomato piercing-sucking pests, indicating that the effect of the sesquiterpenes found in the wild S. habrochaites can be insect specific. Our results provide for a better understanding of the morphology of S. habrochaites type-VI trichomes and paves the way to obtain insect-resistant tomatoes.

Greenhouse gas emissions (CO2 and CH4) and inorganic carbon behavior in an urban highly polluted tropical coastal lagoon (SE, Brazil) - Luiz C. Cotovicz; Renato P. Ribeiro; Carolina Ramos Régis; Marcelo Bernardes; Rodrigo Sobrinho; Luciana Oliveira Vidal; Daniel Tremmel; Bastiaan A. Knoppers; Gwenaël Abril (Environmental Science and Pollution Research, 2021)

Ruthenium (II)/allopurinol complex inhibits breast cancer progression via multiple targets - Ingrid O. Travassos; Francyelli Mello-Andrade; Raíssa P. Caldeira; Wanessa C. Pires; Paula F. F. da Silva; Rodrigo S. Correa; Tamara Teixeira; Alisson Martins-Oliveira; Alzir. A. Batista; Elisângela P. de Silveira-Lacerda (JBIC Journal of Biological Inorganic Chemistry, 2021)

Deep learning for lithological classification of carbonate rock micro-CT images - Carlos E. M. dos Anjos; Manuel R. V. Avila; Adna G. P. Vasconcelos; Aurea M. Pereira Neta; Lizianne C. Medeiros; Alexandre G. Evsukoff; Rodrigo Surmas; Luiz Landau (Computational Geosciences, 2021)

Electrochemically Assisted Soil Washing for the Remediation of Non-polar and Volatile Pollutants - M. Muñoz-Morales; C. Sáez; P. Cañizares; M. A. Rodrigo (Current Pollution Reports, 2021)

Simple and safe approach for molecular identification of the endangered species Epinephelus itajara - Yrlano Oliveira; Roberto Alencar; Yrlan Oliveira; Rodrigo A. Torres; Iracilda Sampaio; Marcelo Vallinoto; Gláucia C. Silva-Oliveira (Conservation Genetics Resources, 2021)

Glycine is a competitive antagonist of the TNF receptor mediating the expression of inflammatory cytokines in 3T3-L1 adipocytes - Rodrigo Romero-Nava; Francisco J. Alarcón-Aguilar; Abraham Giacoman-Martínez; Gerardo Blancas-Flores; Karla A. Aguayo-Cerón; Martha A. Ballinas-Verdugo; Fausto Sánchez-Muñoz; Fengyang Huang; Santiago Villafaña-Rauda; Julio C. Almanza-Pérez (Inflammation Research, 2021)

Correction to: Transdermal Permeation of Caffeine Aided by Ionic Liquids: Potential for Enhanced Treatment of Cellulites - Audrey N. Hernandes; Rodrigo Boscariol; Victor M. Balcão; Marta M. D. C. Vila (AAPS PharmSciTech, 2021)

Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Naira Fernanda Zanchett Schneider; Danusa Menegaz; Andre Luiz Andreotti Dagostin; Lara Persich; Sayonarah C. Rocha; Ana Carolina Pacheco Ramos; Vanessa Faria Cortes; Carlos Frederico Leite Fontes; Rodrigo Maia de Pádua; Jennifer Munkert; Wolfgang Kreis; Fernão Castro Braga; et al. (Molecular and Cellular Biochemistry, 2021)

Synergy of Aspergillus niger and Components in Biofertilizer Composites Increases the Availability of Nutrients to Plants - Rodrigo Klaic; Gelton G. F. Guimarães; Amanda S. Giroto; Alberto C. C. Bernardi; Teresa C. Zangirolami; Caue Ribeiro; Cristiane S. Farinas (Current Microbiology, 2021)

Differences in circulating corticosterone levels associated with elevation of breeding sites in Rufous-collared Sparrows Zonotrichia capensis - Yanina Poblete; Victor Gutierrez; Paulina L. González-Gómez; John C. Wingfield; Rodrigo A. Vásquez (Journal of Ornithology, 2021)
To facilitate breeding and any energetically costly activity, individuals of the same species can substantially vary their circulating corticosterone (CORT) levels to cope with local environmental conditions at different elevations. We compared baseline and the stress-induced plasma CORT levels during the parental care stage between free-living Rufous-collared Sparrows ( Zonotrichia capensis ) that breed at high (~ 2500 m) and low (~ 500 m) elevations in central Chile. We found that baseline CORT levels at different elevations were similar and that stress-induced levels were significantly lower in birds breeding at high elevation; however, we detected no sexual dimorphism in CORT levels related to elevation. We found that larger individuals had higher stress-induced CORT levels at low elevation regardless of sex. Our results show that environmental conditions at high elevation seem to be not severe enough to promote more elevated baseline CORT levels. However, breeding Rufous-collared Sparrow must still deal with both shorter breeding seasons and increased exposure to unpredictable events. Thus, a reduced stress response during the parental care stage would be more favorable for supporting breeding activities at high elevations. Future studies should focus on describing the life-history traits of these populations and the effects that other stressors, such as predation pressure and food availability, may have on the adrenocortical response in these environments to evaluate the consequences for survival and reproductive success. This information is important for enhancing our understanding of the ecological and evolutionary mechanisms that modulate variation in the adrenocortical response among populations of the same species.

Transdermal Permeation of Caffeine Aided by Ionic Liquids: Potential for Enhanced Treatment of Cellulite - Audrey N. Hernandes; Rodrigo Boscariol; Victor M. Balcão; Marta M. D. C. Vila (AAPS PharmSciTech, 2021)

Age and growth of franciscana, Pontoporia blainvillei , and Guiana, Sotalia guianensis , dolphins from southeastern Brazil - Valéria R. M. Conversani; Débora F. Silva; Rodrigo A. Barbosa; Aleta A. Hohn; Marcos C. de O. Santos (Marine Mammal Science, 2021)

Neonatal Serotonin Depletion Induces Hyperactivity and Anxiolytic-like Sex-Dependent Effects in Adult Rats - Verónica Trujillo; Evandro Valentim-Lima; Rodrigo Mencalha; Quézia S. R. Carbalan; Raoni C. Dos-Santos; Viviane Felintro; Carlos E. N. Girardi; Rodrigo Rorato; Danilo Lustrino; Luis C. Reis; André S. Mecawi (Molecular Neurobiology, 2021)

Multi-mixture herbicides provide management strategies in the control of the aquatic weed Heteranthera reniformis - Úrsula R. Zaidan; Larissa M. Motta; Wendel M. de Souza; Rodrigo M. Faria; Maria C. G. Paiva; Kassio F. Mendes; Francisco Cláudio L. de Freitas (Journal of Crop Science and Biotechnology, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Leaf hydraulic properties are decoupled from leaf area across coffee species - Rafael Mauri; Amanda A. Cardoso; Mariela M. da Silva; Leonardo A. Oliveira; Rodrigo T. Avila; Samuel C. V. Martins; Fábio M. DaMatta (Trees, 2020)

Ocotea mellosilvae (Lauraceae): a new species from the Espinhaço Range, Brazil - Caroline C. Assunção-Silva; Rodrigo A. Magalhães; Leandro C. S. Assis (Kew Bulletin, 2020)

Correction to: Sedimentary records of Marine Isotopic Stage 3 (MIS 3) in southern Brazil - Sergio R. Dillenburg; Eduardo G. Barboza; Maria Luiza C. C. Rosa; Felipe Caron; Rodrigo Cancelli; Cristiane B. Santos-Fischer; Renato P. Lopes; Matias do Nascimento Ritter (Geo-Marine Letters, 2020)

Sedimentary records of Marine Isotopic Stage 3 (MIS 3) in southern Brazil - Sergio R. Dillenburg; Eduardo G. Barboza; Maria Luiza C. C. Rosa; Felipe Caron; Rodrigo Cancelli; Cristiane B. Santos-Fischer; Renato P. Lopes; Matias do Nascimento Ritter (Geo-Marine Letters, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for dissipation of elements to the environment - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma; David Sanjuan-Delmás; Tobias C. Kampmann; Glenn Bark; Ainara Garcia Uriarte; Pierre Menger; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose The methods for assessing the impact of using abiotic resources in life cycle assessment (LCA) have always been heavily debated. One of the main reasons for this is the lack of a common understanding of the problem related to resource use. This article reports the results of an effort to reach such common understanding between different stakeholder groups and the LCA community. For this, a top-down approach was applied. Methods To guide the process, a four-level top-down framework was used to (1) demarcate the problem that needs to be assessed, (2) translate this into a modeling concept, (3) derive mathematical equations and fill these with data necessary to calculate the characterization factors, and (4) align the system boundaries and assumptions that are made in the life cycle impact assessment (LCIA) model and the life cycle inventory (LCI) model. Results We started from the following definition of the problem of using resources: the decrease of accessibility on a global level of primary and/or secondary elements over the very long term or short term due to the net result of compromising actions. The system model distinguishes accessible and inaccessible stocks in both the environment and the technosphere. Human actions can compromise the accessible stock through environmental dissipation, technosphere hibernation, and occupation in use or through exploration. As a basis for impact assessment , we propose two parameters: the global change in accessible stock as a net result of the compromising actions and the global amount of the accessible stock. We propose three impact categories for the use of elements: environmental dissipation, technosphere hibernation, and occupation in use, with associated characterization equations for two different time horizons. Finally, preliminary characterization factors are derived and applied in a simple illustrative case study for environmental dissipation. Conclusions Due to data constraints, at this moment, only characterization factors for “dissipation to the environment” over a very-long-term time horizon could be elaborated. The case study shows that the calculation of impact scores might be hampered by insufficient LCI data. Most presently available LCI databases are far from complete in registering the flows necessary to assess the impacts on the accessibility of elements. While applying the framework, various choices are made that could plausibly be made differently. We invite our peers to also use this top-down framework when challenging our choices and elaborate that into a consistent set of choices and assumptions when developing LCIA methods.

Progression of heart failure is attenuated by antioxidant therapy with N-acetylcysteine in myocardial infarcted female rats - César R. M. Costa; Fernando A. C. Seara; Milena S. Peixoto; Isalira P. Ramos; Raiana A. Q. Barbosa; Adriana B. Carvalho; Rodrigo S. Fortunato; Anderson L. B. Silveira; Emerson L. Olivares (Molecular Biology Reports, 2020)

Guanosine Neuroprotection of Presynaptic Mitochondrial Calcium Homeostasis in a Mouse Study with Amyloid-β Oligomers - Jussemara Souza da Silva; Yasmine Nonose; Francieli Rohden; Pâmela C. Lukasewicz Ferreira; Fernanda Urruth Fontella; Andréia Rocha; Andressa Wigner Brochier; Rodrigo Vieira Apel; Thais Martins de Lima; Bianca Seminotti; Alexandre Umpierrez Amaral; Antonio Galina; et al. (Molecular Neurobiology, 2020)

The use of anthropogenic debris as nesting material by the greater thornbird, an inland–wetland-associated bird of South America - Martín C. M. Blettler; Lucía Gauna; Alex Andréault; Elie Abrial; Rodrigo E. Lorenzón; Luis A. Espinola; Karl M. Wantzen (Environmental Science and Pollution Research, 2020)

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Changes in Phytoplankton Communities Along the Northern Antarctic Peninsula: Causes, Impacts and Research Priorities - Afonso Ferreira; Raul R. Costa; Tiago S. Dotto; Rodrigo Kerr; Virginia M. Tavano; Ana C. Brito; Vanda Brotas; Eduardo R. Secchi; Carlos R. B. Mendes (Frontiers in Marine Science, 2020)

Temporal and individual variation in the diet of the Neotropical otter, Lontra longicaudis (Olfers, 1818) (Carnivora, Mustelidae), as revealed by stable isotope analysis of vibrissae - Thayara S. Carrasco; Renan C. de Lima; Silvina Botta; Rodrigo Machado; Paulo C. Simões-Lopes; Paulo H. Ott; Eduardo R. Secchi (Mammalian Biology, 2020)

Reproductive parameters of franciscana dolphins ( Pontoporia blainvillei ) of Southeastern Brazil - Débora F. Silva; Rodrigo A. Barbosa; Valéria R. M. Conversani; Silvina Botta; Aleta A. Hohn; Marcos C. de O. Santos (Marine Mammal Science, 2020)
Reproductive parameters of 168 franciscana dolphins, Pontoporia blainvillei (73 females and 95 males) incidentally caught ( n = 163) or stranded ( n = 5) between 2005 and 2016 in southeastern Brazil are presented. Ovarian macroscopic analysis revealed 55 immature (75.3%) and 18 mature (24.7%) females. Annual pregnancy rate was estimated to be 0.36, with a calving interval of 2.8 years. Testicular histology revealed 66 immature (69.5%) and 29 mature (30.5%) males. Males with combined testis weight above 4 g were mature, and 1‐year‐old mature males and a 2‐year‐old pregnant female are reported for the first time for the species. Reproductive seasonality does not seem to occur in the study area. Mean age and length at sexual maturation were estimated to be at 2.7 years and 128.5 cm for females, and 2.7 years and 114.0 cm for males. These estimates are lower than most of the estimates for this species. These results add novel and valuable information on the reproductive patterns of this endangered species, threatened by high levels of mortality in gill net fisheries. The information presented here represents an important effort to obtain more reliable parameter estimates for the studied area, needed for a better assessment of its current conservation status.

Amerotyphlops brongersmianus (Vanzolini, 1976) (Typhlopidae, Serpentes) as a model for scolecophidian ontogenetic shifts of heart topography and relative size - Angele Martins; Laryssa Silva; Rodrigo C. Gonzalez (Zoomorphology, 2020)

Restricted connectivity and population genetic fragility in a globally endangered Hammerhead Shark - Danillo Pinhal; Rodrigo R. Domingues; Christine C. Bruels; Bruno L. S. Ferrette; Otto B. F. Gadig; Mahmood S. Shivji; Cesar Martins (Reviews in Fish Biology and Fisheries, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Chemical composition of essential oils from different parts of Protium heptaphyllum (Aubl.) Marchand and their in vitro antibacterial activity - Rodrigo S. C. Cabral; Cassia C. F. Alves; Hellen R. F. Batista; Wendel C. Sousa; Isabela S. Abrahão; Antônio E. M. Crotti; Mariana B. Santiago; Carlos H. G. Martins; Mayker L. D. Miranda (Natural Product Research, 2020)

Ion Pair Strategy in Solid Lipid Nanoparticles: a Targeted Approach to Improve Epidermal Targeting with Controlled Adapalene Release, Resulting Reduced Skin Irritation - Linna B. O. Rodrigues; Flávia A. Lima; Camila P. B. Alves; Elisângela Martins-Santos; Marta M. G. Aguiar; Cleida A. Oliveira; Rodrigo L. Oréfice; Lucas A. M. Ferreira; Gisele A. C. Goulart (Pharmaceutical Research, 2020)

Genome-wide identification of multifunctional laccase gene family in Eucalyptus grandis: potential targets for lignin engineering and stress tolerance - Mariana L. C. Arcuri; Larissa C. Fialho; Alessandra Vasconcellos Nunes-Laitz; Maria Cecília P. Fuchs-Ferraz; Ivan Rodrigo Wolf; Guilherme Targino Valente; Celso L. Marino; Ivan G. Maia (Trees, 2020)

Genetic structure and gene flow among populations of Encholirium magalhaesii, a rocky grassland fields bromeliad - Rodrigo C. Gonçalves-Oliveira; Tina Wöhrmann; Kurt Weising; Maria das Graças L. Wanderley; Ana M. Benko-Iseppon (Brazilian Journal of Botany, 2020)

Effect of temperature on growth, gene expression, and aflatoxin production by Aspergillus nomius isolated from Brazil nuts - Nathália B. S. Yunes; Rodrigo C. Oliveira; Tatiana A. Reis; Arianne C. Baquião; Liliana O. Rocha; Benedito Correa (Mycotoxin Research, 2020)

Ecological response to altered rainfall differs across the Neotropics - Diane S. Srivastava; Régis Céréghino; M. Kurtis Trzcinski; A. Andrew M. MacDonald; Nicholas A. C. Marino; Dimaris Acosta Mercado; Céline Leroy; Bruno Corbara; Gustavo Q. Romero; Vinicius F. Farjalla; Ignacio M. Barberis; Olivier Dézerald; et al. (Ecology, 2020)
There is growing recognition that ecosystems may be more impacted by infrequent extreme climatic events than by changes in mean climatic conditions. This has led to calls for experiments that explore the sensitivity of ecosystems over broad ranges of climatic parameter space. However, because such response surface experiments have so far been limited in geographic and biological scope, it is not clear if differences between studies reflect geographic location or the ecosystem component considered. In this study, we manipulated rainfall entering tank bromeliads in seven sites across the Neotropics, and characterized the response of the aquatic ecosystem in terms of invertebrate functional composition, biological stocks (total invertebrate biomass, bacterial density) and ecosystem fluxes (decomposition, carbon, nitrogen). Of these response types, invertebrate functional composition was the most sensitive, even though, in some sites, the species pool had a high proportion of drought‐tolerant families. Total invertebrate biomass was universally insensitive to rainfall change because of statistical averaging of divergent responses between functional groups. The response of invertebrate functional composition to rain differed between geographical locations because (1) the effect of rainfall on bromeliad hydrology differed between sites, and invertebrates directly experience hydrology not rainfall and (2) the taxonomic composition of some functional groups differed between sites, and families differed in their response to bromeliad hydrology. These findings suggest that it will be difficult to establish thresholds of “safe ecosystem functioning” when ecosystem components differ in their sensitivity to climatic variables, and such thresholds may not be broadly applicable over geographic space. In particular, ecological forecast horizons for climate change may be spatially restricted in systems where habitat properties mediate climatic impacts, and those, like the tropics, with high spatial turnover in species composition.

Metacommunity organization in an intermittent river in Brazil: the importance of riverine networks for regional biodiversity - Carlos A. S. Rodrigues-Filho; Ronaldo C. Gurgel-Lourenço; Eliêta A. Ramos; José L. C. Novaes; Danielle S. Garcez; Rodrigo S. Costa; Jorge I. Sánchez-Botero (Aquatic Ecology, 2020)

Assessing the growth and climate sensitivity of secondary forests in highly deforested Amazonian landscapes - Fernando Elias; Joice Ferreira; Gareth D. Lennox; Erika Berenguer; Socorro Ferreira; Gustavo Schwartz; Lia de Oliveira Melo; Denilson N. Reis Júnior; Rodrigo O. Nascimento; Fabrício Nascimento Ferreira; Fernando Espirito‐Santo; Charlotte C. Smith; et al. (Ecology, 2020)
Tropical forests hold 30% of Earth’s terrestrial carbon and at least 60% of its terrestrial biodiversity, but forest loss and degradation are jeopardizing these ecosystems. Although the regrowth of secondary forests has the potential to offset some of the losses of carbon and biodiversity, it remains unclear if secondary regeneration will be affected by climate changes such as higher temperatures and more frequent extreme droughts. We used a data set of 10 repeated forest inventories spanning two decades (1999–2017) to investigate carbon and tree species recovery and how climate and landscape context influence carbon dynamics in an older secondary forest located in one of the oldest post‐Columbian agricultural frontiers in the Brazilian Amazon. Carbon accumulation averaged 1.08 Mg·ha −1 ·yr −1 , and species richness was effectively constant over the studied period. Moreover, we provide evidence that secondary forests are vulnerable to drought stress: Carbon balance and growth rates were lower in drier periods. This contrasts with drought responses in primary forests, where changes in carbon dynamics are driven by increased stem mortality. These results highlight an important climate change–vegetation feedback, whereby the increasing dry‐season lengths being observed across parts of Amazonia may reduce the effectiveness of secondary forests in sequestering carbon and mitigating climate change. In addition, the current rate of forest regrowth in this region was low compared with previous pan‐tropical and Amazonian assessments—our secondary forests reached just 41.1% of the average carbon and 56% of the tree diversity in the nearest primary forests—suggesting that these areas are unlikely to return to their original levels on politically meaningful time scales.

Starch accumulation does not lead to feedback photosynthetic downregulation in girdled coffee branches under varying source-to-sink ratios - Rodrigo T. Avila; Samuel C. V. Martins; Lílian M. V. P. Sanglard; Martielly S. dos Santos; Paulo E. Menezes-Silva; Kelly C. Detman; Matheus L. Sanglard; Amanda A. Cardoso; Leandro E. Morais; Camilo E. Vital; Wagner L. Araújo; Adriano Nunes-Nesi; et al. (Trees, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Determination of fluorescein and brominated fluoresceins in the color additive D&C Orange No. 5 and its lakes using high-performance liquid chromatography - India C. James; Rodrigo Lazo-Portugal; Marianita Perez-Gonzalez; Adrian Weisz (Food Additives & Contaminants: Part A, 2019)

How do coffee trees deal with severe natural droughts? An analysis of hydraulic, diffusive and biochemical components at the leaf level - Samuel C. V. Martins; Matheus L. Sanglard; Leandro E. Morais; Paulo E. Menezes-Silva; Rafael Mauri; Rodrigo T. Avila; Camilo E. Vital; Amanda A. Cardoso; Fábio M. DaMatta (Trees, 2019)

Cranial Geometric Morphometric Analysis of the Genus Tapirus (Mammalia, Perissodactyla) - Larissa C. C. S. Dumbá; Rodrigo Parisi Dutra; Mario A. Cozzuol (Journal of Mammalian Evolution, 2019)

Estimates of groundwater depletion under extreme drought in the Brazilian semi-arid region using GRACE satellite data: application for a small-scale aquifer - Maurício D. Melati; Ayan S. Fleischmann; Fernando M. Fan; Rodrigo C. D. Paiva; Gustavo B. Athayde (Hydrogeology Journal, 2019)

Correction to: Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)
Unfortunately, Fig. 3 was incorrectly published in the original publication. The correct version of Fig. 3 is updated here.

Temperature dependence of parasitic infection and gut bacterial communities in bumble bees - Evan C. Palmer‐Young; Lyna Ngor; Rodrigo Burciaga Nevarez; Jason A. Rothman; Thomas R. Raffel; Quinn S. McFrederick (Environmental Microbiology, 2019)
Summary High temperatures (e.g., fever) and gut microbiota can both influence host resistance to infection. However, effects of temperature‐driven changes in gut microbiota on resistance to parasites remain unexplored. We examined the temperature dependence of infection and gut bacterial communities in bumble bees infected with the trypanosomatid parasite Crithidia bombi . Infection intensity decreased by over 80% between 21 and 37°C. Temperatures of peak infection were lower than predicted based on parasite growth in vitro , consistent with mismatches in thermal performance curves of hosts, parasites and gut symbionts. Gut bacterial community size and composition exhibited slight but significant, non‐linear, and taxon‐specific responses to temperature. Abundance of total gut bacteria and of Orbaceae, both negatively correlated with infection in previous studies, were positively correlated with infection here. Prevalence of the bee pathogen‐containing family Enterobacteriaceae declined with temperature, suggesting that high temperature may confer protection against diverse gut pathogens. Our results indicate that resistance to infection reflects not only the temperature dependence of host and parasite performance, but also temperature‐dependent activity of gut bacteria. The thermal ecology of gut parasite‐symbiont interactions may be broadly relevant to infectious disease, both in ectothermic organisms that inhabit changing climates, and in endotherms that exhibit fever‐based immunity.

The public and private benefit of an impure public good determines the sensitivity of bacteria to population collapse in a snowdrift game - Robert P. Smith; Aimee Doiron; Rodrigo Muzquiz; Marla C. Fortoul; Meghan Haas; Tom Abraham; Rebecca J. Quinn; Ivana Barraza; Khadija Chowdhury; Louis R. Nemzer (Environmental Microbiology, 2019)
Summary When cooperation is critical for survival, cheating can lead to population collapse. One mechanism of cooperation that permits the coexistence of cooperators and cheaters is an impure public good, whose public benefits are shared, but with a private benefit retained by the cooperator. It has yet to be determined how the contributions of the public and private benefit affect population survival. Using simulations and experiments with β‐lactamase‐expressing bacteria, we found that for a given amount of public and private benefit, the population was most sensitive to collapse when initiated from an intermediate fraction of cooperators due to the near‐concurrent collapse of the cooperator and cheater populations. We found that increasing the ratio of public to private benefit increased sensitivity to collapse. A low ratio allowed cooperators to survive on their private benefit after the public benefit could not rescue the cheaters. A high ratio allowed the cheaters to survive to high concentrations of ampicillin due to the high public benefit. However, small increases in ampicillin caused a rapid decline in the entire population as the private benefit was insufficient to allow self‐rescue of the cooperators. Our findings have implications in the persistence of populations that rely on cooperation for survival.

Colletotrichum acutatum M11 can suppress the defence response in strawberry plants - Rodrigo H. Tomas-Grau; Pia Di Peto; Nadia R. Chalfoun; Carlos F. Grellet-Bournonville; Gustavo G. Martos; Mario Debes; Marta E. Arias; Juan C. Díaz-Ricci (Planta, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Rodrigo H. S. Tanabe; Melissa A. Vieira; Noelle A. B. Mariano; Regiane C. B. Dias; Rafael Ventin da Silva; Caroline M. Castro; Luis F. dos Santos; Carlos H. Camargo; Ricardo S. Yamatogi; Vera L. M. Rall; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2019)

Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)

Global agricultural productivity is threatened by increasing pollinator dependence without a parallel increase in crop diversification - Marcelo A. Aizen; Sebastián Aguiar; Jacobus C. Biesmeijer; Lucas A. Garibaldi; David W. Inouye; Chuleui Jung; Dino J. Martins; Rodrigo Medel; Carolina L. Morales; Hien Ngo; Anton Pauw; Robert J. Paxton; et al. (Global Change Biology, 2019)
The global increase in the proportion of land cultivated with pollinator‐dependent crops implies increased reliance on pollination services. Yet agricultural practices themselves can profoundly affect pollinator supply and pollination. Extensive monocultures are associated with a limited pollinator supply and reduced pollination, whereas agricultural diversification can enhance both. Therefore, areas where agricultural diversity has increased, or at least been maintained, may better sustain high and more stable productivity of pollinator‐dependent crops. Given that >80% of all crops depend, to varying extents, on insect pollination, a global increase in agricultural pollinator dependence over recent decades might have led to a concomitant increase in agricultural diversification. We evaluated whether an increase in the area of pollinator‐dependent crops has indeed been associated with an increase in agricultural diversity, measured here as crop diversity, at the global, regional, and country scales for the period 1961–2016. Globally, results show a relatively weak and decelerating rise in agricultural diversity over time that was largely decoupled from the strong and continually increasing trend in agricultural dependency on pollinators. At regional and country levels, there was no consistent relationship between temporal changes in pollinator dependence and crop diversification. Instead, our results show heterogeneous responses in which increasing pollinator dependence for some countries and regions has been associated with either an increase or a decrease in agricultural diversity. Particularly worrisome is a rapid expansion of pollinator‐dependent oilseed crops in several countries of the Americas and Asia that has resulted in a decrease in agricultural diversity. In these regions, reliance on pollinators is increasing, yet agricultural practices that undermine pollination services are expanding. Our analysis has thereby identified world regions of particular concern where environmentally damaging practices associated with large‐scale, industrial agriculture threaten key ecosystem services that underlie productivity, in addition to other benefits provided by biodiversity.

Corrigendum: Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia's Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

Individual field-collected glassy-winged sharpshooter vectors harbor sequences from two Xylella fastidiosa subspecies - Drake C. Stenger; Lindsey P. Burbank; Rodrigo Krugner; Mark S. Sisterson (European Journal of Plant Pathology, 2019)

Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Carolina D. Teixeira; Rodrigo L. L. Leitão; Felipe V. Ribeiro; Fernando C. Moraes; Leonardo M. Neves; Alex C. Bastos; Guilherme H. Pereira-Filho; Milton Kampel; Paulo S. Salomon; João A. Sá; Ludmilla N. Falsarella; Michelle Amario; et al. (Coral Reefs, 2019)

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Spatial Variability in the Resistance and Resilience of Giant Kelp in Southern and Baja California to a Multiyear Heatwave - Kyle C. Cavanaugh; Daniel C. Reed; Tom W. Bell; Max C. N. Castorani; Rodrigo Beas-Luna (Frontiers in Marine Science, 2019)

Selenium downregulates auxin and ethylene biosynthesis in rice seedlings to modify primary metabolism and root architecture - Rafael S. P. Malheiros; Lucas C. Costa; Rodrigo T. Ávila; Thaline M. Pimenta; Lubia S. Teixeira; Fred A. L. Brito; Agustín Zsögön; Wagner L. Araújo; Dimas M. Ribeiro (Planta, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Potential of southern Latin-American coastal areas for stone pine (Pinus pinea L.) cropping - Verónica Loewe-Muñoz; Mónica Balzarini; Claudia Delard R.; Rodrigo del Rio M.; Andrea Álvarez C. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Isotopic niche of the Neotropical otter, Lontra longicaudis (Carnivora, Mustelidae), in different coastal aquatic systems in southern Brazil - Thayara S. Carrasco; Silvina Botta; Rodrigo Machado; Paulo C. Simões-Lopes; Oldemar Carvalho-Junior; Paulo H. Ott; Elton P. Colares; Eduardo R. Secchi (Hydrobiologia, 2019)

Long‐term temporal and spatial patterns in bioeroding sponge distribution at the Abrolhos Bank, Brazil, Southwestern Atlantic - Fernando Coreixas de Moraes; Fernanda Cervi; Cláudia S. Karez; Leonardo T. Salgado; Rodrigo L. Moura; Gabriella A. Leal; Alex C. Bastos; Gilberto M. Amado‐Filho (Marine Ecology, 2019)
Bioeroding sponges belong to the most dominant bioeroders, significantly contributing to the erosion of coral reefs. Some species are tolerant or even benefit from environmental conditions such as ocean warming, acidification, and eutrophication. In consequence, increases in sponge bioerosion have been observed on some coral reefs over the last decades. The Abrolhos Bank is the largest coral reef system in the South Atlantic. It has been affected by sedimentation, eutrophication, overfishing, and climate change, mainly affecting coastal reefs, and at lesser intensity outer ones as well. This study aimed to describe spatial and temporal patterns in bioeroding sponge distribution in carbonate substrates in the Abrolhos Bank. Photo‐quadrats were used to compare bioeroding sponge abundance between two shallow reefs: a coastal, Pedra de Leste (PL), and an outer reef, Parcel dos Abrolhos (PAB). Each individual was delimitated over the substrate by determining the sponge surface through a line connecting the outermost papillae. The study was conducted over 6 years in 2008–2009 and 2013–2016. Four species of bioeroding sponges were identified: Cliona carteri Ridley, 1881, C. delitrix Pang, 1973, C. cf. schmidtii Ridley, 1881, and Siphonodictyon coralliphagum Rützler, 1971. The distribution and abundance of species varied between the inner and outer reefs and across the years, and displayed certain selectivity for the calcareous substrates recorded. Crustose coralline algae (CCA) were the main substrate excavated by the most abundant bioeroding species, C. carteri , and represented 70% of the substrate types occupied by this sponge (CCA, coral overgrown by CCA and plain coral). The highest abundance of bioeroding sponges observed in photo‐quadrats was 21.3 individuals/m 2 at the outer reefs (PAB) in 2014. The abundances or areal extents of bioeroding sponges were up to 10 times greater on the outer reefs than on the coastal ones, where sedimentation is higher and more strongly influenced by siliciclastic material. Moreover, a higher herbivorous fish biomass has been reported on outer reefs which could also influence the higher abundance of bioeroding sponges in outer reefs. During the study period of 6 years, an increase in bioeroding sponge abundance was observed at the outer reefs (PAB), with the sea surface temperature increase. As CCA have an important role in reefal cementation and carbonate production in the Abrolhos reefs, a bioerosion impact might be expected, in particular, on the outer reefs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

The rostrodorsal periaqueductal gray influences both innate fear responses and acquisition of fear memory in animals exposed to a live predator - Rodrigo de Andrade Rufino; Sandra Regina Mota-Ortiz; Miguel Antonio Xavier De Lima; Marcus Vinicius C. Baldo; Newton Sabino Canteras (Brain Structure and Function, 2019)

Multiscale climate change impacts on plant diversity in the Atacama Desert - Francisca P. Díaz; Claudio Latorre; Gabriela Carrasco‐Puga; Jamie R. Wood; Janet M. Wilmshurst; Daniela C. Soto; Theresa L. Cole; Rodrigo A. Gutiérrez (Global Change Biology, 2019)
Comprehending ecological dynamics requires not only knowledge of modern communities but also detailed reconstructions of ecosystem history. Ancient DNA (aDNA) metabarcoding allows biodiversity responses to major climatic change to be explored at different spatial and temporal scales. We extracted aDNA preserved in fossil rodent middens to reconstruct late Quaternary vegetation dynamics in the hyperarid Atacama Desert. By comparing our paleo‐informed millennial record with contemporary observations of interannual variations in diversity, we show local plant communities behave differentially at different timescales. In the interannual (years to decades) time frame, only annual herbaceous expand and contract their distributional ranges (emerging from persistent seed banks) in response to precipitation, whereas perennials distribution appears to be extraordinarily resilient. In contrast, at longer timescales (thousands of years) many perennial species were displaced up to 1,000 m downslope during pluvial events. Given ongoing and future natural and anthropogenically induced climate change, our results not only provide baselines for vegetation in the Atacama Desert, but also help to inform how these and other high mountain plant communities may respond to fluctuations of climate in the future.

A dark side of cleaning symbiosis: manned submersible observations - Rodrigo L. Moura; Fernando C. Moraes; Gilberto M. Amado-Filho; Leonardo M. Neves; Alexandre D. Kassuga; Danielle D’Agostini; Alex C. Bastos (Marine Biodiversity, 2019)

Morphology and sedimentology of the shelf-upper slope transition in the Abrolhos continental shelf (east Brazilian margin) - Danielle P. D’Agostini; Alex C. Bastos; Gilberto M. Amado-Filho; Claudia G. Vilela; Thaís C. S. Oliveira; Jody M. Webster; Rodrigo L. Moura (Geo-Marine Letters, 2019)

Ingestion of plastic fragments by the Guri sea catfish Genidens genidens (Cuvier, 1829) in a subtropical coastal estuarine system - David V. Dantas; Cristian I. R. Ribeiro; Catarina de C. A. Frischknecht; Rodrigo Machado; Eduardo G. G. Farias (Environmental Science and Pollution Research, 2019)

Lack of contact with feline immunodeficiency virus in the Iberian lynx - Guillermo López; Teresa del Rey-Wamba; Brian Willet; Leonardo Fernández-Pena; Marcos López-Parra; Clara I. León; Rodrigo C. Serra; Irene Zorrilla; Regina Hofmann-Lehmann; Miguel A. Simón; Marina L. Meli (European Journal of Wildlife Research, 2019)

Amber, beads and social interaction in the Late Prehistory of the Iberian Peninsula: an update - Carlos P. Odriozola; Ana C. Sousa; Rui Mataloto; Rui Boaventura; Marco Andrade; Rodrigo Villalobos García; José Ángel Garrido-Cordero; Eugenio Rodríguez; José María Martínez-Blanes; Miguel Ángel Avilés; Joan Daura; Montserrat Sanz; et al. (Archaeological and Anthropological Sciences, 2019)

Seasonal modulation of the adrenocortical stress responses in Chilean populations of Zonotrichia capensis - Aaron D. Clark; Elizabeth A. Addis; Rodrigo A. Vásquez; John C. Wingfield (Journal of Ornithology, 2019)

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Beneficial Effects of the Calcium Channel Blocker CTK 01512-2 in a Mouse Model of Multiple Sclerosis - Rodrigo B. M. Silva; Samuel Greggio; Gianina T. Venturin; Jaderson C. da Costa; Marcus V. Gomez; Maria M. Campos (Molecular Neurobiology, 2018)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Analysis of potential contamination factors in musculoskeletal tissues - Guilherme G. Naves; André F. Silva; Uri Antebi; Priscila C. Cristovam; Emerson K. Honda; Rodrigo P. Guimarães (Cell and Tissue Banking, 2018)

Role of Phosphatidylinositol-3 Kinase Pathway in NMDA Preconditioning: Different Mechanisms for Seizures and Hippocampal Neuronal Degeneration Induced by Quinolinic Acid - Leandra C. Constantino; Luisa B. Binder; Samuel Vandresen-Filho; Giordano G. Viola; Fabiana K. Ludka; Mark W. Lopes; Rodrigo B. Leal; Carla I. Tasca (Neurotoxicity Research, 2018)

Mineralization of humic acids (HAs) by a solar photo-Fenton reaction mediated by ferrioxalate complexes: commercial HAs vs extracted from leachates - Ana P. F. Santos; Bianca M. Souza; Tânia F. C. V. Silva; Rodrigo P. Cavalcante; Silvio C. Oliveira; Amílcar Machulek; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2018)

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Dynamics of spontaneous activity in random networks with multiple neuron subtypes and synaptic noise - Rodrigo F. O. Pena; Michael A. Zaks; Antonio C. Roque (Journal of Computational Neuroscience, 2018)

Identification of compounds from Palicourea rigida leaves with topical anti-inflammatory potential using experimental models - Rafael P. Pinheiro; Muiara A. Moraes; Bruna C. S. Santos; Rodrigo L. Fabri; Glauciemar Del-Vechio-Vieira; Célia H. Yamamoto; Ana Lúcia S. M. Araújo; Aílson L. A. Araújo; Orlando V. Sousa (Inflammopharmacology, 2018)

The mapping of storm surge-prone areas and characterizing surge-producing cyclones in Leyte Gulf, Philippines - Socorro Margarita T. Rodrigo; Cesar L. Villanoy; Jeric C. Briones; Princess Hope T. Bilgera; Olivia C. Cabrera; Gemma Teresa T. Narisma (Natural Hazards, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Rainfall and land management effects on erosion and soil properties in traditional Brazilian tobacco plantations - Valdemir Antoneli; Hélio H. Lenatorvicz; João A. Bednarz; Manuel Pulido-Fernández; Eric C. Brevik; Artemi Cerdà; Jesús Rodrigo-Comino (Hydrological Sciences Journal, 2018)

Purification of arsenic-contaminated water with K-jarosite filters - Rodrigo C. Hott; Luiz F. O. Maia; Mayra S. Santos; Márcia C. Faria; Luiz C. A. Oliveira; Márcio C. Pereira; Cleide A. Bomfeti; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2018)

Assessment of temporal and spatial water quality in international Gomishan Lagoon, Iran, using multivariate analysis - Nabee Basatnia; Seyed Abbas Hossein; Jesús Rodrigo-Comino; Yones Khaledian; Eric C. Brevik; Jacqueline Aitkenhead-Peterson; Usha Natesan (Environmental Monitoring and Assessment, 2018)

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

Spatial and temporal dynamics of the abundance of crustose calcareous algae on the southernmost coral reefs of the western Atlantic (Abrolhos Bank, Brazil) - Gilberto M. Amado-Filho; Ricardo G. Bahia; Rodrigo Mariath; Michel B. Jesionek; Rodrigo Leão Moura; Alex C. Bastos; Guilherme Henrique Pereira-Filho; Ronaldo Bastos Francini-Filho (Algae, 2018)

Meta‐analysis approach to the effects of live prey on the growth of Octopus vulgaris paralarvae under culture conditions - Diego Garrido; M. Virginia Martín; Covadonga Rodríguez; José Iglesias; Juan C. Navarro; Alicia Estévez; Francisco Hontoria; Mikel Becerro; Juan J. Otero; Josu Pérez; Inmaculada Varó; Diana B. Reis; et al. (Reviews in Aquaculture, 2018)
The common octopus ( Octopus vulgaris , Cuvier 1797) is a promising species for aquaculture diversification, but the massive mortality during the first life stage is the main bottleneck for its commercial production. The aim of the present study was to compare the effects of different live preys ( Artemia and crustacean zoeae) and/or Artemia enrichment protocols in the paralarval growth by using a meta‐analysis approach. A total of 26 independent assays were used, including data from the bibliography and from experiments carried out by our group. Three comparisons were established: (i) crustacean zoeae vs. Artemia , (ii) different crustacean zoeae species and (iii) Artemia enriched with marine lecithin (rich in polar lipids‐ PL and docosahexaenoic acid‐ DHA ) vs. previously used Artemia enrichments. The meta‐analysis approach allowed a quantitative review of independent studies with reliable conclusions, avoiding the subjectivity inherent to classical reviews. The outputs provided statistical confirmation of the better suitability of crustacean zoeae with respect to Artemia . However, not all crustacean species showed the same results, given that the high variability on Grapsus zoeae hampered finding significant differences with respect to the control treatment ( Artemia ). Nutrient composition and biometry of the different types of prey are discussed as possible causes of the differences arising from the meta‐analysis. Finally, the present results suggest that marine lecithin has a beneficial effect on paralarval growth with respect to previously used enrichments, which could be related to the increase in DHA and PL in Artemia , given the essential role of these lipid components in octopus paralarval physiology.

Correction to: Somatic embryogenesis of a seedless sweet orange (Citrus sinensis (L.) Osbeck) - Jean C. Cardoso; Maisa Curtolo; Rodrigo R. Latado; Adriana P. Martinelli (In Vitro Cellular & Developmental Biology - Plant, 2018)

Networking our science to characterize the state, vulnerabilities, and management opportunities of soil organic matter - Jennifer W. Harden; Gustaf Hugelius; Anders Ahlström; Joseph C. Blankinship; Ben Bond‐Lamberty; Corey R. Lawrence; Julie Loisel; Avni Malhotra; Robert B. Jackson; Stephen Ogle; Claire Phillips; Rebecca Ryals; et al. (Global Change Biology, 2018)
Soil organic matter ( SOM ) supports the Earth's ability to sustain terrestrial ecosystems, provide food and fiber, and retains the largest pool of actively cycling carbon. Over 75% of the soil organic carbon ( SOC ) in the top meter of soil is directly affected by human land use. Large land areas have lost SOC as a result of land use practices, yet there are compensatory opportunities to enhance productivity and SOC storage in degraded lands through improved management practices. Large areas with and without intentional management are also being subjected to rapid changes in climate, making many SOC stocks vulnerable to losses by decomposition or disturbance. In order to quantify potential SOC losses or sequestration at field, regional, and global scales, measurements for detecting changes in SOC are needed. Such measurements and soil‐management best practices should be based on well established and emerging scientific understanding of processes of C stabilization and destabilization over various timescales, soil types, and spatial scales. As newly engaged members of the International Soil Carbon Network, we have identified gaps in data, modeling, and communication that underscore the need for an open, shared network to frame and guide the study of SOM and SOC and their management for sustained production and climate regulation.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Assessment of sexual maturity in captive Amazonian manatees ( Trichechus inunguis ) - Rodrigo S. Amaral; Vera M. F. Da Silva; Stella Maris lazzarini; José Anselmo D'affonsêca Neto; Daniella Ribeiro; Fernando C. W. Rosas (Marine Mammal Science, 2018)

Neotropical savanna ants show a reversed latitudinal gradient of species richness, with climatic drivers reflecting the forest origin of the fauna - Heraldo L. Vasconcelos; Jonas B. Maravalhas; Rodrigo M. Feitosa; Renata Pacheco; Karen C. Neves; Alan N. Andersen (Journal of Biogeography, 2018)
Aim To evaluate the extent to which ant species richness in Neotropical savannas varies with macrogeographic variables, and to identify the potential climatic drivers of such variation. Location The Cerrado savanna biome of central Brazil, in a region spanning ca. 20° of latitude and 18°of longitude. Methods Standardized sampling of the arboreal and ground‐dwelling faunas was performed in 29 well‐preserved savanna sites using pitfall traps. Species were classified according to their habitat affinities: open‐savanna specialists, forest‐associated species or habitat generalists. We used generalized linear models to evaluate the importance of geographic (latitude, longitude and elevation) and climatic (mean temperature and three metrics of rainfall) variables as predictors of species richness. Results The total number of species recorded at each site varied more than twofold (from 59 to 144), and latitude was the best geographic correlate of overall species richness. However, contrary to the expected pattern, more species were found at higher than lower latitudes. This reversed latitudinal pattern of diversity occurred for both the arboreal and ground‐dwelling faunas, and for the habitat generalists and forest specialists. The savanna specialists showed a mid‐latitudinal peak in diversity. Overall, there was a significant positive association between rainfall and species richness, but the strength of this relationship varied with ant habitat affinity. Main conclusions The Cerrado ant fauna shows a reverse latitudinal gradient in species diversity, and this can be explained by increasing rainfall during the warmest months of the year (and therefore in plant productivity) with increasing latitude. The sensitivity of Cerrado ant diversity to declining rainfall contrasts with the high resilience to aridity of the Australian savanna ant fauna, and this reflects the contrasting evolutionary histories of these faunas. Our findings highlight the importance of historical processes as drivers of intercontinental contrasts in macroecological patterns.

Somatic embryogenesis of a seedless sweet orange (Citrus sinensis (L.) Osbeck) - Jean C. Cardoso; Maisa Curtolo; Rodrigo R. Latado; Adriana P. Martinelli (In Vitro Cellular & Developmental Biology - Plant, 2017)

Erratum to: Availability of fertiliser sulphate and elemental sulphur to canola in two consecutive crops - Fien Degryse; Babasola Ajiboye; Roslyn Baird; Rodrigo C. da Silva; Mike J. McLaughlin (Plant and Soil, 2017)

Quercetin Exerts Differential Neuroprotective Effects Against H2O2 and Aβ Aggregates in Hippocampal Neurons: the Role of Mitochondria - Juan A. Godoy; Carolina B. Lindsay; Rodrigo A. Quintanilla; Francisco J. Carvajal; Waldo Cerpa; Nibaldo C. Inestrosa (Molecular Neurobiology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Physical Exercise Attenuates Experimental Autoimmune Encephalomyelitis by Inhibiting Peripheral Immune Response and Blood-Brain Barrier Disruption - Priscila S. Souza; Elaine D. Gonçalves; Giulia S. Pedroso; Hemelin R. Farias; Stella C. Junqueira; Rodrigo Marcon; Talita Tuon; Maíra Cola; Paulo C. L. Silveira; Adair R. Santos; João B. Calixto; Cláudio T. Souza; et al. (Molecular Neurobiology, 2017)

Investigations into, and development of, a lyophilized and formulated recombinant human factor IX produced from CHO cells - Aline G. Almeida; Rodrigo C. V. Pinto; C. Mark Smales; Leda R. Castilho (Biotechnology Letters, 2017)

Assessment of agri-spillways as a soil erosion protection measure in Mediterranean sloping vineyards - Jesús Rodrigo-Comino; Stefan Wirtz; Eric C. Brevik; José D. Ruiz-Sinoga; Johannes B. Ries (Journal of Mountain Science, 2017)

Association between sleep quality and pain in the cervical region and scapular waist in adolescent athletes - Muana Hiandra Pereira dos Passos; Hítalo A. Silva; Ana C. R. Pitangui; Valéria M. A. Oliveira; Gabriel Cordeiro Gomes; Rodrigo C. Araújo (Sleep and Biological Rhythms, 2017)

Cytotoxic effects of the cardenolide convallatoxin and its Na,K-ATPase regulation - Naira Fernanda Zanchett Schneider; Izabella Thais Silva; Lara Persich; Annelise de Carvalho; Sayonarah C. Rocha; Lucas Marostica; Ana Carolina Pacheco Ramos; Alex G. Taranto; Rodrigo M. Pádua; Wolfgang Kreis; Leandro A. Barbosa; Fernão C. Braga; et al. (Molecular and Cellular Biochemistry, 2017)

Modeling abundance, growth, and health of the solitary coral Scolymia wellsi (Mussidae) in turbid SW Atlantic coral reefs - Ericka O. C. Coni; Camilo M. Ferreira; Pedro M. Meirelles; Rafael Menezes; Erika F. C. Santana; Ana Paula B. Moreira; Gilberto M. Amado-Filho; Beatrice P. Ferreira; Guilherme H. Pereira-Filho; Fabiano L. Thompson; Rodrigo L. Moura; Ronaldo B. Francini-Filho (Marine Biology, 2017)

Investigating essential and toxic elements in Antarctic macroalgae using a green analytical method - Rochele S. Picoloto; Rodrigo M. Pereira; Vanize C. Costa; Carla A. Hartwig; Claudio M. P. Pereira; Pio Colepicolo; Fabio A. Duarte; Marcia F. Mesko (Journal of Applied Phycology, 2017)

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

No evidence of transmission of grapevine leafroll-associated viruses by phylloxera (Daktulosphaira vitifoliae) - C. M. Wistrom; G. K. Blaisdell; L. R. Wunderlich; M. Botton; Rodrigo P. P. Almeida; K. M. Daane (European Journal of Plant Pathology, 2017)

Synthesis, antimicrobial activity and cytotoxic investigation of novel trifluoromethylated tetrazolo[1,5-a]pyrimidines - Elisandra Scapin; Clarissa P. Frizzo; Leticia V. Rodrigues; Geórgia C. Zimmer; Rodrigo A. Vaucher; Michelle R. Sagrillo; Janice L. Giongo; Carlos A. M. Afonso; Patrícia Rijo; Nilo Zanatta; Helio G. Bonacorso; Marcos A. P. Martins (Medicinal Chemistry Research, 2017)

Mutations in chromatin regulators functionally link Cornelia de Lange syndrome and clinically overlapping phenotypes - Ilaria Parenti; María E. Teresa-Rodrigo; Jelena Pozojevic; Sara Ruiz Gil; Ingrid Bader; Diana Braunholz; Nuria C. Bramswig; Cristina Gervasini; Lidia Larizza; Lutz Pfeiffer; Ferda Ozkinay; Feliciano Ramos; et al. (Human Genetics, 2017)

SNPs markers for the heavily overfished tambaqui Colossoma macropomum, a Neotropical fish, using next-generation sequencing-based de novo genotyping - José Gregorio Martínez; Valéria Nogueira Machado; Susana J. Caballero-Gaitán; Maria da C. Freitas Santos; Rodrigo Maciel Alencar; Maria Doris Escobar L.; Tomas Hrbek; Izeni Pires Farias (Conservation Genetics Resources, 2017)

Partitioning controls on Amazon forest photosynthesis between environmental and biotic factors at hourly to interannual timescales - Jin Wu; Kaiyu Guan; Matthew Hayek; Natalia Restrepo‐Coupe; Kenia T. Wiedemann; Xiangtao Xu; Richard Wehr; Bradley O. Christoffersen; Guofang Miao; Rodrigo da Silva; Alessandro C. de Araujo; Raimundo C. Oliviera; et al. (Global Change Biology, 2017)
Gross ecosystem productivity ( GEP ) in tropical forests varies both with the environment and with biotic changes in photosynthetic infrastructure, but our understanding of the relative effects of these factors across timescales is limited. Here, we used a statistical model to partition the variability of seven years of eddy covariance‐derived GEP in a central Amazon evergreen forest into two main causes: variation in environmental drivers (solar radiation, diffuse light fraction, and vapor pressure deficit) that interact with model parameters that govern photosynthesis and biotic variation in canopy photosynthetic light‐use efficiency associated with changes in the parameters themselves. Our fitted model was able to explain most of the variability in GEP at hourly ( R 2 = 0.77) to interannual ( R 2 = 0.80) timescales. At hourly timescales, we found that 75% of observed GEP variability could be attributed to environmental variability. When aggregating GEP to the longer timescales (daily, monthly, and yearly), however, environmental variation explained progressively less GEP variability: At monthly timescales, it explained only 3%, much less than biotic variation in canopy photosynthetic light‐use efficiency, which accounted for 63%. These results challenge modeling approaches that assume GEP is primarily controlled by the environment at both short and long timescales. Our approach distinguishing biotic from environmental variability can help to resolve debates about environmental limitations to tropical forest photosynthesis. For example, we found that biotically regulated canopy photosynthetic light‐use efficiency (associated with leaf phenology) increased with sunlight during dry seasons (consistent with light but not water limitation of canopy development) but that realized GEP was nonetheless lower relative to its potential efficiency during dry than wet seasons (consistent with water limitation of photosynthesis in given assemblages of leaves). This work highlights the importance of accounting for differential regulation of GEP at different timescales and of identifying the underlying feedbacks and adaptive mechanisms.

Effects of dietary Gracilaria sp. and Alaria sp. supplementation on growth performance, metabolic rates and health in meagre (Argyrosomus regius) subjected to pathogen infection - Maria João Peixoto; Emílio Salas-Leitón; Francisca Brito; Luís Ferreira Pereira; Jon C. Svendsen; Teresa Baptista; Rui Pereira; Helena Abreu; Pedro Alexandre Reis; José Fernando Magalhães Gonçalves; Rodrigo Otávio de Almeida Ozório (Journal of Applied Phycology, 2017)

Estimation of genetic parameters for longevity considering the cow’s age at last calving - Sabrina L. Caetano; Guilherme J. M. Rosa; Rodrigo P. Savegnago; Salvador B. Ramos; Priscila A. Bernardes; Luiz A. F. Bezerra; Raysildo B. Lôbo; Claudia C. P. de Paz; Danísio Prado Munari (Journal of Applied Genetics, 2017)

Metals Content in Herbal Supplements - Michelle Vieira Barrella; Otavio Arruda Heringer; Priscylla Maria Martins Cardoso; Elisangela Flavia Pimentel; Rodrigo Scherer; Dominik Lenz; Denise C. Endringer (Biological Trace Element Research, 2017)

Dissolution rate and agronomic effectiveness of struvite fertilizers – effect of soil pH, granulation and base excess - Fien Degryse; Roslyn Baird; Rodrigo C. da Silva; Mike J. McLaughlin (Plant and Soil, 2017)

Central Nervous System and Vertebrae Development in Horses: a Chronological Study with Differential Temporal Expression of Nestin and GFAP - Nathia N. Rigoglio; Rodrigo S. N. Barreto; Phelipe O. Favaron; Júlio C. F. Jacob; Lawrence C. Smith; Melba O. Gastal; Eduardo L. Gastal; Maria Angélica Miglino (Journal of Molecular Neuroscience, 2017)

Mesophotic ecosystems of the unique South Atlantic atoll are composed by rhodolith beds and scattered consolidated reefs - Gilberto M. Amado-Filho; Rodrigo L. Moura; Alex C. Bastos; Ronaldo B. Francini-Filho; Guilherme H. Pereira-Filho; Ricardo G. Bahia; Fernando C. Moraes; Fabio S. Motta (Marine Biodiversity, 2016)

Life history parameters and feeding preference of the green lacewing Ceraeochrysa cubana fed with virus-free and potato leafroll virus-infected Myzus persicae - Rodrigo L. de Oliveira; Valéria F. Moscardini; Pablo C. Gontijo; Rafaella R. Sâmia; Rosangela C. Marucci; Flor Budia; Geraldo A. Carvalho (BioControl, 2016)

Development of two artificial neural network models to support the diagnosis of pulmonary tuberculosis in hospitalized patients in Rio de Janeiro, Brazil - Fábio S. Aguiar; Rodrigo C. Torres; João V. F. Pinto; Afrânio L. Kritski; José M. Seixas; Fernanda C. Q. Mello (Medical & Biological Engineering & Computing, 2016)

Adsorption of arsenic from water and its recovery as a highly active photocatalyst - Rodrigo C. Hott; Thaina G. Andrade; Mayra S. Santos; Anne C. F. Lima; Márcia C. S. Faria; Cleide A. Bomfeti; Fernando Barbosa; Luiz F. O. Maia; Luiz C. A. Oliveira; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2016)

Multitaxon activity profiling reveals differential microbial response to reduced seawater pH and oil pollution - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rodrigo Costa; Marina Ferreira; Ana R. M. Polónia; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Newton C. M. Gomes (Molecular Ecology, 2016)
There is growing concern that predicted changes to global ocean chemistry will interact with anthropogenic pollution to significantly alter marine microbial composition and function. However, knowledge of the compounding effects of climate change stressors and anthropogenic pollution is limited. Here, we used 16S and 18S rRNA ( cDNA )‐based activity profiling to investigate the differential responses of selected microbial taxa to ocean acidification and oil hydrocarbon contamination under controlled laboratory conditions. Our results revealed that a lower relative abundance of sulphate‐reducing bacteria ( Desulfosarcina / Desulfococcus clade) due to an adverse effect of seawater acidification and oil hydrocarbon contamination (reduced pH –oil treatment) may be coupled to changes in sediment archaeal communities. In particular, we observed a pronounced compositional shift and marked reduction in the prevalence of otherwise abundant operational taxonomic units ( OTU s) belonging to the archaeal Marine Benthic Group B and Marine Hydrothermal Vent Group ( MHVG ) in the reduced pH –oil treatment. Conversely, the abundance of several putative hydrocarbonoclastic fungal OTU s was higher in the reduced pH –oil treatment. Sediment hydrocarbon profiling, furthermore, revealed higher concentrations of several alkanes in the reduced pH –oil treatment, corroborating the functional implications of the structural changes to microbial community composition. Collectively, our results advance the understanding of the response of a complex microbial community to the interaction between reduced pH and anthropogenic pollution. In future acidified marine environments, oil hydrocarbon contamination may alter the typical mixotrophic and k‐/r‐strategist composition of surface sediment microbiomes towards a more heterotrophic state with lower doubling rates, thereby impairing the ability of the ecosystem to recover from acute oil contamination events.

Temporal Dissociation of Striatum and Prefrontal Cortex Uncouples Anhedonia and Defense Behaviors Relevant to Depression in 6-OHDA-Lesioned Rats - Filipe C. Matheus; Daniel Rial; Joana I. Real; Cristina Lemos; Reinaldo N. Takahashi; Leandro J. Bertoglio; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2016)

Gene methylation parallelisms between peripheral blood cells and oral mucosa samples in relation to overweight - Rodrigo San-Cristobal; Santiago Navas-Carretero; Fermín I. Milagro; J. Ignacio Riezu-Boj; Elizabeth Guruceaga; Carlos Celis-Morales; Katherine M. Livingstone; Lorraine Brennan; Julie A. Lovegrove; Hannelore Daniel; Wim H. Saris; Iwonna Traczyk; et al. (Journal of Physiology and Biochemistry, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

“Cytochrome c oxidase I DNA sequence of Camponotus ants with different nesting strategies is a tool for distinguishing between morphologically similar species” - Manuela O. F. Ramalho; Rodrigo M. Santos; Tae T. Fernandes; Maria Santina C. Morini; Odair C. Bueno (Genetica, 2016)

Nonthermal Inactivation of Cronobacter sakazakii in Infant Formula Milk: A Review - M. C. Pina-Pérez; D. Rodrigo; A. Martínez (Critical Reviews in Food Science and Nutrition, 2016)

Inhibition of cell proliferation, invasion and migration by the cardenolides digitoxigenin monodigitoxoside and convallatoxin in human lung cancer cell line - Naira F. Z. Schneider; Fabiana C. Geller; Lara Persich; Lucas L. Marostica; Rodrigo M. Pádua; Wolfgang Kreis; Fernão C. Braga; Cláudia M. O. Simões (Natural Product Research, 2016)

Diets supplemented with seaweed affect metabolic rate, innate immune, and antioxidant responses, but not individual growth rate in European seabass (Dicentrarchus labrax) - Maria J. Peixoto; Jon C. Svendsen; Hans Malte; Luis F. Pereira; Pedro Carvalho; Rui Pereira; José F. M. Gonçalves; Rodrigo O. A. Ozório (Journal of Applied Phycology, 2016)

Projections of climate change effects on discharge and inundation in the Amazon basin - Mino Viana Sorribas; Rodrigo C. D. Paiva; John M. Melack; Juan Martin Bravo; Charles Jones; Leila Carvalho; Edward Beighley; Bruce Forsberg; Marcos Heil Costa (Climatic Change, 2016)

Gap-junctional channel and hemichannel activity of two recently identified connexin 26 mutants associated with deafness - Viviana Dalamon; Mariana C. Fiori; Vania A. Figueroa; Carolina A. Oliva; Rodrigo del Rio; Wendy Gonzalez; Jonathan Canan; Ana B. Elgoyhen; Guillermo A. Altenberg; Mauricio A. Retamal (Pflügers Archiv - European Journal of Physiology, 2016)

Optimization of a combined electrocoagulation-electroflotation reactor - C. Jiménez; C. Sáez; P. Cañizares; M. A. Rodrigo (Environmental Science and Pollution Research, 2016)

Terrestrial carbon balance in a drier world: the effects of water availability in southwestern North America - Joel A. Biederman; Russell L. Scott; Michael L. Goulden; Rodrigo Vargas; Marcy E. Litvak; Thomas E. Kolb; Enrico A. Yepez; Walter C. Oechel; Peter D. Blanken; Tom W. Bell; Jaime Garatuza‐Payan; Gregory E. Maurer; et al. (Global Change Biology, 2016)
Global modeling efforts indicate semiarid regions dominate the increasing trend and interannual variation of net CO 2 exchange with the atmosphere, mainly driven by water availability. Many semiarid regions are expected to undergo climatic drying, but the impacts on net CO 2 exchange are poorly understood due to limited semiarid flux observations. Here we evaluated 121 site‐years of annual eddy covariance measurements of net and gross CO 2 exchange (photosynthesis and respiration), precipitation, and evapotranspiration ( ET ) in 21 semiarid North American ecosystems with an observed range of 100 – 1000 mm in annual precipitation and records of 4–9 years each. In addition to evaluating spatial relationships among CO 2 and water fluxes across sites, we separately quantified site‐level temporal relationships, representing sensitivity to interannual variation. Across the climatic and ecological gradient, photosynthesis showed a saturating spatial relationship to precipitation, whereas the photosynthesis– ET relationship was linear, suggesting ET was a better proxy for water available to drive CO 2 exchanges after hydrologic losses. Both photosynthesis and respiration showed similar site‐level sensitivity to interannual changes in ET among the 21 ecosystems. Furthermore, these temporal relationships were not different from the spatial relationships of long‐term mean CO 2 exchanges with climatic ET . Consequently, a hypothetical 100‐mm change in ET , whether short term or long term, was predicted to alter net ecosystem production ( NEP ) by 64 gC m −2 yr −1 . Most of the unexplained NEP variability was related to persistent, site‐specific function, suggesting prioritization of research on slow‐changing controls. Common temporal and spatial sensitivity to water availability increases our confidence that site‐level responses to interannual weather can be extrapolated for prediction of CO 2 exchanges over decadal and longer timescales relevant to societal response to climate change.

Effects of treatment with the anti-parasitic drug diminazene aceturate on antioxidant enzymes in rat liver and kidney - Matheus D. Baldissera; Ricardo A. Gonçalves; Michele R. Sagrillo; Thirssa H. Grando; Camila S. Ritter; Fabielly S. Grotto; Gerson F. Brum; Sônia C. A. da Luz; Sergio O. Silveira; Viviane P. Fausto; Aline A. Boligon; Rodrigo A. Vaucher; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

The Western South Atlantic Ocean in a High-CO2 World: Current Measurement Capabilities and Perspectives - Rodrigo Kerr; Letícia C. da Cunha; Ruy K. P. Kikuchi; Paulo A. Horta; Rosane G. Ito; Marius N. Müller; Iole B. M. Orselli; Jannine M. Lencina-Avila; Manoela R. de Orte; Laura Sordo; Bárbara R. Pinheiro; Frédéric K. Bonou; et al. (Environmental Management, 2016)

Landowner perceptions of the value of natural forest and natural grassland in a mosaic ecosystem in southern Brazil - Kirsten A. Henderson; Mateus Reis; Carolina C. Blanco; Valério D. Pillar; Rodrigo C. Printes; Chris T. Bauch; Madhur Anand (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Critical analysis of methods for the measurement of volatile fatty acids - Rodrigo Fernández; Richard M. Dinsdale; Alan J. Guwy; Giuliano C. Premier (Critical Reviews in Environmental Science and Technology, 2016)

Ocean acidification induces changes in algal palatability and herbivore feeding behavior and performance - Cristian Duarte; Jorge López; Samanta Benítez; Patricio H. Manríquez; Jorge M. Navarro; Cesar C. Bonta; Rodrigo Torres; Pedro Quijón (Oecologia, 2016)

In vitro cytotoxicity study of ent-kaurenoic acid derivatives against human breast carcinoma cell line - Marília R. Simão; Luiza J. Carneiro; Raquel A. dos Santos; Jairo K. Bastos; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio; Cassia S. Mizuno (Medicinal Chemistry Research, 2016)

Silencing of Gonad-Inhibiting Hormone Transcripts in Litopenaeus vannamei Females by use of the RNA Interference Technology - Rubens G. Feijó; André L. Braga; Carlos F. C. Lanes; Márcio A. Figueiredo; Luis A. Romano; Marta C. Klosterhoff; Luis E. M. Nery; Rodrigo Maggioni; Wilson Wasielesky; Luis F. Marins (Marine Biotechnology, 2016)

Shallow landslide susceptibility mapping using high-resolution topography for areas devastated by super typhoon Haiyan - Maricar L. Rabonza; Raquel P. Felix; Alfredo Mahar Francisco A. Lagmay; Rodrigo Narod C. Eco; Iris Jill G. Ortiz; Dakila T. Aquino (Landslides, 2016)

The impact of salinity on the symbiosis between Casuarina glauca Sieb. ex Spreng. and N2-fixing Frankia bacteria based on the analysis of Nitrogen and Carbon metabolism - Nuno Duro; Paula Batista-Santos; Mário da Costa; Rodrigo Maia; Isabel V. Castro; Margarida Ramos; José C. Ramalho; Katharina Pawlowski; Cristina Máguas; Ana Ribeiro-Barros (Plant and Soil, 2016)

Availability of fertiliser sulphate and elemental sulphur to canola in two consecutive crops - Fien Degryse; Babasola Ajiboye; Roslyn Baird; Rodrigo C. da Silva; Mike J. McLaughlin (Plant and Soil, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Wood density, but not leaf hydraulic architecture, is associated with drought tolerance in clones of Coffea canephora - Paulo E. Menezes-Silva; Paulo C. Cavatte; Samuel C. V. Martins; Josimar V. Reis; Lucas F. Pereira; Rodrigo T. Ávila; Andréa L. Almeida; Marília C. Ventrella; Fábio M. DaMatta (Trees, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

In vitro antifungal activity of silver nanoparticles against fluconazole-resistant Candida species - Jhon J. Artunduaga Bonilla; Daissy J. Paredes Guerrero; Clara I. Sánchez Suárez; Claudia C. Ortiz López; Rodrigo G. Torres Sáez (World Journal of Microbiology and Biotechnology, 2015)

Microbial and sponge loops modify fish production in phase‐shifting coral reefs - Cynthia B. Silveira; Arthur W. Silva‐Lima; Ronaldo B. Francini‐Filho; Jomar S.M. Marques; Marcelo G. Almeida; Cristiane C. Thompson; Carlos E. Rezende; Rodolfo Paranhos; Rodrigo L. Moura; Paulo S. Salomon; Fabiano L. Thompson (Environmental Microbiology, 2015)
Summary Shifts from coral to algae dominance of corals reefs have been correlated to fish biomass loss and increased microbial metabolism. Here we investigated reef benthic and planktonic primary production, benthic dissolved organic carbon ( DOC ) release and bacterial growth efficiency in the A brolhos B ank, S outh A tlantic. Benthic DOC release rates are higher while water column bacterial growth efficiency is lower at impacted reefs. A trophic model based on the benthic and planktonic primary production was able to predict the observed relative fish biomass in healthy reefs. In contrast, in impacted reefs, the observed omnivorous fish biomass is higher, while that of the herbivorous/coralivorous fish is lower than predicted by the primary production‐based model. Incorporating recycling of benthic‐derived carbon in the model through microbial and sponge loops explains the difference and predicts the relative fish biomass in both reef types. Increased benthic carbon release rates and bacterial carbon metabolism, but decreased bacterial growth efficiency could lead to carbon losses through respiration and account for the uncoupling of benthic and fish production in phase‐shifting reefs. Carbon recycling by microbial and sponge loops seems to promote an increase of small‐bodied fish productivity in phase‐shifting coral reefs.

Effects of cadmium metal on young gametophytes of Gelidium floridanum: metabolic and morphological changes - Carmen Simioni; Éder C. Schmidt; Ticiane Rover; Rodrigo dos Santos; Elisa P. Filipin; Debora T. Pereira; Giulia Burle Costa; Eva Regina Oliveira; Fungyi Chow; Fernanda Ramlov; Luciane Ouriques; Marcelo Maraschin; et al. (Protoplasma, 2015)

The effect of different concentrations of copper and lead on the morphology and physiology of Hypnea musciformis cultivated in vitro: a comparative analysis - Rodrigo W. Santos; Éder C. Schmidt; Izabela C. Vieira; Giulia B. Costa; Ticiane Rover; Carmen Simioni; José Bonomi Barufi; Carlos Henrique L. Soares; Zenilda L. Bouzon (Protoplasma, 2015)

Fe2+ substrate transport through ferritin protein cage ion channels influences enzyme activity and biomineralization - Rabindra K. Behera; Rodrigo Torres; Takehiko Tosha; Justin M. Bradley; Celia W. Goulding; Elizabeth C. Theil (JBIC Journal of Biological Inorganic Chemistry, 2015)

Cellular Changes Induced by Kinin B1 Receptor Deletion: Study of Endothelial Nitric Oxide Metabolism - Rodrigo A. Loiola; Tathiany C. Torres; Richardt G. Landgraf; João Bosco Pesquero; Liliam Fernandes (International Journal of Peptide Research and Therapeutics, 2015)

The Scent Glands of the Neotropical Harvestman Discocyrtus pectnifemur: Morphology, Behavior and Chemistry - Júlio M. G. Segovia; Marcos Ryotaro Hara; Guilherme Ferreira Pagoti; Miriam Sannomiya; Deborah Y. A. C. Santos; Rodrigo Hirata Willemart (Journal of Chemical Ecology, 2015)

Marker-trait association and epistasis for brown rust resistance in sugarcane - Fernanda R. C. Santos; Luciana R. Pinto; Luciana A. Carlini-Garcia; Rodrigo Gazaffi; Melina C. Mancini; Bruna S. Gonçalves; Cibele N. F. Medeiros; Dilermando Perecin; Antônio A. F. Garcia; Anete P. Souza; Maria I. Zucchi (Euphytica, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Early abstinence of crack-cocaine is effective to attenuate oxidative stress and to improve antioxidant defences - Aline Zaparte; Thiago W. Viola; Rodrigo Grassi-Oliveira; Maurilio da Silva Morrone; José C. Moreira; Moisés E. Bauer (Psychopharmacology, 2015)

Over-expression of muscle glycogen synthase in human diabetic nephropathy - Rodrigo Gatica; Romina Bertinat; Pamela Silva; Pamela Kairath; Felipe Slebe; Fabián Pardo; María J. Ramírez; Juan C. Slebe; José M. Campistol; Francisco Nualart; Carme Caelles; Alejandro J. Yáñez (Histochemistry and Cell Biology, 2015)

Microbial community diversity and physical–chemical features of the Southwestern Atlantic Ocean - Nelson Alves Junior; Pedro Milet Meirelles; Eidy de Oliveira Santos; Bas Dutilh; Genivaldo G. Z. Silva; Rodolfo Paranhos; Anderson S. Cabral; Carlos Rezende; Tetsuya Iida; Rodrigo L. de Moura; Ricardo Henrique Kruger; Renato C. Pereira; et al. (Archives of Microbiology, 2015)

D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Ruin Moaddel; David A. Luckenbaugh; Ying Xie; Alma Villaseñor; Nancy E. Brutsche; Rodrigo Machado-Vieira; Anuradha Ramamoorthy; Maria Paz Lorenzo; Antonia Garcia; Michel Bernier; Marc C. Torjman; Coral Barbas; et al. (Psychopharmacology, 2015)

Toxicological effects of copper oxide nanoparticles on the growth rate, photosynthetic pigment content, and cell morphology of the duckweed Landoltia punctata - Cristina Moreira Lalau; Rodrigo de Almeida Mohedano; Éder C. Schmidt; Zenilda L. Bouzon; Luciane C. Ouriques; Rodrigo W. dos Santos; Cristina H. da Costa; Denice S. Vicentini; William Gerson Matias (Protoplasma, 2015)

Azadirachtin-mediated reproductive response of the predatory pirate bug Blaptostethus pallescens - Daiane Celestino; Guilherme I. Braoios; Rodrigo S. Ramos; Lessando M. Gontijo; Raul Narciso C. Guedes (BioControl, 2014)

Methods, fluxes and sources of gas phase alkyl nitrates in the coastal air - Alin C. Dirtu; Anna J. Buczyńska; Ana F. L. Godoi; Rodrigo Favoreto; László Bencs; Sanja S. Potgieter-Vermaak; Ricardo H. M. Godoi; René Van Grieken; Luc Van Vaeck (Environmental Monitoring and Assessment, 2014)

Differential Effects of Fluoride During Osteoblasts Mineralization in C57BL/6J and C3H/HeJ Inbred Strains of Mice - Sandra S. Matsuda; Thelma L. Silva; Marília A. Buzalaf; Antonio C Rodrigues; Rodrigo Cardoso de Oliveira (Biological Trace Element Research, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

Primers for the amplification of the MHC IIβ chain exon 2 in the Atlantic goliath grouper (Epinephelus itajara) - Gláucia C. Silva-Oliveira; Anete B. C. Silva; Fabian Blanchard; Zélia Nunes; Rodrigo A. Torres; Iracilda Sampaio; Marcelo Vallinoto (Conservation Genetics Resources, 2014)

Geoacoustic character, sedimentology and chronology of a cross-shelf Holocene sediment deposit off Cabo Frio, Brazil (southwest Atlantic Ocean) - Ursula Mendoza; Arthur Ayres Neto; Rodrigo C. Abuchacra; Cátia Fernandes Barbosa; Alberto G. Figueiredo; Manoela C. Gomes; Andre L. Belem; Ramsés Capilla; Ana Luiza S. Albuquerque (Geo-Marine Letters, 2014)

High efficiencies in the electrochemical oxidation of an anthraquinonic dye with conductive-diamond anodes - José Mario Aquino; Romeu C. Rocha-Filho; Cristina Sáez; Pablo Cañizares; Manuel A. Rodrigo (Environmental Science and Pollution Research, 2014)

In vitro anther culture of sweet orange (Citrus sinensis L. Osbeck) genotypes and of a C. clementina × C. sinensis ‘Hamlin’ hybrid - Jean C. Cardoso; Adriana P. Martinelli; Maria Antonieta Germanà; Rodrigo R. Latado (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Temporal dynamics of prokaryotic communities in the marine sponge S arcotragus spinosulus - Cristiane C. P. Hardoim; Rodrigo Costa (Molecular Ecology, 2014)
In spite of their putative relevance to host functioning, in‐depth knowledge of sponge microbiome stability over time is scarce. This study tackles the temporal maintenance of bacterial and archaeal assemblages in the model host S arcotragus spinosulus along three successive years. Prokaryotic communities were profiled by polymerase chain reaction‐denaturing gradient gel electrophoresis ( PCR ‐ DGGE ) and 454‐pyrosequencing of S . spinosulus ‐derived 16 S rRNA gene amplicons. Prevailing bacterial phyla were A ctinobacteria , A cidobacteria , P roteobacteria , P oribacteria , PAUC 34f, C hloroflexi and B acteroidetes , with B acteroidetes , C hloroflexi and P oribacteria showing different abundances over the years. At the approximate species level (operational taxonomic units, OTU s, defined at 97% sequence similarity), no major changes in bacterial richness and composition were found through time. Nearly 50% of all detected bacterial symbionts (96 in 205 OTU s) were recovered from all sampling years, whereas a taxonomically equivalent community of less dominant bacteria characterized the transient sponge microbiota. Despite the evidence for temporal symbiont maintenance, an intriguing cumulative degree of variation between individuals was unravelled, with all the surveyed sponge specimens sharing only 27 bacterial OTU s. Archaeal communities were dominated by one single symbiont of the candidate genus N itrosopumilus ( T haumarchaeota ), known for its ability to aerobically oxidize ammonia to nitrite. Only few bacterial ammonia oxidizers consistently occurred in S . spinosulus across the years as documented by PCR ‐ DGGE fingerprinting. In conclusion, prokaryotic symbionts of S . spinosulus display a state of dynamic stability shaped by the interplay between the maintenance of dominant players and turnover of less prevalent community members, in time and across host individuals, with no apparent consequences to holobiont functioning.

Influence of tea tree oil (Melaleuca alternifolia) on the cattle tick Rhipicephalus microplus - Rafael Pazinato; Vanderlei Klauck; Andreia Volpato; Alexandre A. Tonin; Roberto C. Santos; Márcia E. de Souza; Rodrigo A. Vaucher; Renata Raffin; Patrícia Gomes; Candice C. Felippi; Lenita M. Stefani; Aleksandro S. Da Silva (Experimental and Applied Acarology, 2014)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Remarkably low genetic diversity and strong population structure in common bottlenose dolphins (Tursiops truncatus) from coastal waters of the Southwestern Atlantic Ocean - Pedro F. Fruet; Eduardo R. Secchi; Fábio Daura-Jorge; Els Vermeulen; Paulo A. C. Flores; Paulo César Simões-Lopes; Rodrigo Cézar Genoves; Paula Laporta; Juliana C. Di Tullio; Thales Renato O. Freitas; Luciano Dalla Rosa; Victor Hugo Valiati; et al. (Conservation Genetics, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

Rust disease of eucalypts, caused by P uccinia psidii , did not originate via host jump from guava in B razil - Rodrigo N. Graça; Amy L. Ross‐Davis; Ned B. Klopfenstein; Mee‐Sook Kim; Tobin L. Peever; Phil G. Cannon; Cristina P. Aun; Eduardo S. G. Mizubuti; Acelino C. Alfenas (Molecular Ecology, 2013)
The rust fungus, P uccinia psidii , is a devastating pathogen of introduced eucalypts ( E ucalyptus spp.) in Brazil where it was first observed in 1912. This pathogen is hypothesized to be endemic to S outh and C entral A merica and to have first infected eucalypts via a host jump from native guava ( P sidium guajava ). Ten microsatellite markers were used to genotype 148 P . psidii samples from eucalypts and guava plus five additional myrtaceous hosts across a wide geographic range of south‐eastern Brazil and Uruguay. Principal coordinates analysis, a B ayesian clustering analysis and a minimum‐spanning network revealed two major genetic clusters among the sampled isolates, one associated with guava and another associated with eucalypts and three additional hosts. M ultilocus genotypes infecting guava differed by multiple mutational steps at eight loci compared with those infecting eucalypts. Approximate B ayesian computation revealed that evolutionary scenarios involving a coalescence event between guava‐ and eucalypt‐associated pathogen populations within the past 1000 years are highly unlikely. None of the analyses supported the hypothesis that eucalypt‐infecting P . psidii in Brazil originated via host jump from guava following the introduction of eucalypts to Brazil approximately 185 years ago. The existence of host‐associated biotypes of P . psidii in Brazil indicates that this diversity must be considered when assessing the invasive threat posed by this pathogen to myrtaceous hosts worldwide.

Refugia in Patagonian fjords and the eastern Andes during the Last Glacial Maximum revealed by huemul ( H ippocamelus bisulcus ) phylogeographical patterns and genetic diversity - Juan C. Marín; Valeria Varas; Alejandro R. Vila; Rodrigo López; Pablo Orozco‐terWengel; Paulo Corti (Journal of Biogeography, 2013)
Aim Our aim was to determine the combined impacts of Pleistocene climatic oscillations and glacial periods with recognized biogeographical barriers on the evolutionary history of huemul deer ( H ippocamelus bisulcus ). Location Southern Chile and Argentina's Andean forest, and Patagonian fjords. Methods We examined the phylogeography of huemul using 772 bp of the mitochondrial DNA control region sequence from 275 samples (29 locations) collected throughout the distributional range of the species. We grouped samples into clusters based on Bayesian genetic and spatial structure analyses and reconstructed the species' phylogeographical and demographic history. Results We observed 63 haplotypes that grouped into three clusters (Central Chile, North Patagonia and South Patagonia). All but five haplotypes in North and South Patagonia were distributed locally. Bayesian skyline plots showed that population sizes remained fairly constant until an increase during and after the Last Glacial Maximum. Genetic diversity was generally low, except in three populations in the eastern Andes and on Wellington Island (Patagonian fjords). Main conclusions Our results suggest that the biogeographical separation of huemul into phylogeographical groups has been heavily influenced by Pleistocene glacial stages, and more recently by habitat fragmentation and isolation. This provides the first evidence that the region west of the Cordilleran ice field was a refugium for at least one species of large mammal during the Pleistocene in southern South America. These results have direct implications for the conservation and management of this endangered deer species.

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Chemical constituents of Machaerium hirtum Vell. (Fabaceae) leaves and branches and its anti-inflammatory activity evaluation - Marlene C. Ignoato; Rodrigo M. Fabrão; Ivânia T.A. Schuquel; Marcos F.P. Botelho; Geanderson Bannwart; Armando M. Pomini; Laura L.M. Arruda; Ciomar A. Bersani-Amado; Silvana M.O. Santin (Natural Product Research, 2013)

Blockade of cannabinoid receptors reduces inflammation, leukocyte accumulation and neovascularization in a model of sponge-induced inflammatory angiogenesis - Rodrigo Guabiraba; Remo C. Russo; Amanda M. Coelho; Mônica A. N. D. Ferreira; Gabriel A. O. Lopes; Ariane K. C. Gomes; Silvia P. Andrade; Luciola S. Barcelos; Mauro M. Teixeira (Inflammation Research, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Manganese-exposed developing rats display motor deficits and striatal oxidative stress that are reversed by Trolox - Fabiano M. Cordova; Aderbal S. Aguiar; Tanara V. Peres; Mark W. Lopes; Filipe M. Gonçalves; Daniela Z. Pedro; Samantha C. Lopes; Célso Pilati; Rui D. S. Prediger; Marcelo Farina; Keith M. Erikson; Michael Aschner; et al. (Archives of Toxicology, 2013)

Determination and confirmation of metronidazole, dimetridazole, ronidazole and their metabolites in bovine muscle by LC-MS/MS - Rodrigo H.M.M. Granja; Alfredo M.M. Nino; Karine V.G. Reche; Fabio M. Giannotti; Andreia C. de Lima; Amarylis C.B.A. Wanschel; Alessandro G. Salerno (Food Additives & Contaminants: Part A, 2013)

Plant-derived essential oils affecting settlement and oviposition of Bemisia tabaci (Genn.) biotype B on tomato - Edson L. L. Baldin; Antônio E. M. Crotti; Kamila A. L. Wakabayashi; José P. G. F. Silva; Gabriela P. Aguiar; Efrain S. Souza; Rodrigo C. S. Veneziani; Milton Groppo (Journal of Pest Science, 2013)

Absorption of 15NH3 volatilized from urea by Citrus trees - Rodrigo M. Boaretto; Dirceu Mattos; José A. Quaggio; Heitor Cantarella; Paulo C. O. Trivelin (Plant and Soil, 2013)

Changes in ultrastructure and cytochemistry of the agarophyte Gracilaria domingensis (Rhodophyta, Gracilariales) treated with cadmium - Rodrigo W. dos Santos; Éder C. Schmidt; Zenilda L. Bouzon (Protoplasma, 2013)

Effects of host plant and maternal feeding experience on population vital rates of a specialized leaf beetle - Rodrigo S. Rios; Maritza Cárdenas; Kely González; Mónica F. Cisternas; Patricia C. Guerra; Andrea P. Loayza; Ernesto Gianoli (Arthropod-Plant Interactions, 2013)

Electrochemical Degradation of the Reactive Red 141 Dye Using a Boron-Doped Diamond Anode - José Mario Aquino; Romeu C. Rocha-Filho; Manuel A. Rodrigo; Cristina Sáez; Pablo Cañizares (Water, Air, & Soil Pollution, 2013)

Disentangling the origins of branched tetraether lipids and crenarchaeol in the lower Amazon River: Implications for GDGT‐based proxies - Claudia Zell; Jung-Hyun Kim; Patricia Moreira-Turcq; Gwenaël Abril; Ellen C. Hopmans; Marie-Paule Bonnet; Rodrigo Lima Sobrinho; Jaap S. Sinninghe Damsté (Limnology and Oceanography, 2013)
To trace the origin of branched glycerol dialkyl glycerol tetraethers (brGDGTs), their distribution in soils and suspended particulate matter (SPM) of Amazonian rivers and floodplain lakes ( várzeas ) was studied. Differences in distribution between river SPM and surrounding (lowland) soils suggests an additional brGDGT source to eroded soils in the lowland drainage basin. Erosion of high Andean soils (above 2500 m in altitude) has no major influence because its brGDGT distribution differs substantially from that in river SPM. Furthermore, SPM in the Tapajós River, a tributary that does not derive from the Andes, has a virtually identical brGDGT distribution to that of the Amazon main stem. The higher proportion of phospholipid‐derived brGDGTs in river SPM compared to soils indicates that in situ production in the Amazon is an additional source for riverine brGDGTs. This affects the methylation and cyclization index of brGDGTs (MBT‐CBT), resulting in slightly lower MBT‐CBT‐derived temperatures and slightly higher CBT‐derived pH values, i.e., between the pH of the basin soil and that of the river. Since the difference between MBT‐CBT‐derived temperatures of Amazon River SPM and the surrounding soils is relatively small (2°C) compared to other aquatic systems (for lakes a difference of ∼ 10°C has been observed), it might still be possible to trace large climate changes in the Amazon basin with the MBT‐CBT using river fan cores. However, variations in in situ production of brGDGTs in the Amazon River over time and space have to be evaluated in the future. Likewise, in situ production may affect the application of the MBT‐CBT paleothermometer in other river systems. Our results also show that crenarchaeol is primarily produced in the Amazon River and that its varying production influences the branched vs. isoprenoid tetraether (BIT) index. This indicates that the BIT index not only represents the input of soil organic carbon to the river but is also affected by in situ production of brGDGTs and crenarchaeol.

Cognitive Deficits in Machado–Joseph Disease Correlate with Hypoperfusion of Visual System Areas - Pedro Braga-Neto; Lívia Almeida Dutra; José Luiz Pedroso; André C. Felício; Helena Alessi; Ruth F. Santos-Galduroz; Paulo Henrique F. Bertolucci; Mário Luiz V. Castiglioni; Rodrigo Affonseca Bressan; Griselda Esther Jara de Garrido; Orlando Graziani Povoas Barsottini; Andrea Jackowski (The Cerebellum, 2012)

Response of the agarophyte Gelidium floridanum after in vitro exposure to ultraviolet radiation B: changes in ultrastructure, pigments, and antioxidant systems - Éder C. Schmidt; Rodrigo W. dos Santos; Caroline de Faveri; Paulo A. Horta; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Marcelo Maraschin; Zenilda L. Bouzon (Journal of Applied Phycology, 2012)

Hidden genetic diversity and distinct evolutionarily significant units in an commercially important Neotropical apex predator, the catfish Pseudoplatystoma corruscans - Daniel C. Carvalho; Denise A. A. Oliveira; Luciano B. Beheregaray; Rodrigo A. Torres (Conservation Genetics, 2012)

Higher striatal dopamine transporter density in PTSD: an in vivo SPECT study with [99mTc]TRODAT-1 - Marcelo Q. Hoexter; Gustavo Fadel; André C. Felício; Mariana B. Calzavara; Ilza R. Batista; Marilia A. Reis; Ming C. Shih; Roger K. Pitman; Sérgio B. Andreoli; Marcelo F. Mello; Jair J. Mari; Rodrigo A. Bressan (Psychopharmacology, 2012)

Phylogenetic signal and variation of visceral pigmentation in eight anuran families - Diogo B. Provete; Lilian Franco‐Belussi; Lia R. De Souza Santos; Rodrigo Zieri; Rafaela M. Moresco; Itamar A. Martins; Silvio C. De Almeida; Classius De Oliveira (Zoologica Scripta, 2012)
Provete, D. B, Franco‐Belussi, L., de Souza Santos, L. R., Zieri, R., Moresco, R. M., Martins, I. A., de Almeida, S. C., & de Oliveira, C. (2012). Phylogenetic signal and variation of visceral pigmentation in eight anuran families. — Zoologica Scripta , 41 , 547‐556. Visceral pigmentation is found in several organs and structures of ectothermic animals, comprising the extracutaneous pigmentary system. Its function is not well defined, although it is known that melanin is produced and stored inside pigmented cells. Previous studies demonstrated that the distribution of visceral pigmentation is neither homogeneous among organs among anuran species. We described the diversity of visceral pigmentation in 12 organs/structures from 32 anuran species belonging to eight families in a phylogenetic context. We also determined in which node(s) of the phylogeny there is more variation in the pigmentation and whether this variation has phylogenetic signal. The visceral pigment cells in organs and structures of the abdominal cavity varied among genera. All species had pigmentation in the urogenital and cardiorespiratory systems, whereas the stomach lacks pigmentation in all species. We also found a phylogenetic signal for pigmentation in all organs and structures taken together, besides heart, testes, lumbar parietal peritoneum and lumbar nerve plexus when considered separately. Overall, considering all organs, the highest diversity of categories of pigmentation was found in the nodes corresponding to Cruciabatrachia and Athesphatanura. This study constitutes the first step towards understanding the evolution of visceral pigmentation in anurans.

Bioconversion of Iodoacetophenones by Marine Fungi - Lenilson C. Rocha; Rodrigo F. Luiz; Isac G. Rosset; Cristiano Raminelli; Mirna H. R. Seleghim; Lara Durães Sette; André L. M. Porto (Marine Biotechnology, 2012)

Influences of cadmium on fine structure and metabolism of Hypnea musciformis (Rhodophyta, Gigartinales) cultivated in vitro - Zenilda L. Bouzon; Eduardo C. Ferreira; Rodrigo dos Santos; Fernando Scherner; Paulo A. Horta; Marcelo Maraschin; Éder C. Schmidt (Protoplasma, 2012)

Electrochemical Degradation of a Real Pharmaceutical Effluent - Joaquín R. Domínguez; T. González; P. Palo; J. Sánchez-Martín; M. A. Rodrigo; C. Sáez (Water, Air, & Soil Pollution, 2012)

Contribution of phosphorus (32P) absorption and remobilization for citrus growth - Fernando C. Bachiega Zambrosi; Dirceu Mattos; Rodrigo M. Boaretto; José A. Quaggio; Takashi Muraoka; James P. Syvertsen (Plant and Soil, 2012)

Stereoselective Bioreduction of 1-(4-Methoxyphenyl)ethanone by Whole Cells of Marine-Derived Fungi - Lenilson C. Rocha; Hercules V. Ferreira; Rodrigo F. Luiz; Lara D. Sette; André L. M. Porto (Marine Biotechnology, 2012)

Quantitative trait loci associated with grain moisture at harvest for line per se and testcross performance in maize: a meta-analysis - Rodrigo G. Sala; Fernando H. Andrade; Julio C. Cerono (Euphytica, 2012)

Floral resource partitioning by ants and bees in a jambolan Syzygium jambolanum (Myrtaceae) agroforestry system in Brazilian Meridional Amazon - Wesley Dáttilo; Rodrigo L. Martins; Vera Uhde; Janaína C. Noronha; Fernando P. Florêncio; Thiago J. Izzo (Agroforestry Systems, 2012)

Alterations in architecture and metabolism induced by ultraviolet radiation-B in the carragenophyte Chondracanthus teedei (Rhodophyta, Gigartinales) - Éder C. Schmidt; Beatriz Pereira; Carime L. Mansur Pontes; Rodrigo dos Santos; Fernando Scherner; Paulo A. Horta; Roberta de Paula Martins; Alexandra Latini; Marcelo Maraschin; Zenilda L. Bouzon (Protoplasma, 2012)

Somatic embryogenesis from ovaries of sweet orange cv. Tobias - Jean C. Cardoso; Adriana P. Martinelli; Rodrigo R. Latado (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

The activity of leech motoneurons during motor patterns is regulated by intrinsic properties and synaptic inputs - C. Bernardo Perez-Etchegoyen; Rodrigo J. Alvarez; Mariano J. Rodriguez; Lidia Szczupak (Journal of Comparative Physiology A, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

Olfactory sensitivity to amino acids in the blackspot sea bream (Pagellus bogaraveo): a comparison between olfactory receptor recording techniques in seawater - Peter C. Hubbard; Eduardo N. Barata; Rodrigo O. A. Ozório; Luisa M. P. Valente; Adelino V. M. Canário (Journal of Comparative Physiology A, 2011)

A new race of Puccinia psidii defeats rust resistance in eucalypt - Rodrigo N. Graça; Cristina P. Aun; Lúcio M. S. Guimarães; Bruno V. A. Rodrigues; Edival A. V. Zauza; Acelino C. Alfenas (Australasian Plant Pathology, 2011)

GH overexpression causes muscle hypertrophy independent from local IGF-I in a zebrafish transgenic model - Rafael Y. Kuradomi; Márcio A. Figueiredo; Carlos F. C. Lanes; Carlos E. da Rosa; Daniela V. Almeida; Rodrigo Maggioni; Maeli D. P. Silva; Luis F. Marins (Transgenic Research, 2011)

Hypocretin 1/orexin A in the ventral tegmental area enhances dopamine responses to cocaine and promotes cocaine self-administration - Rodrigo A. España; James R. Melchior; David C. S. Roberts; Sara R. Jones (Psychopharmacology, 2011)

Transcriptional Profiles of Roots of Different Soybean Genotypes Subjected to Drought Stress - Renata Stolf-Moreira; Eliana G. M. Lemos; Lúcia Carareto-Alves; Jackson Marcondes; Selma S. Pereira; Amanda A. P. Rolla; Rodrigo M. Pereira; Norman Neumaier; Eliseu Binneck; Ricardo V. Abdelnoor; Maria C. N. de Oliveira; Francismar C. Marcelino; et al. (Plant Molecular Biology Reporter, 2011)

DTI-MR tractography of white matter damage in stroke patients with neglect - M. Urbanski; M. Thiebaut de Schotten; S. Rodrigo; C. Oppenheim; E. Touzé; J.-F. Méder; K. Moreau; C. Loeper-Jeny; B. Dubois; P. Bartolomeo (Experimental Brain Research, 2011)

Tolerance response to ammonia and nitrite in hatchlings paralarvae of Octopus vulgaris and its toxic effects on prey consumption rate and chromatophores activity - Paloma Feyjoo; Rodrigo Riera; Beatriz C. Felipe; Alí Skalli; Eduardo Almansa (Aquaculture International, 2011)

Analyzing GNSS data in precise point positioning software - Rodrigo F. Leandro; Marcelo C. Santos; Richard B. Langley (GPS Solutions, 2011)

Rapid response of a grassland ecosystem to an experimental manipulation of a keystone rodent and domestic livestock - Ana D. Davidson; Eduardo Ponce; David C. Lightfoot; Ed L. Fredrickson; James H. Brown; Juan Cruzado; Sandra L. Brantley; Rodrigo Sierra-Corona; Rurik List; David Toledo; Gerardo Ceballos (Ecology, 2010)
Megaherbivores and small burrowing mammals commonly coexist and play important functional roles in grassland ecosystems worldwide. The interactive effects of these two functional groups of herbivores in shaping the structure and function of grassland ecosystems are poorly understood. In North America's central grasslands, domestic cattle ( Bos taurus ) have supplanted bison ( Bison bison ), and now coexist with prairie dogs ( Cynomys spp.), a keystone burrowing rodent. Understanding the ecological relationships between cattle and prairie dogs and their independent and interactive effects is essential to understanding the ecology and important conservation issues affecting North American grassland ecosystems. To address these needs, we established a long‐term manipulative experiment that separates the independent and interactive effects of prairie dogs and cattle using a 2 × 2 factorial design. Our study is located in the Janos‐Casas Grandes region of northwestern Chihuahua, Mexico, which supports one of the largest remaining complexes of black‐tailed prairie dogs ( C. ludovicianus ). Two years of posttreatment data show nearly twofold increases in prairie dog abundance on plots grazed by cattle compared to plots without cattle. This positive effect of cattle on prairie dogs resulted in synergistic impacts when they occurred together. Vegetation height was significantly lower on the plots where both species co‐occurred compared to where either or both species was absent. The treatments also significantly affected abundance and composition of other grassland animal species, including grasshoppers and banner‐tailed kangaroo rats ( Dipodomys spectabilis ). Our results demonstrate that two different functional groups of herbivorous mammals, burrowing mammals and domestic cattle, have distinctive and synergistic impacts in shaping the structure and function of grassland ecosystems.

Higher dopamine transporter density in Parkinson’s disease patients with depression - Andre C. Felicio; Tais S. Moriyama; Clecio Godeiro-Junior; Ming C. Shih; Marcelo Q. Hoexter; Vanderci Borges; Sonia M. A. Silva; Edson Amaro-Junior; Luiz A. F. Andrade; Henrique B. Ferraz; Rodrigo A. Bressan (Psychopharmacology, 2010)

Myrtaceae species resistance to rust caused by Puccinia psidii - Edival A. V. Zauza; Acelino C. Alfenas; Ken Old; Michelle M. F. Couto; Rodrigo N. Graça; Luiz Antônio Maffia (Australasian Plant Pathology, 2010)

Selection of a Clostridium perfringens type D epsilon toxin producer via dot-blot test - Luciana A. Gonçalves; Zélia I. P. Lobato; Rodrigo O. S. Silva; Felipe M. Salvarani; Prhiscylla S. Pires; Ronnie A. Assis; Francisco C. F. Lobato (Archives of Microbiology, 2009)

MMP-9 and CD68+ cells are required for tissue remodeling in response to natural hydroxyapatite - Willian F. Zambuzzi; Katiúcia B. S. Paiva; Renato Menezes; Rodrigo C. Oliveira; Rumio Taga; José M. Granjeiro (Journal of Molecular Histology, 2009)

Improved Enrichment and Isolation of Polycyclic Aromatic Hydrocarbons (PAH)-Degrading Microorganisms in Soil Using Anthracene as a Model PAH - Rodrigo J. S. Jacques; Benedict C. Okeke; Fátima M. Bento; Maria C. R. Peralba; Flávio A. O. Camargo (Current Microbiology, 2009)

Fire‐related traits for plant species of the Mediterranean Basin - S. Paula; M. Arianoutsou; D. Kazanis; Ç Tavsanoglu; F. Lloret; C. Buhk; F. Ojeda; B. Luna; J. M. Moreno; A. Rodrigo; J. M. Espelta; S. Palacio; et al. (Ecology, 2009)
Plant trait information is essential for understanding plant evolution, vegetation dynamics, and vegetation responses to disturbance and management. Furthermore, in Mediterranean ecosystems, changes in fire regime may be more relevant than direct changes in climatic conditions, making the knowledge of fire‐related traits especially important. Thus the purpose of this data set was to compile the most updated and comprehensive information on fire‐related traits for vascular plant species of the Mediterranean Basin, that is, traits related to plant persistence and regeneration after fire. Data were collected from an extensive literature review and from field and experimental observations. The data source is documented for each value. Since life history traits may vary spatially or with environmental conditions, we did not aggregate them by species; i.e., traits and species are repeated in different records if they were observed by different researchers and/or in different locations. Life history traits included in the data set are: life form, resprouting ability (after fire, after clipping, or after other disturbances that remove all the aboveground biomass), resprouting bud source, heat‐stimulated germination, other germination cues, seed bank location and longevity, post‐fire seedling emergence and survival, maturity age of resprouts and saplings, and seed mass. Several traits are unknown for many species; consequently, the data set reflects the state of the knowledge on the topic. However, since the ability to resprout is a trait of paramount relevance in fire‐prone environments, it was considered a core trait in the data set, and thus species whose resprouting capacity was unknown were not included. Life form is also provided for all taxa. The structure of the database allows different levels of information (and accuracy) for each entry, and thus some traits may include different types of data (quantitative, semi‐quantitative, or categorical) from different sources. The data set is structured in 8263 records and 11 columns, obtained from 301 published and unpublished sources of information. It includes 952 taxa determined at specific or infraspecific level, which comprise 859 species, 384 genera, and 79 families. Although this is the most comprehensive data set of fire‐relevant plant traits for Mediterranean species, there is still a considerable need for observations and experiments, especially in little‐studied Mediterranean areas, such as northern Africa. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

An autochthonous case of hepatitis C virus genotype 5a in Brazil: phylogenetic analysis - Luciano C. Ribeiro; Francisco Jose Dutra Souto; Márcia P. do Espírito-Santo; Rodrigo G-Oliveira; Elisabeth Lampe (Archives of Virology, 2009)

Net ion fluxes in the facultative air-breather Hoplosternum littorale (tamoata) and the obligate air-breather Arapaima gigas (pirarucu) exposed to different Amazonian waters - Bernardo Baldisserotto; Carlos E. Copatti; Levy C. Gomes; Edsandra C. Chagas; Richard P. Brinn; Rodrigo Roubach (Fish Physiology and Biochemistry, 2008)

Molecular mapping of two loci that confer resistance to Asian rust in soybean - Danielle C. G. Silva; Naoki Yamanaka; Rodrigo L. Brogin; Carlos A. A. Arias; Alexandre L. Nepomuceno; Antônio O. Di Mauro; Selma S. Pereira; Livia M. Nogueira; André L. L. Passianotto; Ricardo V. Abdelnoor (Theoretical and Applied Genetics, 2008)

Population variation in plant traits associated with ant attraction and herbivory in Chamaecrista fasciculata (Fabaceae) - Rodrigo S. Rios; Robert J. Marquis; John C. Flunker (Oecologia, 2008)

Identification of new ABA- and MEJA-activated sugarcane bZIP genes by data mining in the SUCEST database - Paulo Sérgio Schlögl; Fábio Tebaldi S. Nogueira; Rodrigo Drummond; Juliana M. Felix; Vicente E. De Rosa; Renato Vicentini; Adilson Leite; Eugênio C. Ulian; Marcelo Menossi (Plant Cell Reports, 2008)

Guarana (Paullinia cupana var. sorbilis), an anciently consumed stimulant from the Amazon rain forest: the seeded-fruit transcriptome - Paula C. S. Ângelo; Carlos G. Nunes-Silva; Marcelo M. Brígido; Juliana S. N. Azevedo; Enedina N. Assunção; Alexandra R. B. Sousa; Fernando J. B. Patrício; Mailson M. Rego; Jean C. C. Peixoto; Waldesse P. Oliveira; Danival V. Freitas; Elionor R. P. Almeida; et al. (Plant Cell Reports, 2008)

UNB3m_pack: a neutral atmosphere delay package for radiometric space techniques - Rodrigo F. Leandro; Richard B. Langley; Marcelo C. Santos (GPS Solutions, 2008)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)

Conservation Priorities and Population Structure of Woody Medicinal Plants in an Area of Caatinga Vegetation (Pernambuco State, NE Brazil) - Rodrigo L. C. de Oliveira; Ernani M. F. Lins Neto; Elcida L. Araújo; Ulysses P. Albuquerque (Environmental Monitoring and Assessment, 2007)

Pseudomonas community structure and antagonistic potential in the rhizosphere: insights gained by combining phylogenetic and functional gene‐based analyses - Rodrigo Costa; Newton C. M. Gomes; Ellen Krögerrecklenfort; Katja Opelt; Gabriele Berg; Kornelia Smalla (Environmental Microbiology, 2007)
Summary The Pseudomonas community structure and antagonistic potential in the rhizospheres of strawberry and oilseed rape (host plants of the fungal phytopathogen Verticillium dahliae ) were assessed. The use of a new PCR‐DGGE system, designed to target Pseudomonas ‐specific gacA gene fragments in environmental DNA, circumvented common biases of 16S rRNA gene‐based DGGE analyses and proved to be a reliable tool to unravel the diversity of uncultured Pseudomonas in bulk and rhizosphere soils. Pseudomonas ‐specific gacA fingerprints of total‐community (TC) rhizosphere DNA were surprisingly diverse, plant‐specific and differed markedly from those of the corresponding bulk soils. By combining multiple culture‐dependent and independent surveys, a group of Pseudomonas isolates antagonistic towards V. dahliae was shown to be genotypically conserved, to carry the phlD biosynthetic locus (involved in the biosynthesis of 2,4‐diacetylphloroglucinol – 2,4‐DAPG), and to correspond to a dominant and highly frequent Pseudomonas population in the rhizosphere of field‐grown strawberries planted at three sites in Germany which have different land use histories. This population belongs to the Pseudomonas fluorescens phylogenetic lineage and showed closest relatedness to P. fluorescens strain F113 (97% gacA gene sequence identity in 492‐bp sequences), a biocontrol agent and 2,4‐DAPG producer. Partial gacA gene sequences derived from isolates, clones of the strawberry rhizosphere and DGGE bands retrieved in this study represent previously undescribed Pseudomonas gacA gene clusters as revealed by phylogenetic analysis.

Electrical and electronic components in the automotive sector: Economic and environmental assessment - Juan C. Alonso; Julia Dose; Günter Fleischer; Kate Geraghty; André Greif; Julio Rodrigo; Wulf-Peter Schmidt (The International Journal of Life Cycle Assessment, 2007)

Exposure of C6 glioma cells to Pb(II) increases the phosphorylation of p38MAPK and JNK1/2 but not of ERK1/2 - Thaís Posser; Cláudia B. N. Mendes de Aguiar; Ricardo C. Garcez; Francesco M. Rossi; Camila S. Oliveira; Andréa G. Trentin; Vivaldo Moura Neto; Rodrigo B. Leal (Archives of Toxicology, 2007)

Antipredator Behavior of Brown Howlers Attacked by Black Hawk-eagle in Southern Brazil - João M. D. Miranda; Itiberê P. Bernardi; Rodrigo F. Moro-Rios; Fernando C. Passos (International Journal of Primatology, 2006)

Efficient Genetic Transformation System for the Ochratoxigenic Fungus Aspergillus carbonarius - Luiz Rodrigo I. Morioka; Márcia C. Furlaneto; Andréa C. Bogas; Patrícia Pompermayer; Rubens T. D. Duarte; Maria Lúcia C. Vieira; Maria Angélica Ehara Watanabe; Maria Helena P. Fungaro (Current Microbiology, 2006)

Cytotoxic, immunosuppressive and trypanocidal activities of agrocybin, a polyacetylene produced by Agrocybe perfecta (Basidiomycota) - Luiz H. Rosa; Elaine M. Souza-Fagundes; Kátia M.G. Machado; Tânia M. A. Alves; Olindo A. Martins-Filho; Alvaro J. Romanha; Rodrigo C. Oliveira; Carlos A. Rosa; Carlos L. Zani (World Journal of Microbiology and Biotechnology, 2006)

Use of plant growth regulators in micropropagation of Kappaphycus alvarezii (Doty) in airlift bioreactors - Julieta Muñoz; Armando C. Cahue-López; Rodrigo Patiño; Daniel Robledo (Journal of Applied Phycology, 2006)

Testing time–place learning in the cichlid fish Nile tilapia - Helton C. Delicio; Ana C. Luchiari; Rodrigo E. Barreto; Ana L. Marcondes (Journal of Ethology, 2006)

Unusual Orofacial Manifestations of Histoplasmosis in Renal Transplanted Patient - Ana Carolina F. Motta; Rodrigo Galo; Alan Grupioni Lourenço; Marilena C. Komesu; Darlene Arruda; Fabiana Guerra Velasco; Beatriz C. Garcia; Norma T. Foss (Mycopathologia, 2006)

Quantitative trait loci for grain moisture at harvest and field grain drying rate in maize (Zea mays, L.) - Rodrigo G. Sala; Fernando H. Andrade; Elsa L. Camadro; Julio C. Cerono (Theoretical and Applied Genetics, 2006)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Pneumococcal bacteremia in children: an 8-year review in two hospitals in Barcelona - A. Prez; P. Sala; M. Gimnez; M. Sierra; A. Esteve; A. Alonso; M. Quesada; F. Raspall; V. Ausina; C. Rodrigo (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Inferring nocturnal surface fluxes from vertical profiles of scalars in an Amazon pasture - Otávio C. Acevedo; Osvaldo L. L. Moraes; Rodrigo Da Silva; David R. Fitzjarrald; Ricardo K. Sakai; Ralf M. Staebler; Matthew J. Czikowsky (Global Change Biology, 2004)
Ecosystem carbon budgets depend on there being good representative surface flux observations for all land use types during the entire diurnal cycle. In calm conditions that often occur at night, especially in areas of small roughness (such as pastures), ecosystem respiration rate is poorly measured using the eddy covariance (EC) technique. Nocturnal vertical profiles of temperature, humidity and winds were observed using tethered balloon soundings in a pasture in the eastern Amazon during two campaigns in 2001. The site is characterized by very weak winds at night, so that there is insufficient turbulence for the EC technique to determine fluxes accurately. To compensate, the time evolution of the profiles is used to determine surface fluxes at early morning and these are compared with those observed by EC at a nearby micrometeorological tower. The nocturnal boundary layer thickness h is determined as the height to which the surface fluxes must converge so that energy budget closure is achieved. The estimated values range from 30 m, around 22:00 hours LST, to more than 100 m just before dawn. These are in good agreement with the observed thickness of a frequently observed fog layer during the middle of the night. During the early portion of the night, when the accumulation layer is shallow, there is appreciable decrease of dCO 2 /d t with height. On calm nights, CO 2 accumulation rate is larger near the surface than at higher levels. On windier nights, this accumulation rate is vertically uniform. Hence, extrapolation of tower profiles for estimating fluxes must be done carefully. Although uncertainties remain large, an alternate approach to the EC method is described for measuring nighttime surface CO 2 fluxes under stable atmospheric conditions.

Land‐use change effects on local energy, water, and carbon balances in an Amazonian agricultural field - Ricardo K. Sakai; David R. Fitzjarrald; Osvaldo L.L. Moraes; Ralf M. Staebler; Otávio C. Acevedo; Matthew J. Czikowsky; Rodrigo da Silva; Eleazar Brait; Valdelirio Miranda (Global Change Biology, 2004)
To study how changing agricultural practices in the eastern Amazon affect carbon, heat and water exchanges, a 20 m tower was installed in a field in August 2000. Measurements include turbulent fluxes (momentum, heat, water vapor, and CO 2 ) using the eddy covariance (EC) approach, soil heat flux, wind, and scalar profiles ( T , q , and CO 2 ), soil moisture content, terrestrial, total solar radiation, and photosynthetically active radiation (PAR, 400–700 nm). At the beginning of the measurements, in September 2000, the field was a pasture. On November 2001, the pasture was burned, plowed, and planted in upland (nonirrigated) rice. Calm nights were the norm in this site. Anomalously low values of net ecosystem exchange (NEE) were found using the EC method, even when the common criterion u * −1 was used to identify and exclude poor performance nights. We observed more plausible values of NEE using criterion u * −1 , indicating that the criterion must be revised downward for flow over surfaces smoother than forests. However, even using the lower threshold, u * was lower than this limit for 82% of nights, and this led to nocturnal respiration underestimates. We compensate for this difficulty by estimating the respiration rate using the nocturnal boundary layer budget method. Land‐use change from pasture to rice cultivation strongly affected both diurnal rates of turbulent exchange but also the pattern of seasonal variation. Seasonal wet and dry season differences in vegetation state were clearly detected in the albedo and PAR‐albedo. These reflectivity changes were accompanied by modified net radiative flux, turbulent heat flux and evaporation rates. The highest evaporation rate was observed during the rice crop, when the field had total evaporation approximately half the precipitation input, less than that of the surrounding forest. Effects of the land‐cover changes were also detected in the carbon budget. For the pasture, the maximum CO 2 uptake occurred in May, appreciably delayed from the start of the rainy season. After the field was plowed and the soil was exposed and there was efflux of CO 2 to the atmosphere day and night for an extended period. Highest values of carbon uptake occurred during the rice plantation. Although the upland rice took up carbon at double the rate of the pasture that it replaced, the field was left fallow for much of the year, during the dry season.

Use of Quantitative and Semiquantitative Procalcitonin Measurements to Identify Children with Sepsis and Meningitis - M. Azuara; S. Blanco; V. Ausina; J. Domnguez; C. Rodrigo; C. Prat; M. Gimnez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Altered Modulation of Soluble Guanylate Cyclase by Nitric Oxide in Patients with Liver Disease - R. Corbalán; C. Montoliu; M. D. Miñana; J. A. Del Olmo; M. A. Serra; L. Aparisi; J. M. Rodrigo; V. Felipo (Metabolic Brain Disease, 2002)

Avoiding offshore transport of competent larvae during upwelling events: The case of the gastropod Concholepas concholepas in Central Chile - Elie Poulin; Alvaro T. Palma; Germán Leiva; Diego Narvaez; Rodrigo Pacheco; Sergio A. Navarrete; Juan C. Castilla (Limnology and Oceanography, 2002)
The coast of central Chile is characterized by the occurrence of coastal upwelling during the austral spring and summer seasons, which probably has important consequences for the cross‐shelf transport of larval stages of many species. Three cruises were conducted off the locality of El Quisco during upwelling‐favorable wind periods to determine the surface distribution of epineustonic competent larvae of the gastropod Concholepas concholepas during such events. Contrary to the predictions of a traditional model, where neustonic‐type larvae are transported offshore under such conditions, competent larvae of this species were exclusively found in the area between the shore and the upwelling front. Two additional cruises were conducted during calm periods to determine diel variation in the vertical distribution of C. concholepas competent larvae. The absence of competent larvae at the surface during early night hours suggests a reverse vertical migration. Thus, the retention of C. concholepas competent larvae in the upwelled waters could be the result of the interaction between their reverse diel vertical migration and the typical two‐layer upwelling dynamics.

The Na + -activated K + channel contributes to K + efflux in Na + -loaded guinea-pig but not rat ventricular myocytes - Lawrence C.; Rodrigo G. (Pflügers Archiv - European Journal of Physiology, 2001)

Intercropping of immature rubber in Sri Lanka: present status and financial analysis of intercrops planted at three densities of banana - V. H. L. Rodrigo; C. M. Stirling; R. M. A. K. B. Naranpanawa; P. H. M. U. Herath (Agroforestry Systems, 2001)

Up-regulation of neuronal NO synthase immunoreactivity in opiate dependence and withdrawal - B. Cuéllar; A. P. Fernández; I. Lizasoain; M. A. Moro; P. Lorenzo; M. L. Bentura; J. Rodrigo; J. C. Leza (Psychopharmacology, 2000)

Behavioral Correlates of Dispersal in Female Muriquis (Brachyteles arachnoides) - Rodrigo C. Printes; Karen B. Strier (International Journal of Primatology, 1999)

Comparison of drainage estimation methods in irrigated citrus orchards - A. Lidón; C. Ramos; A. Rodrigo (Irrigation Science, 1999)

A Na + -activated K + current ( I K,Na ) is present in guinea-pig but not rat ventricular myocytes - C. Lawrence; G. C. Rodrigo (Pflügers Archiv - European Journal of Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Investigating the molecular basis of desiccation tolerance using the resurrection plant Craterostigma plantagineum as an experimental system - D. Bartels; J. Chandler; C. Bockel; W. Frank; M. Kleines; M. J. Rodrigo; J. Phillips; J. -B. Mariaux; A. Furini; F. Salamini (Acta Physiologiae Plantarum, 1997)